A novel Csi-miR20 targets CsMT760 to regulate lignification-associated postharvest resistance against Penicillium digitatum in citrus fruit - Jixin Tian; Wenjun Wang; Ou Chen; Xindan Li; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2027)

Energy evolution and fracture mechanisms of single-fissure rock-like specimens subjected to pore water pressure - Shuguang Zhang; Junkang Zhao; Shutian Zhao; Wenbo Liu; Yipin Liu; Xiaodong Sun; Wenwu Ou; Yingbo Li; Xiangpan Zeng; Gui Cheng (European Journal of Environmental and Civil Engineering, 2026)

Can the ecological transition of cropland use narrow rural-urban income inequality? Evidence from China’s Huang-Huai-Hai Region - Linpeng Yang; Yansui Liu; Cong Ou; Yurui Li (Land Use Policy, 2026)

Geochemical characteristics of tourmaline in Longqiao skarn Fe deposit in LYRMB, Eastern China: Constraints on magmatic-hydrothermal processes - Shasha Liu; Yu Wang; Mingguang Sun; Zhuang Zhao; Hui Luo; Muhammad Hafeez; Linzi Li; Xiaoyong Yang; Jiandong Sun; Bangguo Ou (Journal of Geochemical Exploration, 2026)

Untangling how thermal pretreatment and distiller’s grains enhance humification and reduce emissions in food waste residue composting - Qinghong Jiang; Yun Xu; Peng Xu; Yuanji Kang; Rongtao Ou; Xiaoqing Wu; Xuya Peng; Lei Li (Bioresource Technology, 2026)

Genome-wide analysis of cation-proton antiporter (CPA) family involved in salt stress tolerance in pepper (Capsicum annuum L.) - Yitong Cheng; Yuanyuan Ding; Jiaxue Guo; Yuyang Li; Shengbao Yang; Lijun Ou (Molecular Biology Reports, 2026)

Large-scale mitogenome analysis reveals complex maternal genetic connections between Sino-Tibetan- and Altaic-speaking populations - Yutong Jiang; Lintao Luo; Yunhui Liu; Lingqing Ou; Jiayan Liang; Limei Zhang; Moru Guo; Yanling Liu; Jie Zhong; Bowen Li; Zihao Zhu; Yuzhu Wang; et al. (Human Genetics, 2026)

A data-driven framework for effective single-group cross section adjustment in point-depletion burnup calculations - Wei-Jia Meng; Te Sheng; Ou-Yi Li; Gang-Lin Yu (Annals of Nuclear Energy, 2026)

Multi-component crustal recycling recorded by LiMg isotopes in Emeishan mafic–ultramafic layered intrusions with implications for Fe–Ti–V metallogeny - Yan-Fang Luo; Dong-Bo Tan; Hai-Ou Gu; Yang-Yang Wang; He Sun; Dong-Yong Li; Qian-Ling Zhou; Shi-Chu Zhao; Yilin Xiao (Lithos, 2026)

Asynchronous variation between aboveground carbon storage and structural complexity motivates stage-specific structural regulation across successional stages in Pinus kesiya var. langbianensis secondary forests - Zhi Liu; Hongbin Luo; Yong Wu; Shiqi Su; Yuansu Xu; Jing Li; Zhibo Yu; Lei Bao; Zongjian Peng; Hao Zhou; Xiaohan Liu; Weibin Wang; et al. (Forest Ecology and Management, 2026)

Testing and design analysis of WAAM high strength steel square hollow sections in compression - Ren Li; Andi Su; Yuyin Wang; Ou Zhao (Engineering Structures, 2026)

Performance of base-isolated structures with eddy current damper tuned tandem mass dampers-inerters considering soil–structure interaction - Yuqing Ou; Liyuan Cao; Wenhan Yin; Chunxiang Li; Xin Li (Soil Dynamics and Earthquake Engineering, 2026)

U-series and OSL dating of late Pleistocene mammal fossils in Lower Pubu Cave, South China - Jiemei Zhong; Wei Liao; Yanyan Yao; Chun Tian; Guoshan Li; Qingfeng Shao; Xianjiao Ou; Wei Wang (Quaternary International, 2026)

Seven undescribed steroidal glycosides with CYP3A4 inhibitory activity from the stems of Marsdenia tenacissima - Bian-Xia Xue; Dong Zhang; Qing-Xia Li; Ze-Min Ou; Chun Li; Li-Hua Yan; Xiao-Qian Liu; Zhi-Min Wang (Phytochemistry, 2026)

Clay-infilled micro-scaffolding: 3D preservation of Tannuolina (tommotiid) in the Cambrian Hongjingshao Formation, South China - Ruibing Liu; Qiang Ou; Ben Yang; Guoxiang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Light Mo isotope composition of arc front adakites from western Northern Luzon, Philippines: products of fore-arc subduction erosion? - Xin-Feng Ou; Hai-Quan Liu; Graciano P. Yumul; Carla B. Dimalanta; Betchaida D. Payot; Gabriel Theophilus V. Valera; Jie Li; Le Zhang; Xiao-Long Huang; Yi-Gang Xu (Lithos, 2026)

Quantifying hillslope-to-river phosphorus contributions to water quality through a cascading framework of hydrological connectivity - Yanan Wang; Guishan Yang; Weixin Ou; Hengpeng Li (Journal of Hydrology, 2026)

Biological pretreatment of lignocellulosic biomass for biofuels: An overview and new insights - Yingnan Liu; Ou Li; Fuping Zheng; Amin Amani; Wensheng Qin (Journal of Environmental Chemical Engineering, 2026)

Sulfur-release paper treatment delays longan pericarp browning involving flavonoid branch remodeling and the attenuation of enzymatic oxidation - Yongqi Chen; Md Mahfuzur Rob; Dongmei Han; Tao Luo; Difa Zhu; Jingyi Li; Wenbo Ou; Chulin Zhou; Chenning Ning; Zhenxian Wu (Food Research International, 2026)

Highly selective NO2 sensing for mobile on-site monitoring enabled by a dual-sensitization mechanism in palladium sulfide-based nanocomposites - Yongjing Guo; Hangshuo Feng; Qiuni Zhao; Shenghui Guo; Renminxi Ou; Shunping Zhang; Zaihua Duan; Yi Xia; Zhen Yuan; Ming Hou; Li Yang; Huiling Tai (Chemical Engineering Journal, 2026)

Doping of polycyclic aromatic chromophores into melamine-formaldehyde networks: An organic room-temperature phosphorescence platform with high stability and excellent processability - Xichang Ou; Shijun Lu; Zhaowei Lan; Qianyi He; Shaolin Lu; Shaoheng Yang; Laixing Pang; Jing Li; Dengchong Feng; Qi Guo; Yuzhao Yang; Zhongke Yuan; et al. (Chemical Engineering Journal, 2026)

Anaerobic digestion of recalcitrant organics and emerging contaminants in pharmaceutical wastewater for carbon neutrality and bioresource recovery: A critical review - Xinru Niu; Tao Zhang; Yao Xu; Jiaxin Ou; Chengzhen Meng; Fan Li; Lan Tang; Yong Hu; Chao Rong; Dapeng Li; Zhe Kong (Bioresource Technology, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Dual-ionic strategy modulates fibroblast fate for dynamically preventing ventricular aneurysm in mice - Yuxuan Pan; Jianfeng Zhong; Xiliang Mo; Chi Zhang; Shanghai Li; Xu Shi; Xiaodong Ning; Xueting Liu; Xueqin Shi; Jiaqi He; Yanan Jia; Bin Yu; et al. (Chemical Engineering Journal, 2026)

Allroad-SLAM: Factor graph-based 3D reconstruction in diverse road scenarios with a consumer-grade GNSS-LiDAR-inertial system - Xuzhe Duan; Pengcheng Zhao; Wenwu Ou; Guangshuo Zhu; Mingyao Ai; Jiayuan Li; Xujie Zhang; Ju Zhang; Qingwu Hu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Hydrogeochemical constraints on the genesis, fluid mixing, and heavy metal mobilization of low-temperature geothermal systems in the Mufushan granite batholith, South China - Linxin Li; Zhengqing Wu; Lei Wang; Jian Ou; Jing Pi; Sheng Liu; Lala Wei; Liuqin Huang; Hongchen Jiang; Yanlong Dong (Geothermics, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

A visual dual-signal paper biosensor based on CRISPR/Cas12a and nanozyme-responsive hydrogel for ultrasensitive detection of aflatoxin B1 - Lihua Fan; Mingying Hu; Zongyuan Ou; Fan Li; Yiheng Shi; Di Wu; Yongning Wu; Guoliang Li (Food Bioscience, 2026)

An interpretable data-driven intelligent prediction framework for wind turbine wake turbulence intensity based on machine learning model - Zhengnong Li; Yaowei Fan; Terigen Bao; Ou Pu (Engineering Structures, 2026)

Operationalizing the serviceshed concept to enhance the effectiveness and equity of flood regulation services in systematic conservation planning - Xue Ding; Jun-Long Huang; Yu Tao; Jiman Li; Henghui Xi; Weixin Ou (Environmental Impact Assessment Review, 2026)

Multifunctional aramid honeycombs filled with PVDF composite foams via in situ supercritical foaming: Nearly-isotropic broadband microwave absorption and mechanical reinforcement - Yang Ou; Hongbo Hou; Jingfeng He; Wenhan Cui; Jiaju Zhu; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2026)

Combinatorial flora C1 enhances urea utilization and bioconversion efficiency in black soldier fly larvae - Dan Shao; Chaowei Qin; Yongqing Niu; Yani Ou; Zhenyu Zhang; Qing Li; Menghong Dai (Biomass and Bioenergy, 2026)

Diurnal variations of organic molecules in atmospheric PM2.5 in urban areas of the Yangtze River Basin, China characterized by UHPLC–Orbitrap MS - Xin Ou; Lijuan Li; Xin Qi; Jiawei Zhou; Hanxiong Che; Zhier Bao; Yiliang Liu; Lingshuo Meng; Xin Long; Xiaojiang Yao; Shumin Zhang; Yang Chen (Atmospheric Environment, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Multifaceted assessment of recent saltwater intrusion along China’s coasts - Nan Xu; Zihao Zhang; Hao Xu; Jiaqi Yao; Hui Lu; Wenjia Cai; Yifu Ou; Hong Luan; Peng Gong; Wei Tu; Qingquan Li (Science Bulletin, 2026)

A VvETC3-linked repressive layer mediates extracellular self-DNA–primed resistance to gray mold in postharvest grapes - Chunhong Li; Yijia Xia; Siyu Ou; Kejiang Chen; Fei Xiang; Kaituo Wang; Jun He; Minghua Zhou; Yonghua Zheng (Postharvest Biology and Technology, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Microcystin-LR induces dopaminergic neurodegeneration by MyD88-dependent neuroinflammation in zebrafish (Danio rerio) - Ya He; Kang Ou-Yang; Hui Yang; Liangmou Wang; Mengya Li; Dapeng Li; Li Li (Journal of Hazardous Materials, 2026)

Structural and physicochemical responses of seaweed-derived insoluble dietary fiber to temperature-controlled steam explosion: A case study on Porphyra haitanensis - Yujia Ou; Binhui Zhou; Yesong Wang; Tao Hong; Lijun Li; Zedong Jiang; Hui Ni; Jun Lu; Mingjing Zheng (Innovative Food Science & Emerging Technologies, 2026)

Rock surface luminescence dating of the 2000 CE Yigong Flood Cobbles, southeastern Tibet: Implications for dating catastrophic outburst flood events - Anna Yang; Xianjiao Ou; Xinlei Ma; Xinzheng Li; Hao Wang; Yang Li; Kunmei Yang; Yantian Xu; Weiming Liu (Geomorphology, 2026)

Universal primer-based RPA combined with parallel CRISPR/Cas12a decoding for rapid multi-species meat authentication - Shuang Han; Xinyi Lin; Yuting Lei; Zhen Liu; Jiayang Li; Xueling Ou (Food Chemistry, 2026)

Metagenomic and metabolomic integration reveals microbial mechanisms underlying low-temperature-driven flavor diversity in backslopped wheat sourdough - Yuan Zheng; Linyi Lei; Yixue Ou; Qin Li; Kaidi Hu; Ning Zhao; Jianlong Li; Shuliang Liu; Shujuan Chen; Aiping Liu (Food Bioscience, 2026)

Seismic performance of novel prefabricated self-centering shear walls based on UHPC - Gao Ma; Jiang Wang; Hyeon-Jong Hwang; Ou Yang; Su-Min Kang; Tiantian Li (Engineering Structures, 2026)

CRISPR-Cas12a-coupled split-promoter activator bridge enables reusable one-reporter-multiple-target cell-free nucleic acid diagnostics - Fengling Fang; Mingming Zhao; Weiquan You; Xiangjun Tang; Shanjian Chen; Yao Yin; Qishui Ou; Yueguo Li; Ya Fu (Chemical Engineering Journal, 2026)

Upgrading industrial electrolytic MnO2 to highly active MnO/C supercapacitor electrode materials via composite-carbon-assisted solid-phase transition - Jiangtao Liu; Kaiwen Zhang; Yifan Li; Yang Zhou; Yuan Qin; Zihao Ou; Zhenbo Wang; Wenliang Feng; Bin Xiang; Xuefeng Zou (Chemical Engineering Journal, 2026)

Optimization of indoor airflow distribution for air cleaners using a CFD–random forest approach - Yuzhan Ma; Angui Li; Ou Han; Jing Xiong; Baoyun Bu (Building and Environment, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Mechanical behavior and critical state constitutive model of granite soil-rock mixture subjected to drying-wetting cycles - Youneng Liu; Hongming Li; Hongri Zhang; Dongyi Ya; Ou Guo; Tianzhu Lan; Jianqing Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Prenatal exposure to polystyrene nanoplastics impairs offspring fertility in mice by disrupting meiotic recombination and chromatin accessibility in oocytes - Xu Zhou; Di Zhang; Liangran Zhang; Shunxin Wang; Wei Shen; Xiang-Hong Ou; Guang Wang; Qing-Yuan Sun; Fali Zhang; Weidong Li (Archives of Toxicology, 2026)

SAR-based monitoring of shipping reorganization under a maritime chokepoint disruption: Evidence from the Strait of Hormuz crisis - Haotian Yang; Nan Xu; Jihong Chen; Yuhao Wang; Yinxia Cao; Fenzhen Su; Han-Su Zhang; Chunpeng Chen; Yifu Ou; Qingquan Li (Ocean & Coastal Management, 2026)

Research on Cloud Water Resources in the Bayinbuluke Alpine Basin: Climatic Characteristics and Development Potential - Miao Cai; Junjie Zhao; Jianjun Ou; Jie Yu; Gang Li; YuQuan Zhou (International Journal of Climatology, 2026)
Under the context of global climate change exacerbating water resource crises in arid and semi‐arid mountainous regions, the scientific assessment and development of cloud water resources (CWR) are of great significance for regional water security and ecological safety. Based on a high‐resolution CWR diagnostic dataset of China from 2000 to 2024, this study quantitatively evaluates the spatiotemporal distribution and development potential of CWR in the Bayinbuluke alpine basin (BAB)—a typical arid zone in Central Asia. The main findings are as follows: (1) Over the past 25 years, the average annual total hydrometeor mass (cloud water) in this region were about 56.89 billion tons (equivalent to a water depth of ~86.4 mm per unit area), of which about 17.32 billion tons (~239.5 mm) formed surface precipitation. The precipitation efficiency of hydrometeors was about 30.5%, with a slow renewal cycle of ~10.8 h; (2) The average annual aerial CWR (i.e., total hydrometeors minus precipitation) in the mountainous area was about 39.56 billion tons, showing significant seasonal variations—most abundant in summer, followed by spring, and least in winter, consistent with the seasonal distribution of precipitation; (3) Considering the demand and technical methods for cloud water resource development, and after excluding days without precipitation and days with heavy precipitation, the developable potential of CWR is estimated to account for 32.8%–50.5% of the total, that is, ~12.98–19.98 billion tons per year (about 179.4–276.2 mm/year). The study recommends implementing regular cold‐cloud seeding (rain/snow enhancement) operations from May to October each year to improve the effective utilization of CWR. This research provides a scientific basis for water resource management in the BAB and serves as a reference for CWR development in similar arid and semi‐arid regions globally.

Exploration of the construction of a food safety risk index evaluation system for chemical contaminants in fresh vegetables - Yijun Ou; Zhiheng Lai; Yuhua Zhang; Yanyan Wang; Yan Li; Rongfei Peng; Zhijun Bai; Sixuan Wu; Jiangbo Lei; Weiwei Zhang (Food Additives & Contaminants: Part A, 2026)

Numerical investigation on liquefaction-induced deformation behavior of sandy foundations under railway embankments - Jinqiao Zhao; Xuanming Ding; Siau Chen Chian; Weiting Deng; Shengnan Li; Qiang Ou (Transportation Geotechnics, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Non-linear responses of ecosystem service trade-offs to landscape heterogeneity: implications for spatially targeted landscape management in an urbanizing agricultural basin - Jiman Li; Henghui Xi; Fei Wang; Xue Ding; Xufei Chen; Yu Tao; Conghong Huang; Qin Tao; Xianbo Cheng; Weixin Ou (Landscape and Urban Planning, 2026)

Deciphering antibiotic resistome in sulfate-reducing bacteria from uranium mining-impacted ecosystems: Distribution, mobility, and links to sulfur metabolism - Shuai Zhou; Xiulan Ou; Fengjuan Yang; Jian Song; Shuang Li; Chao Xiang; Xin Liu; Weigang Wang; Gang Guo; Yinglong Su; Yuanyuan Gao; Yi Duan (Journal of Environmental Sciences, 2026)

Boosting photocatalytic hydrogen evolution by engineering a Yb-O-Ti electron bridge in ytterbium metalloporphyrin MOFs nanohybrid - Zhiyong Ou; Qiaona Sun; Lixia Qin; Taiyang Zhang; Shi-Zhao Kang; Xiangqing Li (Fuel, 2026)

Squid cartilage-derived chondroitin sulfate from Uroteuthis chinensis: a novel marine prebiotic modulating gut microbiota and ameliorating ulcerative colitis - Shiwei Chen; Hanjing Li; Rongkun Chen; Zihua Liang; Zongjie Ou; Pengzhe Zhang; Li Ni; Jiacong Deng; Xucong Lv (Food Research International, 2026)

Photo-responsive films in food packaging: mechanisms, preparation, applications, and machine learning optimization - Haifei Ou; Dandan Zhou; Zhaxi Cairang; Donglu Fang; Chong Shi; Yaqiong Wu; Gongjian Fan; Caie Wu; Weilin Li (Food Research International, 2026)

Improvement of physicochemical and functional properties and potential bioaccessibility of rare ginsenoside Rg3 loaded on modified porous cassava starch - Wen-ting Wang; Hui-min Guo; Sheng-yuan Guo; Wen-jun Ou; Fei Gao; Kai-mian Li; Li-zhen Zhang; Gui-xing Ren (Food Chemistry, 2026)

Antimicrobial hydrogel based on Schiff base-crosslinked dialdehyde microfibrillated cellulose/carboxymethyl chitosan for loquat preservation: High efficiency and mechanism - Xinhui Zhang; Zhaxi Cairang; Chong Shi; Mengyang Xu; Haifei Ou; Donglu Fang; Weizhong You; Hongli Qie; Yicheng Wang; Yaqiong Wu; Lianfei lyu; Zhengjin Huang; et al. (Food Hydrocolloids, 2026)

Comparative evaluation of pH-responsive electrospun nanofiber films: Influence of anthocyanin profiles from six blueberry cultivars for intelligent pork freshness monitoring - Mengyang Xu; Zhaxi Cairang; Haifei Ou; Lanlan Du; Chong Shi; Shuqiong Xia; Fengyi Zhao; Lianfei Lyu; Yaqiong Wu; Fuliang Cao; Donglu Fang; Weilin Li (Food Packaging and Shelf Life, 2026)

Climate-adaptive restructuring of nitrogen inputs to mitigate global trade-offs among fertilizer use, crop yield, and N₂O emissions - Jiman Li; Conghong Huang; Jiaguo Qi; Steve Pueppke; Henghui Xi; Xue Ding; Jinling Luo; Fengyi Du; Dan Kou; Yu Tao; Weixin Ou (Environmental Impact Assessment Review, 2026)

Interface-resolved investigation of flow and transport modulation in heterogeneous porous media - Zhisong Ou; Qiang Xue; Yong Wan; Jiangshan Li (Computers and Geotechnics, 2026)

Engineered antibacterial-based repair peptide platform for the treatment of infected tissues - Hongchuan Wang; Liang Ma; Bide Tong; Shun Zhang; Gang Li; Huaizhen Liang; Hanpeng Xu; Di Wu; Zixuan Ou; Yifan Du; Shuchang Peng; Shihao Zhang; et al. (Chemical Engineering Journal, 2026)

Cancer cell membrane-camouflaged magnetic nanoliposome regulated tumor stemness and immune activation to inhibit the growth and metastasis of triple-negative breast cancer - Yue Wang; Canhong Ou; Jiwang Huang; Zhaowang Ning; Maoyang Wang; Geng Tian; Li Zhang; Guilong Zhang; Wenjuan Gao (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Ternary lithium-ion battery cathode material NCM523 impairs planarian locomotor activity, growth and regeneration - Zhicheng Chen; Yufan Deng; Ying Li; Luyin Wu; Shuhan Zheng; Ziyi Wang; Shi Chen; Yixian Ren; Yuxia Zhang; Shihao Tang; Zhi Wang; Zejin Ou (Aquatic Toxicology, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Mume Flos ameliorates MASLD-associated cognitive impairment by attenuating IL-17/NF-κB-mediated metabolic neuroinflammation - Shuqin Cui; Yali Wang; Qi Zhang; Hongyun Li; Wanting Hu; Fan Yang; Wei Zhang; Jinmei Ou (Metabolic Brain Disease, 2026)

Moderate net-chasing enhances stress resilience in freshwater prawns Macrobrachium rosenbergii: evidence from behavioral and physiological recovery - Jiangtao Li; Jiale Zhou; Licheng Zeng; Yingtong Ou; Zhongjie You; Zheng Xiao; Jianjun Guo; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Highland Barley's future: Processing innovation empowers emerging opportunities in global health foods and sustainable agriculture - Xinlai Dou; Luman Sang; Liangxing Zhao; Yiqing Zhu; Shumin Shu; Yan Zhang; Jing Ou; Hongying Hua; Ge Li; Yong Xue; Qingyu Zhao; Chao Wang; et al. (Trends in Food Science & Technology, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Stability and long-term strategies for poverty alleviation in China from the perspective of multi-dimensional relative poverty: Nationwide county-level analysis - Wenxin Li; Qun'ou Jiang; Lidan Xu; Xiangzheng Deng; Yufei Ren; Chunhong Zhao (Journal of Rural Studies, 2026)

Garnet’s impact on the petrogenesis of Himalayan leucogranites - Dong-Yong Li; Fang-Zhen Teng; Yilin Xiao; Zhi-Chao Liu; Hai-Ou Gu; Wang-Ye Li; Xiao-Chi Liu; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Phosphorylated chitosan in-situ ionic self-crosslinked sulfonated poly(etherether ketone) proton exchange membrane for direct methanol fuel cells” [Fuel 427(Part E) (2027) 140108] - Zhuo Li; Guoliang Liu; Fuqiang Hu; Ying Ou; Ting Qu; Yong Liu; Fan Cheng; Quanyuan Zhang; Zushun Xu; Hai Liu; Jie Wang (Fuel, 2026)

Effect of Bangia fusco-purpurea polysaccharides fermented with Enterococcus faecium on enhancing intestinal barrier function - Wenqin Yang; Yuanfan Yang; Ruobing Dai; Yujia Ou; Tao Hong; Zhipeng Li; Yanbing Zhu; Hui Ni; Zedong Jiang; Mingjing Zheng (Food Bioscience, 2026)

Aeromonas hydrophila induces mitophagy for intracellular survival through its secreted effectors in the splenic macrophages of grass carp (Ctenopharyngodon idella) - Xiaoyu Ma; Rong Ye; Wansong Li; Zhenhong Ou; Hong Zhou (Fish & Shellfish Immunology, 2026)

Seismic performance of a full-scale modular steel structure with high-performance grouted joints: Experimental study on global response - Chao Yang; Xiaoguang Wang; Lifei Feng; Siqi Ding; Shan Cang; Zuohua Li; Qiong Wang; Jinping Ou (Engineering Structures, 2026)

Electrochemical construction of Turing-patterned plasmonic MOF substrate for machine learning-assisted SERS analysis of volatile organic compounds - Weihui Ou; Kai Wu; Zhijian He; Junda Shen; Xuanhe Hu; Jiangtao Li; Rui Lang; Jian Lu; Jun He (Chemical Engineering Journal, 2026)

The Effects of Exogenous Cadmium Tolerant Bacteria on the Growth and Physiology of Wheat Seedlings Under Cadmium Stress - Yuting Shi; Riping Duan; Xinyi Gao; Zhouyan Ou; Linya Li; Bohan Zhang; Junli Li (Journal of Soil Science and Plant Nutrition, 2026)

Regulating grain production-water purification trade-offs through landscape structure in a large-scale basin: insights from the pattern-process-service framework - Jiman Li; Henghui Xi; Xue Ding; Jinling Luo; Fengyi Du; Conghong Huang; Yu Tao; Weixin Ou (Applied Geography, 2026)

Research on the Adaptive Response Mechanism of Bacterial Infection in Triplophysa siluroides - Yuanliang Duan; Ya Liu; Jun Ou; Feiyang Li; Xiaoyun Wu; Jianshen Lai; Jian Zhou; Mingjiang Song (Fishes, 2026)
Triplophysa siluroides, a unique species of plateau fish, holds significant economic value. However, its natural population has sharply declined due to overfishing and the construction of water conservancy projects. Investigating the various conditions necessary for its growth is a crucial prerequisite for successful artificial breeding. This study used Edwardsiella tarda as the pathogenic bacterium to determine the median lethal concentration following infection of T. siluroides, as well as to examine changes in tissues, organs, and gene expression. The study found that dead T. siluroides displayed symptoms such as abdominal distension, fluid accumulation, and a reddened anus, and the median lethal concentration of E. tarda for T. siluroides was calculated to be 1.00 × 106 CFU/mL. Following infection with E. tarda, the liver, intestine, gills, spleen, and kidneys exhibited varying degrees of lesions. Transcriptome sequencing identified a total of 54,667 genes. Compared to the blank control group, 192 genes were downregulated and 125 genes were upregulated in T. siluroides infected with E. tarda. In contrast, after infection with the poly(I:C) viral mimic, 225 genes were downregulated and 436 genes were upregulated. This study determined the median lethal concentration of E. tarda for T. siluroides via intraperitoneal injection under laboratory conditions. The results may contribute to disease prevention and control in the breeding of T. siluroides, as well as inform future risk assessments of infection in aquaculture water bodies.

Development of rapid visual LAMP-based assay and nanoencapsulated carvacrol formulation for early detection and sustainable management of Fusarium solani in Morchella esculenta - Ju Ou; Minggui Ou; Qingyin Liu; Xuemei Lu; Bangxi Zhang; Ming Li; Rongyu Li (Crop Protection, 2026)

Exploring sustainable pathways and strategies for China’s “Shan-Shui” ecological restoration initiatives - Tao Liu; Le Yu; Xin Chen; Yanshu Liu; Cong Ou; Zhengrong Du; Zhouyuan Li; Dailiang Peng (Science Bulletin, 2026)

Oxygen vacancy-driven coherent interface engineering boosts carbon-coated LiNiO2 performance - Yucen Yan; Bianzheng You; Jiping Sun; Zhixing Wang; Guochun Yan; Huajun Guo; Xinhai Li; Wenjie Peng; Gui Luo; Guangchao Li; Bichao Wu; Xing Ou; et al. (Science Bulletin, 2026)

Machine learning-based identification of dominant phytoplankton species in the Gouqi Island mussel aquaculture area of the East China Sea - Y. Fang; Q.W. Ou; Z.L. Wu; Z.Y. Gou; X. Zhao; P.L. Li; H. Huang (Regional Studies in Marine Science, 2026)

Mantle eclogite evidence of subducted carbonate sediments in Earth’s deep carbon cycle - Jing Sun; Ross N. Mitchell; Luc S. Doucet; Kouki Kitajima; Ranpeng Li; Jinglin Su; Qiqi Ou; Tanya Kalashnikova; Sergey I. Kostrovitsky (Gondwana Research, 2026)

Soil heterogeneity shapes the responses of soybean yields to changing climates in China - Wenyao Yan; Fangzheng Chen; Junji Ou; Tingyin Li; Jian Liu; William David Batchelor; Yong Chen; Kelin Hu; Puyu Feng (European Journal of Agronomy, 2026)

Deciphering solute transport in crack networks-clay matrix systems: Insights from experiments and numerical modeling - Li Luo; Yong He; Gezhi Ou; Zhao Zhang; Kao-fei Zhu; Xiang-hong Ding (Engineering Geology, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Experimental Study on Shear Anisotropy and Anchoring Mechanism of Fractured Rock Masses - Shuguang Zhang; Jiamian Lin; Wenbo Liu; Xiang Huang; Dipeng Zhu; Wenwu Ou; Shutian Zhao; Yipin Liu; Yingbo Li (Geotechnical and Geological Engineering, 2026)

Foliar dust retention capability and source identification of atmospheric particulates in local urban environments of Xuzhou, China - Yuhan Ou; Mingrui Li; Rui Zhang; Li Xing (Air Quality, Atmosphere & Health, 2026)

Abnormal dynamics of brain networks in bipolar disorder: a dynamic degree centrality and imaging–transcriptomic investigation - Chunguo Zhang; Leyi Zhang; Jiaquan Liang; Yiding Han; Haohao Yan; Wei Huang; Xiaoling Li; Chaohua Tang; Jinbing Xu; Yangpan Ou; Guojun Xie; Wenbin Guo (Psychopharmacology, 2026)

Effect of host switching on the parasitic performance of Habrobracon hebetor (Hymenoptera: Braconidae) against Ephestia elutella in stored tobacco - Jingtian Xue; Yao Huang; Houding Ou; Yi Mao; Ang Li; Liang Wang; Maofa Yang (Crop Protection, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Remote sensing enables rapid assessment of the March 28, 2025 Myanmar earthquake - Nan Xu; Zihao Zhang; Qingquan Li; Yifu Ou; Wei Tu; Chao Yang; Chuanhua Zhu; Peng Gong; Hui Lu; Deliang Chen (Science Bulletin, 2026)

Experimental study of straight tube length and pressure effects on spontaneous ignition and flame transition in high-pressure hydrogen releases - Cuiwei Liu; Weili Ou; Rui Ding; Songming Yu; Hui Han; Hongfang Lu; Minghao Li; Yuxing Li (Process Safety and Environmental Protection, 2026)

Ethephon and alternating magnetic field inhibit the browning of fresh-cut stem lettuce by regulating phenolic and reactive oxygen species metabolism - Tuankui Ou; Mengsheng Deng; Yingmei Tao; Huina Li; Wenao Sun; Xingyong Zhang; Dong Li (Postharvest Biology and Technology, 2026)

End-to-end automatic berthing of USVs in realistic port geometries via adaptive PPO-CBF - Weiqiang Liao; Yanghangcheng Ou; Huihui Li; Yao Chen; Yilong Wang; Wanneng Yu; Changkun Zhang; Jinglei Yang (Ocean Engineering, 2026)

Numerical research on the impact of built-in rectangular poles on the dynamic characteristics of rectangular liquid tanks - Xin He; Chao Li; Lingwei Chen; Gang Hu; Jinping Ou (Ocean Engineering, 2026)

Effects of seed particles and relative humidity on brown carbon formation from NO3-driven oxidation of vanillin - Shixin Mai; Kunpeng Chen; Hengjia Ou; Li Chen; Dexian Chen; Shengzhen Zhou (Atmospheric Environment, 2026)

Generation and Exosomal Noncoding RNA Profiling of Down Syndrome-Specific Induced Pluripotent Stem Cells - Chunxia Li; Weiwei Gong; Gengshuo Chen; Yu Sha; Chune Mo; Jiajun Xu; Xianliang Hou; Minglin Ou (Stem Cell Reviews and Reports, 2026)

Effects of Offset Displacement and Joint Roughness Coefficient (JRC) on the Real Contact Area of Mismatched Rock Joints - Yuzong Li; Haoxiang Cui; Ou Zhang; Zexin Zhang; Fanzhen Meng (Rock Mechanics and Rock Engineering, 2026)

miR-34c-3p promotes osteogenic differentiation of BMSCs by inhibiting DCBLD2 activation of the PI3K/AKT signaling pathway - Yongcheng Deng; Yihao Lei; Yi Ou; Junnan Li; Xingxi Hu; Lei Wen; Kaiyu Hou (Journal of Molecular Histology, 2026)

Evaluation of clinical efficacy and safety of T-705 (Favipiravir) in the treatment of fever with thrombocytopenia syndrome: a propensity score matching study - Fei Zhao; Quanman Hu; Anmin Ge; Yan Hu; Yanyan Yang; Jundong Chen; Saiwei Lu; Yangfan Ou; Wenyao Su; Li Zhang; Shuaiyin Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

UBL4A as a suppressor of intracerebral hemorrhage by binding to MAPK14 and promoting MAPK14 ubiquitination - Yuyang Ou; Chen Chen; Ziyi Wang; Xi Zhu; Yaoxing Luo; Shulin Li; Dan Li (Genes & Genomics, 2026)

Integrating eDNA metabarcoding and functional trait analysis to uncover fish community structure and assembly mechanism in the Taiwan strait - Weiyi He; Hao Huang; Lei Wang; Danyun Ou; Jiaqiao Wang; Runze Han; Yanxu Zhang; Jinli Qiu; Weiwen Li; Kar-Hoe Loh; Sze-Wan Poong (Frontiers in Marine Science, 2026)
Marine fish communities in coastal systems are increasingly shaped by environmental gradients associated with anthropogenic pressures and climate variability, yet how these factors influence community assembly and functional traits remain poorly understood. In this study, environmental DNA (eDNA) metabarcoding using the 12S MiFish primer with 33 water samples was integrated with taxonomic and functional diversity analyses, co-occurrence network analysis, the neutral community model, hierarchical modeling of species communities, and single-trait-based community-weighted means to investigate fish communities in the Taiwan Strait (TWS). This interdisciplinary approach provides both a unique perspective and a comprehensive framework for fish biodiversity assessment. Fish communities exhibited high modularity and weak interspecific interactions, with an uneven distribution of species within functional space, indicating elevated ecological vulnerability. Community assembly was jointly governed by stochastic and deterministic processes, with NO₂⁻ identified as a significant environmental driver shaping fish community assembly. Notably, fish communities in the inshore and principal axis regions exhibited higher clustering coefficient but lower network modularity compared to other regions. Hierarchical modeling of species communities and community-weighted means further indicated clear distributional and trait differences among fish from the estuarine to offshore areas, consistent with species-specific responses to environmental gradients from inshore to offshore areas. Overall, TWS fish communities are dominated by species with very small and small body-length traits, while reef-associated fishes are mainly concentrated in inshore and midshore regions. Fish community assembly and functional traits in TWS exhibited systematic variation along the offshore distance gradient and were jointly modulated by key environmental factors.

Acupuncture was associated with improved functional connectivity of the left hippocampal perceptual subregion in amnestic mild cognitive impairment - Jinhuan Zhang; Juan Ou; Jianxiang Chen; Xiaoming Ma; Xingying Lu; Jiaping Wu; Xinbei Li; Hanqing Lyu; Yongfeng Liu; Jinping Xu (Brain Imaging and Behavior, 2026)

Simultaneous detection of Mycobacterium tuberculosis complex and rifampin/isoniazid resistance with sanity 2.0 MTBC-MDR: a moderate-complexity automated NAAT - Xichao Ou; Bing Zhao; Hui Xia; Xundi Bao; Dongfang Xu; Qi Ma; Ye Xu; Jingjing Li; Wenzhi Shi; Feina Li; Yajie Guo; Ruida Xing; et al. (World Journal of Microbiology and Biotechnology, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Hmgn3 is critical for inducing totipotency in mouse embryonic stem cells - Qing Wang; Yiding Zhao; Xiaoyan Li; Mengyang Geng; Yan Liu; Yi Bai; Jing Yan; Xiao-Ou Zhang; Dayong Liu; Yamin Zhang; Wenhao Zhang; Qian Gao; et al. (Science Bulletin, 2026)

A large-scale framework for deriving tidal flat topography from SWOT data - Hao Xu; Nan Xu; Wenyu Li; Kai Tan; Chunpeng Chen; Huan Li; Lucheng Zhan; Pei Xin; Jiaqi Yao; Peng Li; Zhen Zhang; Haipeng Zhao; et al. (Remote Sensing of Environment, 2026)

Patterns and differences in sucrose metabolism during room-temperature storage in sucrose- and hexose-prevalent types of litchi - Xiaomeng Guo; Chulin Zhou; Tao Luo; Difa Zhu; Jingyi Li; Yongqi Chen; Wenbo Ou; Zhenxian Wu (Postharvest Biology and Technology, 2026)

Tungsten-Induced High-Valent doping activates lattice oxygen in spinel oxides for efficient water oxidation - Yu Zhong; Mingze Ou; Bin Chen; Xiantuo Chen; Zhou Shi; Huanan Wang; Daolei Wang; Cheng Peng; Chaoen Li; Jiang Wu (Fuel, 2026)

Impact of ultra-high pressure assisted alkaline extraction on properties and structural characteristics of carrageenan - Mingjing Zheng; Liyuan Wang; Tao Hong; Zhipeng Li; Yanbing Zhu; Zedong Jiang; Hui Ni; Yuanfan Yang; Yujia Ou (Food Hydrocolloids, 2026)

Effect of molecular weight of carboxymethyl chitosan on the properties of modified pea protein isolate-carboxymethyl chitosan complexes and its potential as stabilizer for high internal phase emulsions - Mianzhang Zhang; Hongliang Li; Shulin Deng; Shiyi Ou; Fu Liu; Jie Zheng (Food Hydrocolloids, 2026)

Geometric properties and cross-section behaviour of wire arc additively manufactured AA5356 I-section and cruciform-section stub columns - Jin Li; Ke Jiang; Ziyi Wang; Man-Tai Chen; Ou Zhao (Engineering Structures, 2026)

Low-alkalinity seawater sea sand columns reinforced with hydrophobic SFCBs and FRP hoops: A durability and energy dissipation capacity enhancement scheme for marine engineering - Kexuan Li; Ao Zhou; Tiejun Liu; Dujian Zou; Zichao Que; Jinping Ou (Engineering Structures, 2026)

Experimental study and predictive model of residual stresses in plates composed of conventional and wire arc additively manufactured steels - Xuanlu Shi; Ziyi Wang; Jin Li; Man-Tai Chen; Ou Zhao (Engineering Structures, 2026)

Electric-field-induced ultrafast and selective ZIF-8 filling in graphene membrane pores for precision dye desalination - Jialu Li; Zhonghao Xu; Yangdong He; Sheng Shi; Sihan Ye; Liyun Zhang; Lan Ma; Jian Zhen Ou; Hao Yu (Desalination, 2026)

Engineered bacterial extracellular vesicles drive anti-tumor immunity via dendritic cell maturation and trafficking - Zihao Ou; Qianbei Li; Bonan Pan; Junjie Feng; Xiaojing He; Yuanyuan Wu; Yudi Wang; Zhen Cai; Jinduan Lin; Lei Zheng (Chemical Engineering Journal, 2026)

High resolution indoor-outdoor urban PM2.5 daily dynamics with low cost solution using novel two-stage model of machine and transfer learning - Changhong Ou; Zhen Wang; Zhuokai Lu; Chang Gao; Hao Li; Yaoming Cai; Jinyuan Guo; Fei Li; Jingdong Zhang (Building and Environment, 2026)

Characteristics and contribution of VOCs emission from motorcycles to ozone formation in Xi’an, China - Wanli Yuan; Yongjie Lv; Jiahui Qu; Baoji Li; Yongfang Rao; Ou Ji; Long Cui; Yu Huang (Aerosol Science and Engineering, 2026)

GWAS and transcriptome analysis reveal male heterogametic sex-specific markers and candidate genes in darkbarbel catfish (Pelteobagrus vachelli) - Jin Zhang; Tongxin Cui; Mi Ou; Qing Luo; Shuzhan Fei; Xincheng Zhang; Kaibin Li; Fang Wang; Baixiang Chen; Xinping Zhu; Kunci Chen; Jian Zhao; et al. (Aquaculture, 2026)

Resveratrol mitigates TOCP-induced spinal cord neurotoxicity by suppressing ferroptosis, a process mediated through the p62/Keap1/Nrf2 pathway - Sangping Li; Shule Tan; Xiangsheng Tian; Yiquan Ou; Shujuan Hu; Weichao Zhao; Dingxin Long (Toxicology and Applied Pharmacology, 2026)

Dynamic multi-objective optimization algorithm via historical collaborative strategy and interval prediction strategy - Junwei Ou; Yana Li; Yaru Hu; Jiankang Peng; Jinhua Zheng; Juan Zou; Shengxiang Yang (Swarm and Evolutionary Computation, 2026)

Structural design and optimization of a novel semi-submersible floating offshore wind turbine platform using reinforced concrete - Weiwen He; Chao Li; Shunyun Zheng; Shengtao Zhou; Shangpei Liu; Jinping Ou (Ocean Engineering, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Thermodynamic and economic analyses of a biomass gasification-based ammonia and electricity polygeneration system integrating semi-closed supercritical CO2 cycle and chemical looping air separation - Siyi Ou; Xin Chen; Lin Zhu; Yu Liu; Qiang Hao; Rou Zheng; Yucen Chen; Jie Li (Fuel, 2026)

Mechanism and dynamic evolution of LED irradiation on volatile metabolites: A novel strategy for optimizing aroma quality in innovative black tea - Jihang He; Xinru Yu; Yunzhi Hao; Qiuming Li; Qingyang Wu; Xiaoxi Ou; Ying Xu; Hongzheng Lin; Ziwei Zhou; Yun Sun (Food Chemistry, 2026)

Synergistic enhancement of gelation and protein interactions in low-salt shrimp gels by static magnetic field and microcrystalline cellulose - Chunyu Li; Siyang Liu; Yingying Yang; Chunhong Yuan; Tong Zhang; Changrong Ou; Wenge Yang; Huamao Wei (Food Hydrocolloids, 2026)

Microbial mediators of environmental change in the Yellow River basin: Flavobacterium and pollution dynamics during the dry season - Xinyi Li; Zehua Zhang; Daichuan Chen; Zhengtong Chen; Longmiao Li; Zihao Song; Jiakun Li; Wencheng Li; Enkai Wang; Ruijia Wang; Ruisheng Huang; Peijun Zhao; et al. (Environmental Research, 2026)

Bisphenol exposure during pregnancy and serum total bile acid levels across trimesters: single and combined effects in pregnant women from Guangxi Zhuang, China - Jun Liang; Yu Zou; Zican Mo; Lixiang Pang; Kaiqi Yang; Peng Tang; Qian Liao; Liujuan Ou; Junshang Wen; Wanhui Li; Huishen Huang; Xiaoqiang Qiu (Environmental Pollution, 2026)

pH-responsive tannic acid-iron nanozymes capable of self-adaptive regulation of oxidative stress for enhancing the treatment of MRSA-infected wound via disrupting PBP2a to restore methicillin sensitivity - Yuze Luo; Ying Wang; Cheng Jin; Ke Yang; Zefeng Wang; Yinbang Zheng; Junqin Li; Chunlei Ou; Li Wang; Dinggeng He (Chemical Engineering Journal, 2026)

Association between atorvastatin and sarcopenia: a study based on NHANES and FAERS databases - Hao Zhang; Ping Zhang; Xi Luo; Li Pan Zhao; Hua Huang; Qi Hong Ou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Design, synthesis and antifungal evaluation of perillaldehyde derivatives as potential laccase inhibitors - Zhennan Cui; Yiming Zheng; Ning Ou; Ziyan Zhang; Boyu Lv; Jia Li; Wen Gu (Molecular Diversity, 2026)

Coupled polyphosphate storage and DOP mobilization along estuarine gradients in the Pearl River Estuary - Xian-Yang Zhang; Feng-Xian Han; Jian-Ting Li; Jia-Xue Wu; Song-Hui Lu; Lin-Jian Ou (Marine Pollution Bulletin, 2026)

Integration of transcriptomic and metabolomic data reveals the low temperature response gene regulatory network of germination in soybean (Glycine max L.) - Wenhui Fu; Jingying Nie; Junli Ou; Yuchen Liu; Benshi Zhou; Yan Jing; Yonggang Zhou; Junlong Gao; Keheng Xu; Chen Feng; Hongtao Gao; Yaxin Li; et al. (Plant Science, 2026)

Ship autonomous collision avoidance: Improving sparrow search algorithm for complex multi-ship encounters - Haijiang Li; Hongdong Ou; Shengke Ni; Jingen Zhou; Xinjian Wang (Ocean Engineering, 2026)

FINDER: Flow-aware intelligent navigation through distilled experience and reinforcement learning for UUVs in complex flow fields - Shuguang Chu; Haihan Feng; Yuheng Ou; Mingwei Lin; Dejun Li (Ocean Engineering, 2026)

Growth phase-linked Sargassum-associated DOM structures microbial succession and carbon-nutrient coupling in a benthic Sargassum bed - Xiao-Li Ou; Long-Long Huang; Qiu-Jie Wang; Li-Li Xu; Lin-Jian Ou; Yu-Feng Yang (Marine Environmental Research, 2026)

Environmental DNA metabarcoding reveals a decline of fish diversity from 2019 to 2023 in Dongshan Bay, China - Weiyi He; Sze-Wan Poong; Hao Huang; Lei Wang; Danyun Ou; Yanxu Zhang; Jinli Qiu; Weiwen Li; Kar Hoe Loh (Marine Environmental Research, 2026)

Insights into the dissipation and absorption behavior of Benzotriazole ultraviolet stabilizers in soil–plant systems: Experiments, molecular simulations, and machine learning - Zhenpeng Xu; Yiwen Ou; Hongxia Zhao; Jiyan Liu; Zhansheng Li; Xintong Li; Xiaonuo Zhang; Jinyang Wang (Journal of Hazardous Materials, 2026)

Integrating source–water connectivity into SWAT for hotspot-oriented nitrogen management in hilly catchments - Yanan Wang; Guishan Yang; Weixin Ou; Hengpeng Li; Saiyu Yuan; Hong Chen; Hongwu Tang (Journal of Environmental Management, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Tensile behaviour of joints composed of dissimilar metallic plates fabricated by wire arc additive manufacturing - Xuanlu Shi; Shuai Li; Jin Li; Man-Tai Chen; Ou Zhao (Engineering Structures, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Comparative Effects of Repeated Intravenous Infusions of Progenitor Cells in a Rat Model of Chronic Ischemic Cardiomyopathy - Xian-Liang Tang; Marcin Wysoczynski; Yan Li; Shengnan Zheng; Anna M. Gumpert; Wen-Jian Wu; Qinghui Ou; Luo Li; Halina Ruble; Heather Stowers; Roberto Bolli (Stem Cell Reviews and Reports, 2026)

The Jekyll and Hyde of Extracellular Vesicles: Dual Roles as Disease Drivers and Therapeutic Saviors in Diabetic Brain - Huiyang Li; Renlin He; Tiantian Luo; Cehua Ou; Yan Hu (Molecular Neurobiology, 2026)

Umbilical Cord Mesenchymal Stromal Cell-Derived Extracellular Vesicles Transfer CD59 to Astrocytes to Alleviate Complement-Dependent Cytotoxicity - Qi Shen; Xueying Wang; Qingjian Ou; Qian Wang; Zhenzhen Zhao; Zhiyang Chen; Xiaoman Zhu; Dongli Li; Caixia Jin; Furong Gao; Juan Wang; Lixia Lu; et al. (Molecular Neurobiology, 2026)

Correction: Lei et al. Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus. Fishes 2024, 9, 452 - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2025)
In the original publication [...]

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Infrared imaging detection for gas leakage based on residual-enhanced nnUNetv2: Taking methane leakage from a natural gas pipeline as a case study - Xiaoyu Ji; Lei Xu; Jiale Xiao; Qi Gao; Ling Tang; Bihua Ou; Changyun Li (Process Safety and Environmental Protection, 2025)

Synergistic antifungal activity and mechanism of carvacrol/citral combination against fusarium oxysporum in Dendrobium officinale - Xuemei Lu; Ke Hu; Minggui Ou; Min Li; Xinchun Zhang; Xingyu Zhan; Xun Liao; Ming Li; Rongyu Li (Pesticide Biochemistry and Physiology, 2025)

A LiDAR-based approach for real-time bulk coal extraction in cargo holds - Xinyi Yu; Dachuan Shi; Yuanlong Li; Kuiguang Jiao; Changrui Chen; Linlin Ou (Ocean Engineering, 2025)

Lateral bearing characteristics and p-y model of single pile in coral sand considering effect of vertical load - Xuanming Ding; Jianyu Liu; Xiao Li; Chunyan Wang; Hanlong Liu; Qiang Ou (Ocean Engineering, 2025)

Regime shift in river-tide dynamics of longitudinal and transverse channels over the Pearl River Delta, China - Bo Li; Hao Yang; Huayang Cai; Suying Ou; Feng Liu; Tongtiegang Zhao; Kairong Lin; Jianliang Lin (Journal of Hydrology, 2025)

Anthraquinone sites engineering of covalent organic frameworks enables efficient and selective 1O2 generation via directed oxidation of peroxymonosulfate - Yuzheng Wu; Jinyi Tan; Zifan Li; Luwen Liang; Bing Chen; Xinwen Ou; Shan Yao; Guiquan Che; Youqun Wang; Bin Han (Journal of Hazardous Materials, 2025)

Biogenic α-Mn2O3 excels in areas where commercial α-Mn2O3 performs poorly: Native and advanced oxidation degradation of atrazine - Huatao Sun; Huiyan Chen; Wuying Chen; Mingzhen Hu; Sha Chen; Yingjie Ma; Runjun Ou; Ding Li (Journal of Environmental Chemical Engineering, 2025)

Study on the adsorption mechanism and durability of non-sintered composite ceramsite as permeable reactive barrier filler for Pb2+ - Shufei Wang; Jie Jiang; Xiaoduo Ou; Jian Su; Changjun Liao; Hongxiang Zhu; Jian Gong; Jue Li (Journal of Environmental Chemical Engineering, 2025)

The 1907 Karatag earthquake doublet in Central Asia: Constraints from historic seismograms and surface rupture analysis - Xiao Yang; Xuhua Shi; Qi Ou; Hanlin Chen; Jin Ge; Feng Li; Mustafo Gadoev; Pulod Aminzoda; Jie Chen; Tao Li; Yangfan Huang (Global and Planetary Change, 2025)

Ultrasound-assisted supercritical carbon dioxide extraction of lutein from Tropaeolum majus flowers - Xing-Yu Liu; Yin-Long Li; Jing Zuo; Bo Zhu; Hong Ou (Food Chemistry, 2025)

Unveiling the phytoremediation potential and mechanisms of Phyla canescens in heavy metal-contaminated soils - Xixi Cai; Ruixiang Ou; Jianquan Wu; Dunhai Li; Jianying Li; Chengrong Peng; Jibing Li; Hongjie Qin (Environmental Research, 2025)

Innovative self-evolution manipulation for constructing ultra-uniform rich copper vacancies Cu31S16/GeS2 heterojunction towards exceptional sodium storage - Liang Cao; Jun Zhao; Yushen Liu; Yiwei Xue; Yafu Wang; Hongbo Geng; Xing Ou; Qingyu Li (Chemical Engineering Journal, 2025)

Effects of silymarin on liver function, antioxidant and immune factors of broilers under immune stress - Qingqing Tao; Haiyun Ou; Guanhong Li; Xiaoying Wang; Baosheng Liu; Qiufen Li (Veterinary Research Communications, 2025)

Effects and Mechanisms of NMDAR-EphB2 on Synapses in Mice by Active Immunization with a GluN1 Peptide - Kai Qian; Youshi Meng; Lin Zhang; Lanfeng Sun; Sijie Ou; Rida Li; Chi Gong; Shengyu Yang; Yuan Wu (Molecular Neurobiology, 2025)

Molar absorption coefficients of water components under vacuum ultraviolet light, implications for pollutant degradation: a review - Yuheng Chen; Boqiang Li; Huashe Ou; Madjid Mohseni; Wen-long Wang; Baiyang Chen (Environmental Chemistry Letters, 2025)

Design of a ball screw for the electric control rod drive mechanism in nuclear reactors - Chaoqun Qian; Yi Ou; Yongjun Bai; Changguang Zhou; Ling Li; Junwan Shen; Hutian Feng; Jian Wu (Annals of Nuclear Energy, 2025)

Nonlinear dynamics of chlorophyll a in relation to environmental factors in Baihua Reservoir - Wu Wei; Mengshu Han; Jing Xiao; Weihua Ou; Qiuhua Li (Aquatic Ecology, 2025)

Parthenolide promotes glucagon-like peptide-1 secreting in human Caco-2 cells via regulation of bitter taste receptor-induced of calcium signaling - Shanshan Li; Ye Chen; Zhaosu Song; Penghui Ou; Yujing Duan; Qinglei Liu; Wei Wang (Molecular and Cellular Biochemistry, 2025)

Bifunctional magnetic Fe/Fe3O4@Fe-N-C core-shell catalysts for external magnetic field-assisted enhancement of microbial fuel cell performance - Hai-Xia Liao; Dong-Ni Ou; Fan-Li Xiao; En-Xi Ruan; Nan Li (Science of The Total Environment, 2025)

Study on hydrogen storage properties of Ca atom modified γ-graphyne - Jun-wei Liu; Jia-cheng Li; Cai-he Fan; Ling Ou; Ying-zhe Zhang (Process Safety and Environmental Protection, 2025)

Research on dynamic characteristics of a tension-leg modular floating structure system under tendon failure - Yanwei Li; Conghao Qian; Nianxin Ren; Jun Yan; Zhe Zhang; Jinping Ou (Ocean Engineering, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

Enrichment effects of vegetation patches on soil water content depend on precipitation and vegetation conditions: A global meta-analysis - Hui-Hua Xu; Zhi-Yun Jiang; Jing-Yi Ding; Xue Guo; Yi-Jia Wang; Xiao-Yan Li; Jia-Lan Feng; Yu-Yao Ou (Journal of Hydrology, 2025)

Co-modification of amylase by acrolein with formaldehyde or methylglyoxal: Impact on enzyme function, structure, and cellular stress in two cell lines - Chunmin Yang; Yixin Li; Jing Huang; Hua Liu; Shiyi Ou; Lei Qian; Juanying Ou (Food Chemistry, 2025)

Prediction of expected maximum moment strength for reinforced concrete columns with normal and high-strength materials under varying axial load ratios - Mu-Hsuan Li; Nguyen Van Bao Nguyen; Yu-Chen Ou; Tung-Chun Tsai (Engineering Structures, 2025)

Post-fire tensile behavior of wire arc additively manufactured duplex stainless steel plates - Zhichao Gong; Hai-Ting Li; Wei Chen; Ou Zhao; Man-Tai Chen (Engineering Structures, 2025)

Post-fire local buckling of recycled 6061-T6 aluminium alloy SHS stub columns - Ziyi Wang; Jin Li; Yuanwen Ouyang; Ou Zhao (Engineering Structures, 2025)

Heat distribution coefficient and cooling load prediction of indoor spaces with attachment ventilation - Ou Han; Angui Li; Yuxin Yang; Thomas Olofsson (Energy and Buildings, 2025)

Eucommia ulmoides gum: A renewable bio-based polymer with potential for advanced materials in biomedicine and engineering - Zemin Ou; Chenxiaoning Meng; Yichun Yang; Qingxia Li; Hong Yi; Zhimin Wang; Xiaoqian Liu (Chemical Engineering Journal, 2025)

Impact of seasonal drought on soil multifunctionality in dry–hot valley forests - Ping Zhong; Shuoxing Wei; Zhihui Wang; Hanbiao Ou; Yong Wang; Hanjie He; Weizhi Lu; Xiaoyong Chen; Shuguang Liu; Songhai Li; Guangjun Wang (Plant and Soil, 2025)

Dietary sodium butyrate and poly-β-hydroxybutyrate improve growth performance, intestinal antioxidant and non-specific immune functions and resilience from ammonia stress in grass carp (Ctenopharyngodon idella) - Yingying Wang; Kang Ou-Yang; Ya He; Hui Yang; Liangmou Wang; Dapeng Li; Li Li (Aquaculture International, 2025)

Unraveling contributors to stepwise water level variations in the Zhujiang River Estuary - Bo Li; Hao Yang; Jing Liu; Feng Liu; Suying Ou; Jianliang Lin; Huayang Cai (Acta Oceanologica Sinica, 2025)

Multidimensional Maritime Route Modeling Method for Complex Port Waters Considering Ship Handling Behavior Diversity - Junmei Ou; Shuangxin Wang; Jingyi Liu; Hongrui Li; Wenyu Zhao; Chenglong Jiang (Journal of Marine Science and Engineering, 2025)
The sea area adjacent to ports features a dense network of intricate access routes. Existing route modeling methods exhibit limitations in accurately capturing these complex routes and effectively representing the diverse handling behavior patterns of ships within them. To address this issue, this paper proposes a maritime route modeling method incorporating ship handling behavior (MARSHB) to accurately identify port channels with diverse traffic flows and enabling a multi-dimensional model of heterogeneous vessel behaviors along these channels. Numerical experiments using extensive automatic identification system (AIS) data from the Bohai Sea show that the proposed method reduces the computational time by 49.75% for route extraction compared to the traditional method. For route modeling, MARSHB covers 88.31% of 95% high-density traffic areas, with safety boundaries exhibiting a higher accuracy of conformity with historical trajectory data.

No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - P. Pitard; A. Replumaz; P.H. Leloup; M.-L. Chevalier; S. Wang; M. Bai; X. Ou; M. Bernet; M. Balvay; E.R. Sobel; A. Vezinet; C. Gautheron; et al. (Tectonophysics, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Comparative DFT study on the reaction mechanism of dry reforming of methane over Ni (111), Ni@Co (111) and Co (111) surface - Zhiliang Ou; Qingsong Zuo; Ziqiang He; Kai Wang; Wenpin Zhang; Xiuquan Li; Jing Liang; Ying Chen; Jingyu Ran (Fuel, 2025)

Temperature-responsive microspheres for antibacterial and anti-inflammatory applications: Synthesis and performance evaluation - Shanshan Li; Penghui Ou; Yihui Wang; Ye Chen; Zhaosu Song; Qinglei Liu; Wei Wang (Food Bioscience, 2025)

Ultrasound-assisted phosphorylation on the functional and structural properties of fish gelatin - Qingfang Ying; Bin Hu; Yijia Li; Liangying Xu; Wenge Yang; Shengnan Zhan; Changrong Ou; Tao Huang (Food Hydrocolloids, 2025)

Single-atom iron-decorated hierarchically porous carbon nanofibers with carbon vacancy-enhanced performance for zinc-air batteries and supercapacitors - Haihan Zhou; Qianqian Wang; Bingyu Zhang; Jing Li; Ting Ou; Hua-Jin Zhai; Jiangwei Zhang (Chemical Engineering Journal, 2025)

Tetrahedral DNA-modified quantum dot nanobeads for highly sensitive fluorescent detection of amyloid-β oligomers in blood serum - Ou Hu; Yingyu Gong; Zeyu Li; Xiaomei Xie; Dongsheng Xu; Wei Bi; Zhengjin Jiang (Chemical Engineering Journal, 2025)

Pinning effect enabling high-entropy layered oxides toward long-life fast-charging sodium-ion batteries - Lianghua Wang; Yang You; Zhen Li; Shengwen Ou; Jingyue Xu; Mingliang Yuan (Chemical Engineering Journal, 2025)

Porous coordinated polymers/chitosan composite monolith with directional pore structure for highly efficient mono−/multi−/global phosphopeptide enrichment - Rong Li; Yan Wang; Dandan Zhou; Ruizhi Tang; Yangyang Bian; Shujuan Ma; Xingtai Qiu; Zichao Tang; Junjie Ou; Yehua Shen (Carbohydrate Polymers, 2025)

Genetic and histological characterization of a dwarf mutant in melon (Cucumis melo L.) reveals potential for breeding semi-dwarf cultivars - Zhuoxi Han; Wanning Zheng; Yang Li; Qingqing Ou; Haipeng Zhao; Han Zhao; Ju Xu; Sen Chai; Xueyong Yang; Zhonghua Zhang; Jinjing Sun (Theoretical and Applied Genetics, 2025)

Thermal Influence on Damage Behavior and Constitutive Response of Granite under Variable Cyclic Loading - Xiankai Bao; Shunjia Huang; Yongjun Lv; Lizhi Wang; Yue Huang; Xinya Li; Jiaao Ou; Meng Yin (Geotechnical and Geological Engineering, 2025)

Isolation, evolution, and biological characterization of non-virulent and non-drug-resistant Escherichia coli from porcine intestine - Bingming Ou; Biyang Xiao; Qingqing Li; Jiayi Wang; Xue Lin; Weinan Zhong; Huimin Zhu; Yufu Liu; Shaoting Li; Hongmei Zhang; Wenhua Liu; Minyu Zhang (Folia Microbiologica, 2025)

How do water quality requirements and spatial flows shape the supply-demand balance of water provision ecosystem services? Evidence from the Taihu Lake Basin - Xue Ding; Yu Tao; Jinling Luo; Henghui Xi; Qin Tao; Jiman Li; Conghong Huang; Fengyi Du; Weixin Ou (Applied Geography, 2025)

One-pot construction of monodisperse core-shell silica microsphere with quinine-containing hybrid fibrous shell for racemates separation - Chenyang Wang; Tiantian Guo; Rong Li; Shujuan Ma; Yinmao Wei; Junjie Ou (Analytica Chimica Acta, 2025)

Isolation, identification and optimization of culture condition of freshwater microalgae in Northwestern Ontario, Canada for sustainable lipid and biomass production - Janak Raj Khatiwada; Ou Li; Chonlong Chio; Rishnika Boteju; Dhanushya Thilagam Jeyakumar; Chao Liu; Sarita Shrestha; Wensheng Qin (Algal Research, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Heterosis analysis of heat and cold tolerance in hybrid offspring of sea urchin Mesocentrotus nudus: Implications for breeding - Wenzhuo Tian; Xuechun Jiang; Hao Guo; Peng Liu; Tongshan Jia; Shuaichen Wu; Fanjiang Ou; Xiaofei Leng; Xuguang Li; Lijie Wang; Yaqing Chang; Weijie Zhang; et al. (Aquaculture International, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Evidence for cognitive compensation mechanism in the postoperative delirium: a prospective multi-modal neuroimaging cohort study - Guo-Bin Zhang; Hao-Yi Li; Jia-Mei Lv; Xiao-Kang Zhang; Yong-Gang Wang; Yun-Yun Duan; Hong-Yan Chen; Zhi-Zheng Zhuo; Ya-Ou Liu; Hua-Wei Huang (Brain Imaging and Behavior, 2025)

A Stacked-PLSR ensemble learning method for estimating heavy metals contents in farmland using spectral response features - Xuying Chen; Long Li; Xuqing Li; Huiping Ou; Tianjiao Liu; Huitao Gu; Tingxuan Wang (International Journal of Remote Sensing, 2025)

Nematicidal activities and preliminary mechanisms of action of natural quinones against plant parasitic nematodes - Xue Guo; Yu-Qin Ou; Qi Zhang; Yan Li; Huan-Huan Hao; Xi-Yue Yu; Wen-Kun Huang; Xiu-Hai Gan (Pesticide Biochemistry and Physiology, 2025)

Multi-functionalities of citric acid assisted thermal hydrolysis for sludge pretreatment: A novel method assisting in sludge treatment targeting multiple-objectives - Yixin Zhang; Maojiong Cao; Yanming Li; Changjin Ou; Yufeng Xu; Yuansong Wei; Zhidan Liu; Jibao Liu (Journal of Hazardous Materials, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Multi-step ahead probabilistic runoff forecasting with SHAP interpretability: a GPR-enhanced deep learning ensemble approach integrating teleconnection factors - Feilin Zhu; Tiantian Hou; Ou Zhu; Yitong Sun; Weifeng Liu; Lingqi Zhao; Xuning Guo; Min Li; Ping-an Zhong (Environmental Modelling & Software, 2025)

Real-time uncertainty quantification for KLT-based displacement estimation - Kang Zhou; Ming-Gang Duan; Ji-Yang Fu; Yun-Cheng He; Zi-Tong Li; Hai-Ou Shi; Jing Song (Engineering Structures, 2025)

Experimental study on the long-term creep behavior of cross-laminated timber under axial compression used for mass timber structural systems - Xiaofeng Sun; Minjuan He; Zheng Li; Jiajia Ou; Xiuzhi Zheng; Mingyu Wei (Engineering Structures, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

MOFs-derived mortise and tenon-shaped hierarchical heterostructure with efficient stress relief for ultrastable sodium storage - Liang Cao; Mingjing Chu; Huilong Dong; Yafu Wang; Yiwei Xue; Yue Dai; Xianglai Cui; Hongbo Geng; Xing Ou; Qingyu Li (Chemical Engineering Journal, 2025)

A multi-effect synergistic photo-therapy PAS/ICG-Cu@ZOL hydrogel dressing with enhancing adaptive immunomodulatory and antibiofilm properties for improved healing of diabetic infected wounds - Bibo Ren; Jun Li; Kang Dai; Jiale Li; Chao Hu; Shiyu Wang; Kaijun Li; Zelin Ou; Haibo Wang (Chemical Engineering Journal, 2025)

Earthworm-driven modulation of atrazine biodegradation pathways in biofilters - Xinyi Li; Jibin Wang; Xinhong Wang; Yang Ou; Huiping Liu; Liming Yan; Minglian Shang (Chemical Engineering Journal, 2025)

Valence-invariable catalysis-mediated generation of reactive oxygen species and subsequent photothermal-triggered release of alkyl radicals via a Zr-based metal-organic framework nanohybrid for programmed multi-mode antibiofilm therapy - Chunlei Ou; Jinyi Chen; Yangxu Li; Xiaohan Zeng; Zefeng Wang; Caiyun Xu; Junqin Li; Yuze Luo; Li Wang; Dinggeng He; Luo Hai (Chemical Engineering Journal, 2025)

Flow Control-Based Aerodynamic Enhancement of Vertical Axis Wind Turbines for Offshore Renewable Energy Deployment - Huahao Ou; Qiang Zhang; Chun Li; Dinghong Lu; Weipao Miao; Huanhuan Li; Zifei Xu (Journal of Marine Science and Engineering, 2025)
As wind energy development continues to expand toward nearshore and deep-sea regions, enhancing the aerodynamic efficiency of vertical axis wind turbines (VAWTs) in complex marine environments has become a critical challenge. To address this, a composite flow control strategy combining leading-edge suction and trailing-edge gurney flap is proposed. A two-dimensional unsteady numerical simulation framework is established based on CFD and the four-equation Transition SST (TSST) transition model. The key control parameters, including the suction slot position and width as well as the gurney flap height and width, are systematically optimized through orthogonal experimental design. The aerodynamic performance under single (suction or gurney flap) and composite control schemes is comprehensively evaluated. Results show that leading-edge suction effectively delays flow separation, while the gurney flap improves aerodynamic characteristics in the downwind region. Their synergistic effect significantly suppresses blade load fluctuations and enhances the wake structure, thereby improving wind energy capture. Compared to all other configurations, including suction-only and gurney flap-only blades, the composite control blade achieves the most significant increase in power coefficient across the entire tip speed ratio range, with an average improvement of 67.24%, demonstrating superior aerodynamic stability and strong potential for offshore applications.

Petrogenesis of rodingite in the Ngamring massif, Xigaze ophiolite (Southern Tibet): Implications for the evolution of the Neo-Tethys Ocean - Gui-Fang Ou; Zhong’ao Liu; Wen-Yong Duan; Guang-Ming Sun; Xu-Ping Li; Song-Jie Wang (Journal of Asian Earth Sciences, 2025)

Efficient degradation of soil polycyclic aromatic hydrocarbons by the nZVI/H2O2/OA system: The key role of oxalic acid - Shixu Feng; Yiwen Ou; Xintong Li; Yunhao Wu; Yaxi Deng; Hongxia Zhao (Environmental Research, 2025)

Generation of hydrogen peroxide by using solid CaCO3 suspension via two-electron water oxidation - Huimin Liu; Guanghui Luo; Qiaozhi Han; Yilin Li; Yonghao Shen; Siyu Guo; Xinyu Wei; Chengyu Duan; Mengdi Sun; Yang Peng; Zheshun Ou; Yinglong Lu; et al. (Chemical Engineering Journal, 2025)

Optimal natural and HVAC ventilation to balance passenger infection risk and thermal comfort across seasons on a cruise ship - Qiqi Luo; Cuiyun Ou; Yulin Li; Zhiwen Luo; Wenxin Tian; Liyue Zeng; Jian Hang (Building and Environment, 2025)

Efficient Adsorption of Dye Pollutant by Anchoring Zr-MOF@GO Composite Matrix Microspheres: Performance and Mechanism Insights - Qianhui Ou; Yan Xiong; Li Chen; Deyong He; Chuxiang Zhou; Lan Wang (Water, Air, & Soil Pollution, 2025)

Lotus japonicus CIP73 functions as a transcriptional repressor to inhibit Nodule Inception gene expression in nodule symbiosis - Hao Li; Yajuan Ou; Jidan Zhang; Aifang Xiao; Zhongming Zhang; Yangrong Cao; Hui Zhu (Plant and Soil, 2025)

Genetic identification and characterization of two novel loci for grain arsenic concentration in tetraploid wheat at various field environments - Zhaoyong Zeng; Dandan Ou; Li Yin; Yueyi Wu; Yuanfeng Huo; Yinggang Xu; Huaping Tang; Shu Yuan; Xuesong Gao; Yusheng Qin; Jian Ma; Guangdeng Chen (Plant and Soil, 2025)

Exosomal circ_0001583 Drives Glioblastoma Cell Advancement Through the miR-647/CKAP2L Pathway - Yuhao Zhang; Shiming Liu; Cheng Wu; Xin Gao; Hongtao Zhao; Ou Li; Kaichuang Yang; Faliang Gao (Molecular Neurobiology, 2025)

Targeting Poly (ADP-ribose) polymerase-1 (PARP-1) for DNA repair mechanism through QSAR-based virtual screening and MD simulation - Kun Cao; Ruonan Wang; Siyu Wu; Dong Ou; Ruixue Li; Lianhai Li; Xinguang Liu (Molecular Diversity, 2025)

Lateral resistance performance of embedded wall panels fabricated by fiber-reinforced foam concrete filled with crumb rubber powders - Ou Geng; Zhen Guo; Yulong Zhang; Fumin Li; Limin Lu (Innovative Infrastructure Solutions, 2025)

Eremothecium species from Cardiospermum halicacabum and Koelreuteria henryi, and their associated soapberry bugs - Cheng-Hsuan Li; Jie-Hao Ou; Chi-Yu Chen (Mycological Progress, 2025)

Quantitatively understanding the ozone formation characteristics in areas with heavy precursor emission through machine learning simulations - Qiaoli Wang; Shengdong Yao; Chengcheng Zhu; Shenlin Huang; Xiaojie Ou; Jingkai Zhao; Shihan Zhang; Wei Li; Jianmeng Chen (Process Safety and Environmental Protection, 2025)

Evaluating equivalent static wave loads for a delta-shaped semi-submersible 10-MW wind turbine - Shunyun Zheng; Shangpei Liu; Chao Li; Xiaolu Wang; Jinping Ou (Ocean Engineering, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Boosting virus enrichment with macroporous magnetic sorbent based on ketoenamine covalent organic framework - Bo'ou Li; Fei Wang; Xiaonan Dong; Yuchang Li; Tao Jiang; Xiaojie Ma; Xiaoping Kang; Bo Wang (Journal of Hazardous Materials, 2025)

Subchronic ozone exposure leads to multi-organ injuries with differential reversibility in male C57BL/6 J mice - Miao Li; Shen Chen; Xinhang Jiang; Lizhu Ye; Yuzhi Guo; Wenxue Li; Jiahao Zhang; Wenjie Liu; Yahan Yang; Zehua Ou; Liping Chen; Guanghui Dong; et al. (Journal of Hazardous Materials, 2025)

Post-fire behaviour of wire arc additively manufactured ER70S-6 steel - Jin Li; Ke Jiang; Man-Tai Chen; Ou Zhao; Leroy Gardner (Engineering Structures, 2025)

Bovine serum albumin modified polymer adsorptive membranes for the selective removal of As(III) from wastewater - Yang Wang; Mingmei Ding; Jingyu Peng; Mingke Qiu; Yuxin Dai; Yang Li; Jingmin Ou; Li Gao (Desalination, 2025)

Self-contained hygroscopic elastic foams for synergistic atmospheric moisture control and shock protection - Shuai Li; Richang Ou; Jingjing Li; Zhaojun Li; Liangmin Yu; Zhihang Wang; Petri Murto; Xiaofeng Xu (Chemical Engineering Journal, 2025)

Nb2C MXene functionalized janus amphiphilic membrane manipulates antioxidant, antibacterial and proangiogenic properties to accelerate diabetic wound healing - Jiankang He; Yachong Li; Nianqiang Jin; Wenqiang Xie; Lingling Ou; Lu Sun; Chufeng Li; Jiayi Luan; Longquan Shao (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Integrating click chemistry into protein expression for efficient preparation of immobilized protein bio-surface with enhanced stability and reproducibility in affinity chromatography - Xue Zhao; Yunshan Wang; Jiatai Yin; Sidi Cun; Yuanyuan Ou; Qian Li; Xinfeng Zhao; Yajun Zhang (Analytica Chimica Acta, 2025)

Optimizing the application of machine learning models in predicting landslide susceptibility using the information value model in Junlian County of Sichuan Basin - Lijun Qian; Lihua Ou; Guoxin Li; Ying Chen; Bo Qian (Advances in Space Research, 2025)

GF-5 hyperspectral inversion of soil parameters using a VAE style-based spectral fusion model - Depin Ou; Jie Li; Zhifeng Wu; Kun Tan; Weibo Ma; Xue Wang; Yueqin Zhu (Computers and Electronics in Agriculture, 2025)

Optimizing biogas production from swine manure: Biogas recirculation coupled with pH adjustment to mitigate lime inhibition - Sicheng Li; Xiaoyu Ou; Dehan Wang; Wei Wang (Process Safety and Environmental Protection, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Multi-stage trajectory compression via speed information for preserving maritime traffic information integrity - Junmei Ou; Shuangxin Wang; Jingyi Liu; Yongze Zhu; Hongrui Li; Wenyu Zhao; Chuiyi Deng (Ocean Engineering, 2025)

Copula-based joint impact assessment of rainfall and tidal level on flood risk in tidal-influenced plain river network areas, Taihu Lake Basin - Hong Zhou; Jun Liu; Cheng Gao; Weidong Li; Shufang Ou; Yi Zhou; Qinghua Luan (Journal of Hydrology, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

The regulatory network on characteristic aroma formation during the processing of Meizhan oolong tea - Xiaoxi Ou; Qiuming Li; Xinru Yu; Yunzhi Hao; Jihang He; Jingjing Liang; Yucheng Zheng; Yun Sun (Food Research International, 2025)

Ripening-stage variations in small metabolites across six banana cultivars: A metabolomic perspective - Huijun Gao; Ping Liu; Weidi He; Fangcheng Bi; Chunhua Hu; Guiming Deng; Tongxin Dou; Qiaosong Yang; Chunyu Li; Ganjun Yi; Ou Sheng; Tao Dong (Food Chemistry, 2025)

Exploration of the development of a food safety risk index system for chemical contamination of aquatic products - Qiqi Liu; Yijun Ou; Mhungu Florence; Yan Li; Yanyan Wang; Yuhua Zhang; Lan Liu; Jiangbo Lei; Lili Huang; Sixuan Wu; Rongfei Peng; Zhijun Bai; et al. (Food Control, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Comparing Cr(III) oxidation intermediated by different manganese oxidizing bacteria: Efficiencies, kinetic and key structure characteristics of biogenic manganese oxides - Guangyuan Tu; Chunyu Ou; Qi Liao; Xiaoming Zhang; Shuangle Hou; Lin Yu; Kun Li; Sen Yang; Qi Li; Weichun Yang; Qingzhu Li; Mengying Si; et al. (Environmental Research, 2025)

Structural performance of aluminium alloy channel section tensile members connected with gusset plates - Ke Jiang; Binxu Li; Yannan Jing; Andi Su; Ou Zhao (Engineering Structures, 2025)

Experimental and analytical investigation of stainless steel reinforced seawater coral concrete beams subjected to four-point bending - Zhibin Li; Weisheng Xu; Zhixin Ma; Zongping Chen; Jiehui Wang; Enrique del Rey Castillo; Wangsheng Ou (Engineering Structures, 2025)

Static magnetic field-enhanced cathodic electrocatalysis of Fe3O4-based nitrogen-doped carbon for improving the performance of microbial fuel cells - Hai-Xia Liao; Dong-Ni Ou; Xiao-Feng Zhou; Ying-Qi Ouyang; Hui-Huan Jiang; Nan Li; Zhao-Qing Liu (Bioresource Technology, 2025)

GLA deficiency causes cardiac hypertrophy via enhanced autophagy - Wei Ou; Xi Li; Kuo Tang; Lin Ding; Tingting Sun; Qian Li; Tao Li (Science China Life Sciences, 2025)

Complete mitochondrial genome of Medicago sativa ssp. falcata (Papilionoideae, Fabaceae): characterization and phylogenetic analysis - Taiyou Ou; Zinian Wu; Qian Liu; Chunyu Tian; Yanting Yang; Lemeng Liu; Maowei Guo; Zhiyong Li (Planta, 2025)

Use of non-targeted metabolomics to explore metabolic differences between stem cells and callus of Tetraena mongolica - Yeru Yang; Haihua Li; Ruiping Wang; Jiahe Li; Ling Li; Jiayu Li; Lin Ou; Jun Li; Chengbo Zhang; Liyu Wang; Fengqiang Yu; Zhi He; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Geomorphological evolution of small watershed on the Chinese Loess Plateau based on slope shape spectra - Hongtao Jiang; Nan Chen; Chen Wang; Sijia Li; Mengyao Ou (Earth Science Informatics, 2025)

Effect of different fermentation substrates on rumen microorganisms and microbe-derived extracellular vesicles (EVs) - Rongxia Zhu; Lijun Ou; Tonghao Li; Caiyu Luo; Zecheng Zou; Qien Qi; Xin Feng (Brazilian Journal of Microbiology, 2025)

The Effect of Plant Quercetin on Immune Function of Microtus Fortis - Yuting An; Dongmei Yang; Bo Ma; Dongming Liu; Kaidong Deng; Shuanglun Tao; Huijuan Cai; Yangjing Ou; Junnian Li (Journal of Chemical Ecology, 2025)

A Review of the Calcium Sulphoaluminate Cement Mixed with Seawater: Hydration Process, Microstructure, and Durability - Han Li; Jing Meng; Yang Liu; Lilin Yang; Yukai Wang; Ning Xie; Jinping Ou; Guoxiang Zhou (Journal of Marine Science and Engineering, 2025)
The preparation of low-cost and high-durability cement-based material systems using seawater mixing has become an urgent task in marine engineering construction. The requirements have addressed key challenges, including high transportation costs for fresh water and raw materials, poor structural durability, and difficulty in meeting actual construction schedules. Sulfatealuminate cement (CSA) has become an ideal material for marine engineering due to its high corrosion resistance, rapid early strength, which is 35–40 MPa of 3-day compressive strength and is 1.5–2 times compared ordinary Portland cement (OPC), and low-carbon characteristics, reduced production energy consumption by 35–50%, and CO2 emissions of 0.35–0.45 tons/ton. The Cl− and SO42− in seawater can accelerate the hydration of CSA, promote the formation of ettringite (AFt), and generate Friedel’s salt fixed chloride ions, significantly enhancing its resistance to chloride corrosion. Its low alkalinity (pH ≈ 10.6) and dense structure further optimize its resistance to sulfate corrosion. In terms of environmental benefits, CSA-mixed seawater can save 15–20% fresh water. And the use of solid waste preparation can reduce environmental burden by 38.62%. In the future, it is necessary to combine multi-scale simulation to predict long-term performance, develop self-healing materials and intelligent control technologies, and promote their large-scale application in sustainable marine infrastructure.

Triploidy induction through cntd1 knockout in red crucian carp (Carassius auratus red var.) - Huilin Li; Yu Zhang; Lina Zhang; Juan Li; Yuan Ou; Ming Wen; Zehong Wei; Jing Wang; Yu Deng; Yinjun Jiang; Conghui Yang; Yuqin Shu; et al. (Aquaculture, 2025)

Exploring the integrating factors and size thresholds affecting cooling effects in urban parks: A diurnal balance perspective - Junyi Li; Daoyuan Chen; Jingyao Ou; Quanquan Rui; Bowen Jin; Zhipeng Zhu; Guochang Ding (Sustainable Cities and Society, 2025)

Mechanisms of soil persistent organic carbon loss in alpine ecosystems: Insights into microbial and calcium spatial footprint - Jie Shen; Bangfei Ou; Yanbao Lei; Yuting He; Juan Xue; Xianzhi Deng; Changquan Wang; Yiding Li; Geng Sun (Soil Biology and Biochemistry, 2025)

Unequal impacts of global urban–rural settlement construction on cropland and production over the past three decades - Yansui Liu; Cong Ou; Yaqun Liu; Zhi Cao; Guy M. Robinson; Xunhuan Li (Science Bulletin, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Expression and sex pheromone-binding characteristics of pheromone-binding protein 3 in Tuta absoluta (Lepidoptera: Gelechiidae) - Xiaolan Ou; Xianya Li; Bo Xu; Yusheng Wang; Guifen Zhang; Wanxue Liu; Fanghao Wan; Hongbo Jiang; Khalid Haddi; Cong Huang; Yibo Zhang (Pesticide Biochemistry and Physiology, 2025)

Machine learning-enhanced flavoromics: Identifying key aroma compounds and predicting sensory quality in sauce-flavor baijiu - Shuai Li; Yueran Han; Li Wang; Ya Zhang; Fan Wang; Youming Ou; Haoying Li; Liang Yang; Shuyi Qiu; Jun Lu (Food Chemistry, 2025)

Impact of agricultural straw open-field burning on concentrations of six criteria air pollutants in China - Hao-Neng Huang; Zhou Yang; Yuming Guo; Jia-Jun Ma; Bo-Wen Ming; Jun Yang; Cui Guo; Li Li; Chun-Quan Ou (Environmental Pollution, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Avian influenza A(H5N6) virus detected during live-poultry market surveillance linked to a human infection in Changsha, China, from 2020 to 2023 - Zheng Huang; Rusheng Zhang; Dong Yao; Huiyuan Fu; Lingzhi Li; Shan Xiao; Xinhua Ou; Mingzhong Xu; Qing-Bin Lu; Xuewen Yang (Archives of Virology, 2025)

Increased CO2 Concentration Mitigates the Impact of Nitrite on Zebrafish (Danio rerio) Liver and Gills - Xinyu Wang; Yao Tang; Hui Yang; Ya He; Kang Ou-Yang; Liangmou Wang; Qian Zhang; Dapeng Li; Li Li (Fishes, 2025)
Nitrite and carbon dioxide (CO2) are common environmental substances in intensive aquaculture ponds. However, the effects and mechanisms of their combined exposure on aquatic animals remain unclear. In this study, we investigated the toxic effects of 2.5, 5, and 10 mg/L CO2 in the presence of 2 mg/L nitrite on hematological, blood gas parameters, and liver physiological and pathological changes in zebrafish (Danio rerio) over 14 days and 28 days. Our results demonstrated a reduced nitrite uptake and accumulation in the gills and liver of zebrafish exposed to nitrite and varying levels of CO2. Increased CO2 levels also led to a decrease in the expression of gill ae1, whereas the transcriptional levels of nhe1 and nhe3b, nkcc and nbc1 were notably upregulated. Moreover, there was a decrease in Cl− and Na+ concentrations, along with an increase in K+ concentrations. These changes suggested that zebrafish responded to increased CO2 stress by reducing their absorption of chloride-dependent nitrite, excreting H+ and maintaining their internal pH. Exposure to higher CO2 levels in the presence of nitrite resulted in lower blood MetHb levels and liver oxidative stress compared to the nitrite single-exposure treatment. Furthermore, co-treatment with CO2 and nitrite attenuated the nitrite-induced damage to genes related to mitochondrial respiratory chain function (ndufs1, mtnd5, mtycb, atp5f1b, mtatp8), leading to elevated ATP levels. Exposure to nitrite alone increased the expression of lipolytic genes (hsla, cpt1aa, atgl) and decreased the expression of lipid synthesis genes (fasn, acaca), resulting in a decrease in TG and TC content in zebrafish liver. However, co-treatment with CO2 and nitrite prevented the nitrite-induced disruption of lipid metabolism, as evidenced by the improvement in TG and TC levels, as well as transcriptional levels of lipid metabolism-related genes. In conclusion, our study suggests that in the presence of 2 mg/L nitrite, increased CO2 (2.5–10 mg/L) may modulate ion transporter genes to reduce the chloride-dependent nitrite uptake and maintain pH homeostasis, concurrently alleviating oxidative stress, restoring mitochondrial respiratory function, and improving lipid metabolism in a dose-dependent manner. These changes may be related to the increase in the concentration of bicarbonate ions in the water as the CO2 level rises. These findings shed light on the potential protective effects of CO2 in mitigating the harmful effects of nitrite exposure in aquatic animals.

Dynamic multi-objective evolutionary algorithm based on dual-layer collaborative prediction under multiple perspective - Yaru Hu; Yana Li; Junwei Ou; Jiankang Peng; Jun Li; Jinhua Zheng (Swarm and Evolutionary Computation, 2025)

A new quasi-accurate detection with equivalent weight for quality control of underwater acoustic measurements - Wenjian Huang; Jikun Ou; Xingliang Huo; Yanju Chai; Wei Li; Yong Wang (Ocean Engineering, 2025)

A coupled hydrological multimedia model used to simulate PFASs transport and fate in the river network of megacity Shanghai - Ye Li; Tianhao He; Jing Yang; Fangfang Ding; Xiaofei Li; Ye Huang; Guoyu Yin; Erkai He; Yan Li; Yuyi Wang; Yushan Li; Yuyan Liu; et al. (Journal of Hydrology, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Prediction and mechanism analysis of octanol-air partition coefficient for persistent organic pollutants based on machine learning models - Zhenpeng Xu; Hongxia Zhao; Jinyang Wang; Xintong Li; Zhansheng Li; Xiaonuo Zhang; Yiwen Ou (Journal of Environmental Chemical Engineering, 2025)

Late Mesozoic Wangxiang Composite Granitic Pluton, South China Block: Implications to Magma Emplacement and Evolution from Geochemical Proxies - Quan Ou; Jing-Yi Liu; Feng Zi; Bruna B. Carvalho; Xiaoping Long; Jian-Qing Lai; Kun Wang; Zi-Qi Jiang; Yi-Zhi Liu; Zheng-Lin Li; Hong-Yun Wang (Journal of Earth Science, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Assessment of total dissolved gas supersaturation stress on passage performance of bighead carp (Hypophthalmichthys nobilis) in vertical slot fishway - Minne Li; Yadong Ou; Jialin Liao; Haoran Shi; Bo Zhu; Xintong Li; Quan Yuan; Xin Yang (Frontiers in Marine Science, 2025)
Total dissolved gas supersaturation (TDGS) due to flood or hydropower station discharge adversely affects the swimming performance of migratory fish, thereby reducing passage efficiency. This study assessed the swimming performance of bighead carp in an experimental vertical slot fishway under varied slot flow velocities of 0.2, 0.25, and 0.3 m/s after 2 h of exposure to different levels of TDGS water. The results demonstrated that increased TDGS levels and flow velocities significantly reduced the fish passage efficiency. Specifically, passage success rates reached 61%, 48%, 37%, and 37% at TDGS levels of 100%, 110%, 120%, and 130% respectively, at a flow velocity of 0.2 m/s. At flow velocities of 0.2, 0.25, and 0.3 m/s with 100% TDGS water, success rates were 61%, 53%, and 47%, respectively. Moreover, increased TDGS levels and increased flow velocities notably extended the passage time in the fishway. Both TDGS levels and fishway flow velocities significantly influenced the swimming trajectories of the fish. Preferences for flow velocities were notably affected by the TDGS levels, whereas preferences for turbulent kinetic energy were affected by both the TDGS levels and the velocities of the fishway flow. In this study, an evaluation method was developed to assess the adverse effects of TDGS on fish passage efficiency based on the following critical parameters: passage success rate, time, trajectory, and preferred hydraulic factor. This study offers valuable insights for optimizing operations and fishway management to enhance fish protection.

Seasonal variations and hydrological management regulate nutrient transport in cascade damming: Insights from carbon and nitrogen isotopes - Yujing Yang; Wanfa Wang; Shengde Yu; Yuanbi Yi; Sen Xu; Yuanzhi Yao; Jun Zhong; Wenhong Shi; Sainan Chen; Qixin Wu; Zuhong Ou; Hu Ding; et al. (Water Research, 2025)

How can street interface morphology effect pedestrian thermal comfort: A case study of the old town of Changsha, China - Jian Zheng; Zixun Ou; Yanfen Xiang; Jiasheng Li; Bohong Zheng (Urban Climate, 2025)

Fatigue analysis of monopile-supported offshore wind turbine under varied supported conditions - Jun Liang; Ying Wang; Chao Li; Jinping Ou (Ocean Engineering, 2025)

Microcystin-LR induces fatty liver metabolic disease in zebrafish through the PPARα-NOD1 pathway: In vivo, in vitro, and in silico investigations - Kang Ou-Yang; Ya He; Hui Yang; Liangmou Wang; Qian Zhang; Dapeng Li; Li Li (Journal of Hazardous Materials, 2025)

Enhancing ozone catalytic decomposition through acid treatment of α-MnO2 for improved activity and humidity resistance - Shangchao Xiong; Kai Zhang; Zhenghao Xu; Hongjun Ou; Yuanyuan Zheng; Xi Li; Yue Peng; Xubiao Luo; Junhua Li (Journal of Environmental Sciences, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Advances and perspectives in biological control of postharvest fungal decay in citrus fruit utilizing yeast antagonists - Xiaojiao Li; Ou Chen; Wenjun Wang; Lili Deng; Shixiang Yao; Jian Ming; Hongyin Zhang; Kaifang Zeng (International Journal of Food Microbiology, 2025)

Scenting: An effective processing technology for enriching key flavor compounds and optimizing flavor quality of decaffeinated tea - Huimin An; Xingchang Ou; Yuan Chen; Yiwen Huang; Jiaqi Ying; Youcang Jiang; Yong Yuan; Yueping Tan; Yongxing Xie; Zhonghua Liu; Jianan Huang; Shi Li (Food Chemistry, 2025)

The effect of resveratrol on lead-induced oxidative damage and apoptosis in HT-22 cells - Xiang Yi; Ruokun Wei; Shaoni Huang; Peiqi Wei; HuiShuai Li; Zhenning Li; Michael Aschner; Yueming Jiang; Shiyan Ou; Shaojun Li (Food and Chemical Toxicology, 2025)

Net section fracture of aluminium alloy angle-to-plate connections: Testing, modelling and design - Ke Jiang; Shuai Li; Tong Guo; Yating Liang; Ou Zhao (Engineering Structures, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Study on the early diagnostic value of nanopore sequencing in alveolar lavage fluid smear-negative pulmonary tuberculosis - Yangjing Ou; Dan Li; Xi Long; Huiyang He; Ling Qing; Yuqiu Tian; Jing Ren; Qing Zhou; Yingzheng Tan (Brazilian Journal of Microbiology, 2025)

How did the regional water-heat distribution in oasis area vary with the different spatial patterns and structures of shelterbelt system—A case study in Ulan Buh desert oasis - Feng Gao; Kexin Lv; Qun'ou Jiang; Huijie Xiao; Junran Li (Agricultural and Forest Meteorology, 2025)

Data-driven models for forecasting algal biomass in a large and deep reservoir - Yuan Li; Kun Shi; Mengyuan Zhu; Huiyun Li; Yulong Guo; Song Miao; Wei Ou; Zhubin Zheng (Water Research, 2025)

How to stop groundwater drawdown in North China Plain? Combining agricultural management strategies and climate change - Junji Ou; Beibei Ding; Puyu Feng; Yong Chen; Lili Yu; De Li Liu; Raghavan Srinivasan; Xueliang Zhang (Journal of Hydrology, 2025)

A novel and efficient strategy for screening high prodigiosin-yielding bacterial mutants by using multiple negative regulatory factors and fermentation optimization under waste cooking oil and precursors - Ou Li; Junyuan Zhu; Yufan Qiao; Yuanru Xiong; Chonlong Chio; Chao Liu; Yunpeng Chen; Rishnika Boteju; Wensheng Qin (Journal of Cleaner Production, 2025)

Investigation of spatiotemporal distribution and formation mechanisms of ozone pollution in eastern Chinese cities applying convolutional neural network - Qiaoli Wang; Dongping Sheng; Chengzhi Wu; Xiaojie Ou; Shengdong Yao; Jingkai Zhao; Feili Li; Wei Li; Jianmeng Chen (Journal of Environmental Sciences, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Mo-doped CoP nanoparticles embedded bamboo-like N-doped carbon nanotube modified hollow carbon nanocage for electrochemical sensing of dopamine in human serum and meat samples - Li Xu; Chengshuang Ling; Lian Ou; Yao Jin; Chao Tan; Yao Gao; Xiaoli Xiong (Food Chemistry, 2025)

Solid-state ion-conductive elastomers with high mechanical robustness and ion-conductivity for highly durable triboelectric nanogenerators - Fangyan Ou; Xinze Li; Liang Tuo; Zhichao Zhang; Wei Tang; Ting Xie; Chuang Ning; Wenyu Pan; Qizhi Chen; Qihua Liang; Zhiyong Qin; Wei Gao; et al. (Chemical Engineering Journal, 2025)

Comprehensive effects of biochar-assisted nitrogen and phosphorus bioremediation on hydrocarbon removal and microecological improvement in petroleum-contaminated soil - Xuhong Zhang; Manli Wu; Zeliang Liu; Yawen Ou; Ting Zhang; Mengqi Li (Bioresource Technology, 2025)

An in-depth understanding of the role and mechanisms of T cells in immune organ aging and age-related diseases - Yudai Xu; Zijian Wang; Shumin Li; Jun Su; Lijuan Gao; Junwen Ou; Zhanyi Lin; Oscar Junhong Luo; Chanchan Xiao; Guobing Chen (Science China Life Sciences, 2025)

Assessing spatial pattern of urban green space coverage and its determining factors: A case study in the Yangtze River Delta region in China - Xiaodan Liu; Yan Li; Henghui Xi; Xiaohong Li; Yiyang Wu; Shirui Yuan; Muwu Xu; Weixin Ou; Conghong Huang (Advances in Space Research, 2025)

Single-cell RNA sequencing analysis reveals the dynamic changes in the tumor microenvironment during NMIBC recurrence - Ziang Chen; Tianxiang Zhang; Weijian Li; Jia Hu; Yuxi Ou; Fangdie Ye; Jinhao Zhang; Haowen Jiang; Shenghua Liu (Apoptosis, 2025)

Numerical Study on Hydrodynamic Performance and Vortex Dynamics of Multiple Cylinders Under Forced Vibration at Low Reynolds Number - Fulong Shi; Chuanzhong Ou; Jianjian Xin; Wenjie Li; Qiu Jin; Yu Tian; Wen Zhang (Journal of Marine Science and Engineering, 2025)
Flow around clustered cylinders is widely encountered in engineering applications such as wind energy systems, pipeline transport, and marine engineering. To investigate the hydrodynamic performance and vortex dynamics of multiple cylinders under forced vibration at low Reynolds numbers, with a focus on understanding the interference characteristics in various configurations, this study is based on a self-developed radial basis function iso-surface ghost cell computing platform, which improves the implicit iso-surface interface representation method to track the moving boundaries of multiple cylinders, and employs a self-constructed CPU/GPU heterogeneous parallel acceleration technique for efficient numerical simulations. This study systematically investigates the interference characteristics of multiple cylinder configurations across various parameter domains, including spacing ratios, geometric arrangements, and oscillation modes. A quantitative analysis of key parameters, such as aerodynamic coefficients, dimensionless frequency characteristics, and vorticity field evolution, is performed. This study reveals that, for a dual-cylinder system, there exists a critical gap ratio between X/D = 2.5 and 3, which leads to an increase in the lift and drag coefficients of both cylinders, a reduction in the vortex shedding periodicity, and a disruption of the wake structure. For a three-cylinder system, the lift and drag coefficients of the two upstream cylinders decrease with increasing spacing. On the other hand, this increased spacing results in a rise in the drag of the downstream cylinder. In the case of a four-cylinder system, the drag coefficients of the cylinders located on either side of the flow direction are relatively high. A significant increase in the lift coefficient occurs when the spacing ratio is less than 2.0, while the drag coefficient of the downstream cylinder is minimized. The findings establish a comprehensive theoretical framework for the optimal configuration design and structural optimization of multicylinder systems, while also providing practical guidelines for engineering applications.

Effects of Chinese Herbal Medicines on Growth Performance, Antioxidant Capacity, and Liver and Intestinal Health of Hybrid Snakehead (Channa maculata ♀ × Channa argus ♂) - Jiamin Kang; Shuzhan Fei; Junhao Zhang; Haiyang Liu; Qing Luo; Mi Ou; Langjun Cui; Tao Li; Jian Zhao (Fishes, 2025)
Chinese herbal medicines have become a new green feed additive in the aquaculture industry. The aim of this study is to investigate the effects of traditional Chinese herbal medicines (Isatidis radix, Forsythia suspensa, and Schisandra chinensis) on the growth performance, antioxidant capacity, and intestinal microbiota of hybrid snakehead (Channa maculata ♀ × Channa argus ♂). A total of 600 fish (mean weight: 15.85 ± 0.15 g) were randomly assigned to five groups, including the control group (CG), I. radix extract group (IRE), F. suspensa extract group (FSE), S. chinensis extract group (SCE), and the Chinese herbal medicine mixture group (CHMM; a mixture of extracts of I. radix, F. suspensa, and S. chinensis at the ratio of 1:1:1) for 6 weeks. The results show that the IRE-supplemented diet improved the survival rate (SR), feed efficiency ratio (FE), and condition factor (CF) compared to others. Compared to the control group, the activity of superoxide dismutase (SOD) in plasma and intestine was significantly increased in the FSE and CHMM groups, whereas the content of malondialdehyde (MDA) in plasma and liver was significantly reduced in the SCE group. A 16s rRNA analysis indicates that dietary supplementation with FSE significantly promoted the proliferation of Fusobacteriota, while IRE supplementation increased the alpha diversity of intestinal bacteria. In conclusion, the addition of I. radix to the diet of hybrid snakehead improves growth, antioxidant capacity, and liver and intestine health, and modulates the intestinal microbiota of snakehead positively.

Optimization of Bulk Cargo Terminal Unloading and Outbound Operations Based on a Deep Reinforcement Learning Framework - Haijiang Li; Jiapeng Zhao; Peng Jia; Hongdong Ou; Weili Zhao (Journal of Marine Science and Engineering, 2025)
This study addresses the integrated scheduling problem of dry bulk cargo terminal yards, which includes three components: transportation planning, yard selection optimization, and equipment scheduling. Additionally, the research integrates safety considerations and addresses the complexities of dynamic transportation planning. This work presents two innovations. Firstly, this study develops a sophisticated modeling framework that integrates graph structures for precise yard mapping with mixed-integer programming to enforce operational constraints. This integrated approach facilitates a more accurate and comprehensive representation of yard operations, capturing diverse operational aspects while maintaining model clarity and computational efficiency. Secondly, this study proposes an advanced solution methodology that employs a reinforcement learning technique integrating a Dueling Deep Q-Network and Double Deep Q-Network. This hybrid algorithm significantly enhances optimization performance and accelerates the learning process, thereby improving the efficiency of the solutions. The experimental results demonstrate that the proposed model effectively manages the integrated scheduling of bulk material ingress, storage, and egress within the yard. The operational plans generated by the approach outperform traditional first-come, first-served strategies, showcasing substantial improvements in port operational efficiency and reliability. This comprehensive solution underscores the potential for significant advancements in the overall management and performance of dry bulk cargo ports.

Efficient 3D Surface-to-Borehole Electromagnetic Modeling Using an Incomplete Fast Fourier Transform Algorithm - Yi-ze Zhao; Jing-he Li; Guo Zhao; Zhan-xiang He; Qi Ou; Zu-chen Huang (Applied Geophysics, 2025)

MABI: A novel Mixed Algal Blooms Index based on color space transformation - Zirui Ou; Xing Li; Fangyuqing Jin; Shuai Peng; Wei Liu; ErZhu Li; Lianpeng Zhang (Marine Pollution Bulletin, 2025)

Non-electroactive bacteria behave variously in AnMBR biofilm control using electric field - Lijie Zhou; Fei Wu; Pingxiang Ou; Haixiang Li; Wei-Qin Zhuang (Water Research, 2025)

Ginsenoside Rg3 attenuates the stemness of breast cancer stem cells by activating the hippo signaling pathway - Zhicheng Deng; Mengdie Ou; Yonghui Shi; Guocheng Li; Li Lv (Toxicology and Applied Pharmacology, 2025)

Critical evaluation of extracellular polymeric substances extraction methods: Extraction efficiency, molecular characteristics, and heavy metals binding properties - Bei Ou; Xueyang Hu; Wenbo Yu; Fanhao Meng; Wen Li; Sha Liang; Shushan Yuan; Huabo Duan; Huijie Hou; Keke Xiao (Science of The Total Environment, 2025)

Identification and detection of label-free polystyrene microplastics in maize seedlings by Raman spectroscopy - Zhaoxing Zhi; Yang Li; Gang Liu; Quanhong Ou (Science of The Total Environment, 2025)

Coupling biogas circulation with slurry reflux for carbon-neutral treatment of lime-disinfected pig wastewater: Enhancing fermentation and CO2 sequestration - Sicheng Li; Wei Wang; Dehan Wang; Xiaoyu Ou (Journal of Water Process Engineering, 2025)

Bending performance of nail laminated timber (NLT): Experiments and probabilistic modelling based on Monte Carlo simulation - Wei Feng; Minjuan He; Jiajia Ou; Zheng Li (Engineering Structures, 2025)

Geometric analysis and local buckling behavior of wire arc additively manufactured ER110S cruciform section stub columns - Ren Li; Andi Su; Yuyin Wang; Ou Zhao (Engineering Structures, 2025)

Tailoring local electronic structure to achieve reversible anion redox chemistry of layered oxide cathodes for high-performance sodium-ion batteries - Lianghua Wang; Yang You; Zhen Li; Shengwen Ou; Jingyue Xu; Mingliang Yuan (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Fore-arc metasomatism by hybrid slab fluids during subduction initiation: Sr–Mg–Ca isotopes of rodingite, western Yarlung Zangbo suture zone - Gui-Fang Ou; Song-Jie Wang; Hao Deng; Wen-Yong Duan; Xu-Ping Li; Hans-Peter Schertl (Chemical Geology, 2025)

Prediction and visualization of 3D wake field of a rectangular high-rise building in tropical island cities based on UAV measurements - Bin Huang; Jinke Liu; Zhengnong Li; Xiangjun Wang; Xijie Liu; Jinshuang Dong; Qiurui Cai; Ou Pu; Terigen Bao (Building and Environment, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Plant-derived exosome-like nanoparticles for microRNA delivery in cancer treatment - Chun Yi; Linzhu Lu; Zhaosheng Li; Qianqian Guo; Longyun Ou; Ruoyu Wang; Xuefei Tian (Drug Delivery and Translational Research, 2025)

Response of acetochlor degradation and bacterial community in black soil to the application of vermicompost - Xia Hou; Xinhong Wang; Yang Ou; Liming Yan; Huiping Liu; Xinyi Li; Minglian Shang (Biology and Fertility of Soils, 2025)

An ultra-sensitive SERS approach by electrostatic enrichment of charged analytes on Ag/laponite nanocomposites - Hao Zhang; Chaopeng Fu; Jianhao Ding; Guoqiang Xu; Chunhui Zhou; Zhenyu He; Zhimin Ou; Dongshen Tong; Minyang Qiu; Xiangdong Zhou; Xiaonian Li (Applied Clay Science, 2025)

Numerical Study on the Hydrodynamics of Fish Swimming with Different Morphologies in Oblique Flow - Fulong Shi; Yu Tian; Jianjian Xin; Chuanzhong Ou; Zhiwei Li; Minjia Rao (Journal of Marine Science and Engineering, 2024)
In confined and intricate aquatic environments, fish frequently encounter the need to propel themselves under oblique flow conditions. This study employs a self-developed ghost-cell immersed boundary method coupled with GPU acceleration technology to numerically simulate the propulsion dynamics of flexible biomimetic fish swimming in oblique flow environments. This research scrutinizes diverse biomimetic fish fin morphologies, with particular emphasis on variations in the Strouhal number and angle of attack, to elucidate hydrodynamic performance and wake evolution. The results demonstrate that as the fin thickness increases, the propulsion efficiency decreases within the Strouhal number range of St = 0.2, 0.4. Conversely, within the range of St = 0.6 to 1.0, the efficiency variations stabilize. For all three fin morphologies, an increase in the Strouhal number significantly augmented both the lift-to-drag ratio and thrust, concomitant with a transition in the wake structure from smaller vortices to a larger alternating vortex shedding pattern. Furthermore, within the Strouhal number range of St = 0.2 to 0.4, the propulsion efficiency exhibits an increase, whereas in the range of St = 0.6 to 1.0, the propulsion efficiency stabilizes. As the angle of attack increases, the drag coefficient increases significantly, while the lift coefficient exhibits a diminishing rate of increase. An increased fin thickness adversely affects the hydrodynamic performance. However, this effect attenuates at higher Strouhal numbers. Conversely, variations in the angle of attack manifest a more pronounced effect on hydrodynamic performance. A thorough investigation and implementation of the hydrodynamic mechanisms demonstrated by swimming fish in complex flow environments enables the development of bio-inspired propulsion systems that not only accurately replicate natural swimming patterns, but also achieve superior locomotion performance and robust environmental adaptability.

Quantitative study on the relationship between land use and land cover and diatom community in urban streams - Xiang Chen; Weiqi Zhou; Wenjuan Yu; Mingwei Yang; Dong Sheng; Kangyong Li; Na Li; Yuling Ou; Feng Wei (Environmental Science and Pollution Research, 2024)

Bioavailability of dissolved organic matter (DOM) derived from seaweed Gracilaria lemaneiformis meditated by microorganisms - Xiao-Li Ou; Lin-Jian Ou; Yu-Feng Yang (Marine Pollution Bulletin, 2024)

Heterosis of the interspecific sea urchin hybrids between Strongylocentrotus intermedius and Heliocidaris crassispina - Fanjiang Ou; Xiaofei Leng; Xuechun Jiang; Hao Guo; Peng Liu; Wenzhuo Tian; Xuguang Li; Lijie Wang; Jun Ding; Yaqing Chang; Weijie Zhang (Aquaculture, 2024)

Temperature differentially regulates estuarine microbial N2O production along a salinity gradient - Tie-Qiang Mao; Yong Zhang; Ya-Fei Ou; Xiao-Fei Li; Yan-Ling Zheng; Xia Liang; Min Liu; Li-Jun Hou; Hong-Po Dong (Water Research, 2024)

The IGD-based prediction strategy for dynamic multi-objective optimization - Yaru Hu; Jiankang Peng; Junwei Ou; Yana Li; Jinhua Zheng; Juan Zou; Shouyong Jiang; Shengxiang Yang; Jun Li (Swarm and Evolutionary Computation, 2024)

Mapping the electric field of high-definition transcranial electrical stimulation across the lifespan - Weiwei Ma; Feixue Wang; Yangyang Yi; Yu Huang; Xinying Li; Ya'ou Liu; Yiheng Tu (Science Bulletin, 2024)

Experimental and numerical study on dynamic responses of a TLP-type modular floating structure system - Yanwei Li; Nianxin Ren; Wenyu Cai; Yaqiong Liu; Jinping Ou (Ocean Engineering, 2024)

Identification and analysis of microplastic aggregation in CAR-T cells - Zhao Yin; Yizhen Huang; Yangmin Zhu; Qi Zhong; Huijuan Shen; Shaya Mahati; Jing Huang; Guangchao Li; Ruiming Ou; Zhi Liu; Qing Zhang; Shuang Liu (Journal of Hazardous Materials, 2024)

Visual signal transduction for environmental stewardship: A novel biosensing approach to identify and quantify chlorpyrifos-related residues in aquatic environments - Can Wu; Yan Guo; Yu-xuan Xie; Shun-yu Hu; Jia-ming Ou; Bo-xin Li; Nai-xing Zhang; Chang-ye Hui (Journal of Hazardous Materials, 2024)

Acrolein scavengers and detoxification: From high-throughput screening of flavonoids to mechanistic study of epigallocatechin gallate - Kaiyu Jiang; Zhao Yin; Wei Gong; Yu-Xuan Liang; Juncai Tu; Xiaoya Tao; Zhengqi Liu; Yuanyuan Hu; Jinjin Li; Xiaoming Guo; Juanying Ou; Jie Zheng; et al. (Journal of Hazardous Materials, 2024)

Optimizing LaNiO3 catalysts with urea-assisted sol-gel synthesis for dry reforming of methane - Huayu Qiu; Kang Hui Lim; Zhiliang Ou; Claudia Li; Yuan Wang; Lei Tang; Xin Huang; Jingyu Ran; Sibudjing Kawi (Journal of Environmental Chemical Engineering, 2024)

Thermodynamic analysis of the air separation unit and CO2 purification unit in the semi-closed supercritical CO2 cycle with nearly zero emission - Ruifan Li; Tuantuan Xin; Hongyu Xu; Zhikun Ou; Yuhao Liu; Cheng Xu (Fuel, 2024)

Catalytic elevation effect of methylglyoxal on invertase and characterization of MGO modification products - Yixin Li; Zitong Wang; Jiaqi Wu; Jie Zheng; Fu Liu; Juanying Ou; Caihuan Huang; Shiyi Ou (Food Chemistry, 2024)

Characterization of the key aroma compounds in different varieties of hops by application of the Sensomics approach - Zejie Ou; Shiyu Chang; Shuchang Li; Yanli Tan; Yuenan Zhou; Xueli Pang (Food Chemistry, 2024)

Sludge-derived biostimulants promote glycosylation of tricin and luteolin in the flavone and flavonol biosynthesis to enhance anti-inflammatory activities of rice - Xin Yuan; Yu Hua; Shu-xian Chen; Qi Song; Xiao-ou Li; Yue Zhang; Xiao-hu Dai (Environmental Research, 2024)

The association between green space around schools, screen time for entertainment, and adolescent depressive symptoms: A nationwide study from China - Yu Liu; Shuqin Li; Tongyan Deng; Lanlan Li; Runyu Wei; Ying Zhang; Jinping Ou; Fangbiao Tao; Yuhui Wan (Environmental Research, 2024)

Continuous peroxymonosulfate activation by a novel CoFe2O4-functionalized carbon fiber electroactive filter towards ultrafast and cost-effective decontamination: Performance, mechanism and application - Dengao Chang; Yi Luo; Siyuan Song; Yu Huang; Yalun Zhao; Yun Ou; Ziming Li; Xu Wang (Chemical Engineering Journal, 2024)

In-situ construction of dual-coated silicon/carbon composite anode for fast-charging Li-ion batteries - Shijie Wu; Heng Wu; Xiangjian Kong; Yuting Li; Guobao Xu; Jincang Su; Jianyu Huang; Gang Wang; Xing Ou (Chemical Engineering Journal, 2024)

Alloyed geometric structure strategy enables high-quality water-soluble quantum dots for ultrasensitive fluorescence immunoassay - Wen Ou; Kaijie Zhu; Xingchang Lu; Dongliang Hu; Zheng Wang; Yang Li; Peixian Li; Zhe Liu; Wenxin Zhou; Xiaoqi Hou; Xuanyong Liu (Chemical Engineering Journal, 2024)

Study on the influence of early frost attack on the performance of cement mortar - Shuai Bai; Lingbo Yu; Yankui Jian; Mingchao Ren; Xinchun Guan; Hui Li; Jinping Ou (Cold Regions Science and Technology, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Lactobacillus rhamnosus GG Regulates Host IFN-I Through the RIG-I Signalling Pathway to Inhibit Herpes Simplex Virus Type 2 Infection - Jingyu Wang; Mei Huang; Yuqi Du; Haoming Chen; Zixiong Li; Taiyu Zhai; Zihao Ou; Yiyi Huang; Fan Bu; Haojun Zhen; Ruoru Pan; Yubing Wang; et al. (Probiotics and Antimicrobial Proteins, 2024)
Numerous recent studies have demonstrated that the commensal microbiota plays an important role in host immunity against infections. During the infection process, viruses can exhibit substantial and close interactions with the commensal microbiota. However, the associated mechanism remains largely unknown. Therefore, in this study, we explored the specific mechanisms by which the commensal microbiota modulates host immunity against viral infections. We found that the expression levels of type I interferon (IFN-I) and antiviral priming were significantly downregulated following the depletion of the commensal microbiota due to treatment with broad-spectrum antibiotics (ABX). In addition, we confirmed a unique molecular mechanism underlying the induction of IFN-I mediated by the commensal microbiota. In vivo and in vitro experiments confirmed that Lactobacillus rhamnosus GG (LGG) can suppress herpes simplex virus type 2 (HSV-2) infection by inducing IFN-I expression via the retinoic acid-inducible gene-I (RIG-I) signalling pathway. Therefore, the commensal microbiota-induced production of IFN-I provides a potential therapeutic approach to combat viral infections. Altogether, understanding the complexity and the molecular aspects linking the commensal microbiota to health will help provide the basis for novel therapies already being developed. Graphical Abstract

Analysis of PANoptosis-related ceRNA network reveals lncRNA MIR17HG involved in osteogenic differentiation inhibition impaired by tumor necrosis factor-α - Jia-Xuan Li; Yu-Dun Qu; Chang-Liang Xia; Wei Zhang; Song-Song Wang; Shuan-Ji Ou; Yang Yang; Yong Qi; Chang-Peng Xu (Molecular Biology Reports, 2024)
Background Inflammatory cytokines such as Interleukin 1β(IL1β), IL6,Tumor Necrosis Factor-α (TNF-α) can inhibit osteoblast differentiation and induce osteoblast apoptosis. PANoptosis, a newly identified type of programmed cell death (PCD), may be influenced by long noncoding RNA (lncRNAs) which play important roles in regulating inflammation. However, the potential role of lncRNAs in inflammation and PANoptosis during osteogenic differentiation remains unclear. This study aimed to investigate the regulatory functions of lncRNAs in inflammation and apoptosis during osteogenic differentiation. Methods and results High-throughput sequencing was used to identify differentially expressed genes involved in osteoblast differentiation under inflammatory conditions. Two lncRNAs associated with inflammation and PANoptosis during osteogenic differentiation were identified from sequencing data and Gene Expression Omnibus (GEO) databases. Their functionalities were analyzed using diverse bioinformatics methodologies, resulting in the construction of the lncRNA-miRNA-mRNA network. Among these, lncRNA (MIR17HG) showed a high correlation with PANoptosis. Bibliometric methods were employed to collect literature data on PANoptosis, and its components were inferred. PCR and Western Blotting experiments confirmed that lncRNA MIR17HG is related to PANoptosis in osteoblasts during inflammation. Conclusions Our data suggest that TNF-α-induced inhibition of osteogenic differentiation and PANoptosis in MC3T3-E1 osteoblasts is associated with MIR17HG. These findings highlight the critical role of MIR17HG in the interplay between inflammation, PANoptosis, and osteogenic differentiation, suggesting potential therapeutic targets for conditions involving impaired bone formation and inflammatory responses.

Disintegration of Cav-1/β-catenin complex attenuates neuronal death after ischemia–reperfusion injury by promoting β-catenin nuclear translocation - Peng Guo; Wan Wang; Zhiyan Liang; Yihang Li; Xiangling Ou; Ming Li; Bin Wang; Xuewen Wei; Linyan Huang; Suhua Qi (Molecular Biology Reports, 2024)

SCINet: A Segmentation and Classification Interaction CNN Method for Arteriosclerotic Retinopathy Grading - Xiongwen Quan; Xingyuan Ou; Li Gao; Wenya Yin; Guangyao Hou; Han Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Competitive adsorption of polycyclic aromatic hydrocarbons on phosphorus tailing-modified sludge biochar provides mechanistic insights - Anrong Liu; Li-Juan Feng; Yangyang Ou; Xiaoya Zhang; Jinhong Zhang; Hongyan Chen (Environmental Geochemistry and Health, 2024)

Soil nutrient levels are associated with suppression of banana Fusarium wilt disease - Yifan Cao; Yannan Ou; Nana Lv; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Soil Ecology Letters, 2024)

Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Incorporating embodied carbon transfer and sequestration service flows into regional carbon neutrality assessment in China - Henghui Xi; Xiaodan Liu; Xue Ding; Conghong Huang; Yu Tao; Qin Tao; Jiman Li; Xianbo Cheng; Fei Wang; Weixin Ou (Sustainable Production and Consumption, 2024)

Origins of atmospheric nitrous acid and their contributions to OH radical from ship plumes, marine atmosphere, and continental air masses over South China Sea - Xue Ni; Cuizhi Sun; Zhenhao Ling; Yao Li; Yongyun Zhang; Hengjia Ou; Baoling Liang; Qibin Sun; Shixin Mai; Shengzhen Zhou; Jun Zhao (Science of The Total Environment, 2024)

Assessment of the relationship between mineral extraction in the southern hemisphere and sustainable development - Xiongying Li; Hongjing Ou; Puyan Nie (Resources Policy, 2024)

Biocontrol efficacy and mechanism of endophytic Bacillus velezensis HE-23 from Aucklandia lappa roots against the gray mold of postharvest tomato - Wei Jian; Yu Chen; Shiyu Liu; Xiaogang Ou; Lixinyu Sun; Huiming Gong; Qiutong Mu; Zhengguo Li; Zhengwu Zhao (Postharvest Biology and Technology, 2024)

A general unit hydrograph theory for water level and tidal range distributions in the Modaomen Estuary, China - Bo Li; Huayang Cai; Gaojin Li; Jing Liu; Zhenyan She; Yajun Wang; Suying Ou; Feng Liu; Tongtiegang Zhao; Kairong Lin (Journal of Hydrology, 2024)

Effectiveness and impact factors of passive convergence-permeable reactive barrier (PC-PRB): Insights from tracer simulation study - Kaixuan Zheng; Yihao Li; Shiyang Tao; Jie Ding; Fuli Li; Xiangqin Peng; Jieyong Ou; Yanzhi Chen; Lei Lei; Wei Wang; Hongtao Wang; Na Liu; et al. (Journal of Environmental Management, 2024)

Dissection of molecular mechanisms of liver injury induced by microcystin-leucine arginine via single-cell RNA-sequencing - Yunmeng Bai; Yali Song; Miaoran Li; Jinhuan Ou; Hong Hu; Nan Xu; Min Cao; Siyu Wang; Lin Chen; Guangqing Cheng; Zhijie Li; Gang Liu; et al. (Journal of Environmental Sciences, 2024)

Impact of millennial-scale fluctuations of the Siberian High on Holocene aeolian activity: Insights from Lake Ailike in arid Central Asia - Yaru Chen; Xingqi Liu; Junfeng Li; Xiangjun Liu; Xianjiao Ou (Global and Planetary Change, 2024)

Protonated carbon nitride cooperated with iron porphyrin metal–organic framework for boosting photocatalytic hydrogen production and degradation of tetracycline - Wenjun Zhu; Lixia Qin; Zhiyong Ou; Jianwei Tao; Taiyang Zhang; Shi-Zhao Kang; Xiangqing Li (Fuel, 2024)

Thermal upheaval buckling framework of a graphene-reinforced subsea pipeline laid on an arched concave seabed - Zhaochao Li; Di Hu; Meiling Shen; Hao Huang; Zhihua Ou (Engineering Structures, 2024)

A new controllable weak recycling inflow turbulence generator for evaluating wind effects on building in LES - Jinghan Wang; Chao Li; Lingwei Chen; Shengtao Zhou; Gang Hu; Jinping Ou (Engineering Structures, 2024)

Potassium isotope evidence for subducted upper and lower oceanic crust in ocean island basalt sources - Haiyang Liu; Ying-Yu Xue; Jörg Geldmacher; Kaj Hoernle; Uwe Wiechert; Shichao An; Hai-Ou Gu; He Sun; Fanfan Tian; Xiaoqiang Li; Kun Wang; Hongli Zhu; et al. (Earth and Planetary Science Letters, 2024)

Lead iodide secondary growth and π-π stack regulation for sequential perovskite solar cells with 23.62% efficiency - Zhangfeng Huang; Zhuowei Du; Zhu Ma; Yujie Zheng; Qian Zhang; Wei You; Junbo Yang; Tangjie Yu; Shanyue Hou; Guoming Li; Hao Du; Yixian Li; et al. (Chemical Engineering Journal, 2024)

Natural enzyme cascade bimetallic sulfide MoCuSx nanozyme for synergistic photothermal/photodynamic enhanced chemodynamic antimicrobial therapy of wound infection - Caiyun Xu; Junqin Li; Chunlei Ou; Jing Yang; Shuting Fu; Weiqing Hu; Li Wang; Zefeng Wang; Luo Hai; Le Deng; Dinggeng He (Chemical Engineering Journal, 2024)

Removal of Typical Heavy Metals from Soil by the Synergistic Interaction between Microbubbles and Washing Agents: Experiments, Influences, and Mechanisms - Jinbao Ou; Xi Wang; Kangning Gao; Mingyu Ma; Juan Wu; Shihong Xu; Dengxin Li; Wenjing Sang (Water, Air, & Soil Pollution, 2024)

TRIM28 Fosters Microglia Ferroptosis via Autophagy Modulation to Enhance Neuropathic Pain and Neuroinflammation - Jian Tang; Qi Chen; Li Xiang; Ting Tu; Ying Zhang; Cehua Ou (Molecular Neurobiology, 2024)

Allicin Ameliorated High-glucose Peritoneal Dialysis Solution-induced Peritoneal Fibrosis in Rats via the JAK2/STAT3 Signaling Pathway - Linwang Gan; Lei Geng; Qiancheng Li; Liling Zhang; Yan Huang; Jiaru Lin; Santao Ou (Cell Biochemistry and Biophysics, 2024)

Rail transit disruptions, traffic generations, and adaptations: Quasi-experimental evidence from Hong Kong - Yifu Ou; Xin Li; Kyung-Min Nam (Transportation Research Part D: Transport and Environment, 2024)

Joint effects of air pollution and genetic susceptibility on incident primary open-angle glaucoma - Hao-Neng Huang; Pan-Pan Zhu; Zhou Yang; Yi-Ming Tao; Xiaofeng Ma; Hai-Bing Yu; Li Li; Chun-Quan Ou (Science of The Total Environment, 2024)

Single-grain K-feldspar post-IR IRSL dating of glaciofluvial sediments of Guxiang Glaciation in SE Tibetan Plateau - Yantian Xu; Xianjiao Ou; Xiaojun Zou; Cai Yang; Geoff A.T. Duller; Yang Li; Helen M. Roberts; Kunmei Yang; Lanhua Zeng (Quaternary Geochronology, 2024)

Study on the hydrodynamic performance of a self-propelled robot fish swimming in pipelines environment - Ou Xie; Chenbo Zhang; Can Shen; Yufan Li; Dawei Zhou (Ocean Engineering, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Spatial phytoplankton community structure revealed by photosynthetic pigments in the tropical estuarine-coastal zone (Bangladesh) - Yu Mo; Keliang Chen; Mohammad Kawser Ahmed; Haifeng Gu; Danyun Ou; Weiwen Li; Hao Huang; Lei Wang (Marine Environmental Research, 2024)

Provincial equity and enhanced health are key drivers for China's 2060 carbon neutrality - Jiaxin Dong; Siwei Li; Yisheng Sun; Weishu Gong; Ge Song; Yu Ding; Jie Yang; Mengfan Teng; Ruilin Wang; Jia Xing; Yang Ou; Wei Gong (Journal of Cleaner Production, 2024)

Prolonging the time of manure by water soaking can alleviate the inhibition of lime disinfection wastewater in a batch anaerobic digestion of swine manure - Wei Wang; Dehan Wang; Sicheng Li; Xiaoyu Ou (Journal of Environmental Chemical Engineering, 2024)

Genome-wide epigenetic dynamics of tea leaves under mechanical wounding stress during oolong tea postharvest processing - Yucheng Zheng; Xiaoxi Ou; Qiuming Li; Zongjie Wu; Liangyu Wu; Xinlei Li; Bo Zhang; Yun Sun (Food Research International, 2024)

Discovery of Momordin Ic that selectively reduces PD-L1 expression in multiple myeloma cells by recruiting SYVN1 - Sizhi Wu; Wen Yan; Wei Ma; Guangchao Li; Zhi Liu; Ruiming Ou; Jing Huang; Huijuan Shen; Qi Zhong; Yangmin Zhu; Qing Zhang; Zhao Yin; et al. (Food Bioscience, 2024)

Structural behaviour and design of cold-formed austenitic stainless steel flat-oval hollow section beam-columns - Shuai Li; Andi Su; Man-Tai Chen; Ou Zhao (Engineering Structures, 2024)

High efficiency and cost-effective innovative self-oxidation in-situ removal scheme for the preparation of battery-grade manganese sulphate - Yang Ou; Yongbin Yang; Hongrui Chen; Ke Li; Yinrui Dong; Qian Li; Yan Zhang; Tao Jiang (Chemical Engineering Journal, 2024)

The growth model of lead-free CsEuBr3 nanocrystals - Xiang Wu; Feilong Wang; Yikun Wang; Chuangchang Lei; Yaohua Li; Shiting Ou; Wenbo Luo; Shuyu Zhang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Probiotic Potential, Antibacterial, and Antioxidant Capacity of Aspergillus luchuensis YZ-1 Isolated From Liubao Tea - Xiyan Zhang; Rui Jiao; Hui Li; Dexin Ou; Danfeng Zhang; Yizhong Shen; Na Ling; Yingwang Ye (Probiotics and Antimicrobial Proteins, 2024)

The New Roles of traf6 Gene Involved in the Development of Zebrafish Liver and Gonads - Hongyan Xu; Wenzhuo Ban; Jiaming Tian; Jianfei Xu; Zhimin Tan; Sendong Li; Kaili Chen; Mi Ou; Kaibin Li (Marine Biotechnology, 2024)

Changes in immune subsets during chemotherapy as prognosis biomarkers for multiple myeloma patients by longitudinal monitoring - Pengcheng Xu; Ying Li; Xibing Zhuang; Lei Yue; Yanna Ma; Wenjin Xue; Lili Ji; Yanxia Zhan; Yang Ou; Tiankui Qiao; Duojiao Wu; Peng Liu; et al. (Immunologic Research, 2024)

The complete chloroplast genome of white towel gourd (Luffa cylindrica) and phylogenetic analysis - Yihui Gong; Yuanyuan Wei; Guihua Zhou; Yanglan Ou; Canmei Zhang; Peng Li (Genetic Resources and Crop Evolution, 2024)

Salinicola avicenniae sp. nov., a Novel Gammaproteobacterium Isolated from Mangrove Plant, Avicennia marina, in Beibu Gulf, China - Wenquan Zhang; Danyun Ou; Yue Ni; Hao Huang; Weiwen Li; Lei Wang; Shunyang Chen; Guangcheng Chen (Current Microbiology, 2024)

The predictive, preventive, and personalized medicine of depression: gut microbiota and inflammation - Jialin Wu; Guosen Ou; Shiqi Wang; Yaokang Chen; Lu Xu; Li Deng; Huachong Xu; Xiaoyin Chen (EPMA Journal, 2024)

Disrupted brain functional asymmetry at rest in patients with major depressive disorder associated with sleep disturbances - Dan Lv; Yangpan Ou; Huabing Li; Feng Liu; Ping Li; Dongsheng Lv; Jingping Zhao; Wenbin Guo (Brain Imaging and Behavior, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

SIZ1-mediated SUMOylation of CPSF100 promotes plant thermomorphogenesis by controlling alternative polyadenylation - Zhibo Yu; Jun Wang; Cheng Zhang; Qiuna Zhan; Leqian Shi; Bing Song; Danlu Han; Jieming Jiang; Junwen Huang; Xiaolin Ou; Zhonghui Zhang; Jianbin Lai; et al. (Molecular Plant, 2024)

Uranium enrichment driven by paleomarine condition and event deposition: Insights from the lower Cambrian Niutitang Formation organic-rich shales in northeastern Guizhou, South China - Zhongzheng Tong; Jinchuan Zhang; Guangxi Ou; Zhen Li; Dongsheng Wang; Yaning Wu; Xingqi Li; Shijing Chen (Marine and Petroleum Geology, 2024)

Adsorptive removal of aflatoxin B1 via spore protein from Aspergillus luchuensis YZ-1 - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Journal of Hazardous Materials, 2024)

Machine learning-driven source identification and ecological risk prediction of heavy metal pollution in cultivated soils - Zihan Bi; Jian Sun; Yutong Xie; Yilu Gu; Hongzhen Zhang; Bowen Zheng; Rongtao Ou; Gaoyuan Liu; Lei Li; Xuya Peng; Xiaofeng Gao; Nan Wei (Journal of Hazardous Materials, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Efficient treatment of high-concentration pharmaceutical wastewater with high-salinity by chemical synthesis coupling with evaporation: From lab-scale to pilot-scale - Mushi Li; Xi Wang; Mingyu Ma; Juan Wu; Yang Chen; Jinbao Ou; Xinyue Chen; Qianying Zhou; Wenjing Sang; Shihong Xu; Li Cai; Dengxin Li (Chemical Engineering Journal, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

Accessing color-tunable afterglows from single conventional chromophore-based polysaccharide films through palette strategy - Tianjie Wang; Zhengshuo Wang; Zijin Li; Zheng Chen; Haowei Sun; Hua Yuan; Hanlin Ou; Xiaoyu Huang; Yeqiang Tan (Chemical Engineering Journal, 2024)

Innovations in food waste management: from resource recovery to sustainable solutions - Na Xiao; Lingxian Kong; Mengmeng Wei; Xiufang Hu; Ou Li (Waste Disposal & Sustainable Energy, 2024)

The characteristics and environmental significance of BVOCs released by aquatic macrophytes - Qiutong Peng; Yujing Yang; Wenhui Ou; Lifei Wei; Zhongqiang Li; Xuwei Deng; Qiang Gao (Chemosphere, 2024)

Single grain pIRIR dating of glacigenic deposits in the Yuzhu Peak area of Kunlun Mountains of Tibetan Plateau revealed the glaciations during Holocene period - Jilei Yang; Yixuan Wang; Guoqiang Li; Xiaoyan Wang; Tao Lu; Weiping Ding; Xianjiao Ou; Donglin Gao (Quaternary Geochronology, 2024)

Urban biodiversity conservation: A framework for ecological network construction and priority areas identification considering habit differences within species - Xiaoxi Li; Xiaoyang Ou; Xingyue Sun; Haoran Li; Yixiao Li; Xi Zheng (Journal of Environmental Management, 2024)

Concentration and health risk assessment of 16 rare earth elements in six types of tea in China - Tong Ou; Hanbing Bao; Yujing Zhou; Zhaoping Liu; Haixia Sui; Ling Yong; Weifeng Mao; Yibaina Wang; Huihui Bao; Xiao Xiao; Lei Zhang; Dajin Yang; et al. (Food and Chemical Toxicology, 2024)

Effects of nitrogen regulation on heavy metal phytoextraction efficiency (Leucaena leucocephala): Application of a nitrogen fertilizer and a fungal agent - Chao Liu; Jiayi Liu; Xiaoli Mei; Jiaxin Zheng; Kang Zheng; Ou Li; Chonlong Chio; Janak Khatiwada; Xiaoxia Zhang; Dong Wang; Haibo Hu; Wensheng Qin; et al. (Environmental Pollution, 2024)

An innovative simplified approach for conductive heat flux in pavement structures - Fanghua Li; Xiaoduo Ou (Energy and Buildings, 2024)

In vivo fiber-optic fluorescent sensor for real-time pH monitoring of tumor microenvironment - Zesen Li; Ni Lan; Zhongyuan Cheng; Fangzhou Jin; Enlai Song; Zhiyuan Xu; Yongkang Zhang; You-Zhen Feng; Xiangran Cai; Yang Ran; Bai-Ou Guan (Chemical Engineering Journal, 2024)

Molecular mechanisms and atmospheric implications of the simplest criegee intermediate and hydrochloric acid chemistry in the gas phase and at the aqueous interfaces - Chao Ding; Mingjie Wen; Tianlei Zhang; Zeyao Li; Rongrong Li; Rui Wang; Ting Ou; Fengmin Song; Qiang Zhang (Atmospheric Environment, 2024)

Nitrite induces hepatic glucose and lipid metabolism disorders in zebrafish through mitochondrial dysfunction and ERs response - Hui Yang; Kang Ou-Yang; Ya He; Xinyu Wang; Liangmou Wang; Qing Yang; Dapeng Li; Li Li (Aquatic Toxicology, 2024)

Multiomics Analyses Explore the Immunometabolic Interplay in the Liver of White Crucian Carp (Carassius cuvieri) After Aeromonas veronii Challenge - Fei Wang; Zi-Rou Zhong; Qing Xie; Jie Ou; Ning-Xia Xiong; Ming-Zhu Huang; Shi-Yun Li; Gang Hu; Zi-Le Qin; Sheng-Wei Luo (Marine Biotechnology, 2024)

Exploring the relationship between infectious agents and autoimmune diseases: a review - Zhihui Feng; Xueli Yang; Biao Zhang; Chune Mo; Chunhong Li; Xiayu Tian; Chong Zhang; Minglin Ou; Xianliang Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Unraveling the hydrogeochemical characteristics and pollution sources of groundwater in an intensive industrial area, East China - Xujuan Huang; Li Ou; Zhendong Xie; Chi Jiang; Yibin Zhao; Guangcai Wang (Environmental Science and Pollution Research, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

Harnessing key bacteria from suppressive soil to mitigate banana Panama disease - Nana Lv; Mohammadhossein Ravanbakhsh; Shuqin Ling; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Biology and Fertility of Soils, 2024)

A self-catalyzing strategy for co-immobilization of two distinct proteins at equimolar ratio: A case study of 3A and 2C to develop a chromatographic method for finding prospective dual-target compoundsfrom complex matrices - Jia Quan; Yuanyuan Ou; Kaihua Long; Yu Li; Jing Kang; Yaqi Wang; Xue Zhao; Xinfeng Zhao (Analytica Chimica Acta, 2024)

Construction of adamantane-based monolithic column with three-dimensionally porous structure for small molecules separation and biosample analysis - Wen Li; Chunli Gao; Yan Wang; Haiyue Zuo; Yangyang Bian; Cong Li; Shujuan Ma; Yehua Shen; Junjie Ou (Analytica Chimica Acta, 2024)

Anti-drift performance of a hoods spray system for soybean (Glycine max (L.) Merr.)-maize (Zea mays L.) strip intercropping - Guanqun Wang; Mengmi Liu; Mingxiong Ou; Weidong Jia; Li Jiang; Ziyu Li; Xiang Dong; Yourui Huang; Tie Zhang (Crop Protection, 2024)

Treatment of manganese and lead poisoning with sodium para-aminosalicylic acid: A contemporary update - Yu-Han Xie; Han-Xiao Song; Jian-Chao Peng; Shao-Jun Li; Shi-Yan Ou; Michael Aschner; Yue-Ming Jiang (Toxicology Letters, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Dynamic modulation of nodulation factor receptor levels by phosphorylation-mediated functional switch of a RING-type E3 ligase during legume nodulation - Hao Li; Yajuan Ou; Jidan Zhang; Kui Huang; Ping Wu; Xiaoli Guo; Hui Zhu; Yangrong Cao (Molecular Plant, 2024)

Indole-3-acetic acid regulating the initial adhesion of microalgae in biofilm formation - Zhihuai Xie; Zixuan Ou; Meili Zhang; Guotao Tang; Xiaoshi Cheng; Wangbei Cao; Jingyang Luo; Fang Fang; Yingqiang Sun; Ming Li; Juan Cai; Qian Feng (Environmental Research, 2024)

Cadmium(II) adsorption by recyclable Zeolite-Loaded Hydrogel: Extension to the removal of Cadmium(II) from contaminated soil - Hanjing Xu; Ziqing Ou; Wenyan Li; Tian Hu; Yulong Zhang; Huijuan Xu; Jinjin Wang; Yongtao Li (Chemical Engineering Journal, 2024)

Engineering of phytic acid-coated Prussian nanoparticles for combined Nitric oxide and Low-Temperature photothermal therapy of osteosarcoma - Ye Zhang; Hai Mou; Qiu Huang; Changchun Jian; Xianglong Li; Sinan Chen; Yuxing Chen; Bailong Tao; Yunsheng Ou (Chemical Engineering Journal, 2024)

Lnc-HIBADH-4 Regulates Autophagy-Lysosome Pathway in Amyotrophic Lateral Sclerosis by Targeting Cathepsin D - Jingxuan Huang; Yujiao Yu; Dejiang Pang; Chunyu Li; Qianqian Wei; Yangfan Cheng; Yiyuan Cui; Ruwei Ou; Huifang Shang (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is the most prevalent and lethal class of severe motor neuron diseases (MND) with no efficacious treatment. The pathogenic mechanisms underlying ALS remain unclear. Nearly 90% of patients exhibit sporadic onset (sALS). Therefore, elucidating the pathophysiology of ALS is imperative. Long non-coding RNA (lncRNA) is a large class of non-coding RNAs that regulate transcription, translation, and post-translational processes. LncRNAs contribute to the pathogenesis of diverse neurodegenerative disorders and hold promise as targets for interference in the realm of neurodegeneration. However, the mechanisms of which lncRNAs are involved in ALS have not been thoroughly investigated. We identified and validated a downregulated lncRNA, lnc-HIBADH-4, in ALS which correlated with disease severity and overall survival. Lnc-HIBADH-4 acted as a “molecular sponge” regulating lysosomal function through the lnc-HIBADH-4/miR-326/CTSD pathway, thereby impacting autophagy-lysosome dynamics and the levels of cell proliferation and apoptosis. Therefore, this study discovered and revealed the role of lnc-HIBADH-4 in the pathogenesis of ALS. With further research, lnc-HIBADH-4 is expected to provide a new biomarker in the diagnosis and treatment of ALS.

Mechanisms and clinical landscape of N6-methyladenosine (m6A) RNA modification in gastrointestinal tract cancers - Dan-Hua Zhu; Kun-Kai Su; Xiao-Xi Ou-Yang; Yan-Hong Zhang; Xiao-Peng Yu; Zu-Hong Li; Seyedeh-Sara Ahmadi-Nishaboori; Lan-Juan Li (Molecular and Cellular Biochemistry, 2024)
Epigenetics encompasses reversible and heritable chemical modifications of non-nuclear DNA sequences, including DNA and RNA methylation, histone modifications, non-coding RNA modifications, and chromatin rearrangements. In addition to well-studied DNA and histone methylation, RNA methylation has emerged as a hot topic in biological sciences over the past decade. N6-methyladenosine (m6A) is the most common and abundant modification in eukaryotic mRNA, affecting all RNA stages, including transcription, translation, and degradation. Advances in high-throughput sequencing technologies made it feasible to identify the chemical basis and biological functions of m6A RNA. Dysregulation of m6A levels and associated modifying proteins can both inhibit and promote cancer, highlighting the importance of the tumor microenvironment in diverse biological processes. Gastrointestinal tract cancers, including gastric, colorectal, and pancreatic cancers, are among the most common and deadly malignancies in humans. Growing evidence suggests a close association between m6A levels and the progression of gastrointestinal tumors. Global m6A modification levels are substantially modified in gastrointestinal tumor tissues and cell lines compared to healthy tissues and cells, possibly influencing various biological behaviors such as tumor cell proliferation, invasion, metastasis, and drug resistance. Exploring the diagnostic and therapeutic potential of m6A-related proteins is critical from a clinical standpoint. Developing more specific and effective m6A modulators offers new options for treating these tumors and deeper insights into gastrointestinal tract cancers.

Luminescence dating of cobbles buried in moraines from the source area of the Litang River (Konglongluo Valley), eastern Tibetan Plateau - Kunmei Yang; Xianjiao Ou; Yang Li; Geraint Jenkins; Pan Yao; Daobin Tang; Yantian Xu; Jinming Xie; Lanhua Zeng; Xiangjun Liu (Quaternary Geochronology, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Insights into benzopyrene formation mechanism in flames: A density functional theory study - Zehong Li; Wei Zhang; Shuo Ning; Zhaohui Chen; Quanchang Zhang; Zhenzhu Ma; Xili Yang; Jincong Ou (Fuel, 2024)

Transcriptomic and biochemical analyses reveal the antifungal mechanism of cell-free supernatant from Aspergillus luchuensis YZ-1 against Aspergillus flavus - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Food Bioscience, 2024)

Effects of essential amino acids supplementation in a low-protein diet on growth performance, intestinal health and microbiota of juvenile blotched snakehead (Channa maculata) - Shuzhan Fei; Jiamin Kang; Mi Ou; Haiyang Liu; Xincheng Zhang; Qing Luo; Kaibin Li; Kunci Chen; Jian Zhao (Fish & Shellfish Immunology, 2024)

Machine-learning-assisted design of high strength steel I-section columns - Jinpeng Cheng; Xuelai Li; Ke Jiang; Shuai Li; Andi Su; Ou Zhao (Engineering Structures, 2024)

In situ formed antibacterial hydrogel with collagenase-responsive activity for prevention of MRSA-induced osteomyelitis - Kejia Li; Xiaoyan Ju; Xiangli Li; Guojun Lu; Jinzhao Ou; Dandan Xu; Chenxiao Wan; Meng Zhu; Chuanchao Du; Ye Tian; Zhongwei Niu (Chemical Engineering Journal, 2024)

Dual–network carboxymethyl chitosan conductive hydrogels for multifunctional sensors and high–performance triboelectric nanogenerators - Ting Xie; Fangyan Ou; Chuang Ning; Liang Tuo; Zhichao Zhang; Yi Gao; Wenyu Pan; Zequan Li; Wei Gao (Carbohydrate Polymers, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Relating extreme precipitation events to atmospheric conditions and driving variables in China - Qianxi Ou; Tongtiegang Zhao; Shuo Wang; Yang Liu; Yongyan Wu; Bo Li; Xiaohong Chen (Climate Dynamics, 2024)

Tumor necrosis factor α1 decreases mucosal immune and antioxidant response in the midgut of hybrid fish (white crucian carp ♀ × red crucian carp ♂) - Ke‐Xin Li; Ning‐Xia Xiong; Jin‐Fang Huang; Shi‐Yun Li; Jie Ou; Fei Wang; Sheng‐Wei Luo (Journal of Fish Biology, 2024)
Tumor necrosis factor α1 (TNFα) is a pleiotropic cytokine involved in immune regulation and cellular homeostasis, but the crucial role of TNFα in fish gut remained unclear. The current study aimed to evaluate the immunoregulatory function of TNFα1 on gut barrier in a novel hybrid fish (WR), which was produced by crossing white crucian carp ( Carassius cuvieri , ♀) with red crucian carp ( Carassius auratus red var, ♂). In this study, WR ‐tnfα1 sequence was identified, and a high‐level expression was detected in the intestine. Elevated levels of WR ‐tnfα1 expressions were detected in immune‐related tissues and cultured fish cells on stimulation. The appearance of vacuolization and submucosal rupture was observed in TNFα1‐treated midgut of WR, along with elevated levels of goblet cell atrophy, whereas no significant changes were detected in most expressions of tight‐junction genes and mucin genes. In contrast, WR receiving gut perfusion with WR‐TNFα1 showed a remarkable decrease in antioxidant status in midgut, whereas the expression levels of apoptotic genes and redox responsive genes increased sharply. These results suggested that TNFα1 could exhibit a detrimental effect on antioxidant defense and immune regulation in the midgut of WR.

Reconstructing the sound speed profile of South China Sea using remote sensing data and long short-term memory neural networks - Yu Zhao; Pan Xu; Guangming Li; Zhenyi Ou; Ke Qu (Frontiers in Marine Science, 2024)
Introduction Sound waves are refracted along the direction of their propagation owing to spatial and temporal fluctuations in the speed of sound in seawater. Errors are compounded when sound speed profiles (SSPs) with low precision are used to detect and locate distant underwater targets because an accurate SSP is critical for the identification of underwater objects based on acoustic data. Only sparse historical spatiotemporal data on the SSP of the South China Sea are available owing to political issues, its complex atmospheric system, and the unique topography of its seabed, because of which frequent oceanic movements at the mesoscale affect the accuracy of inversion of its SSP. Method In this study, we propose a method for the inversion of the SSP of the South China Sea based on a long short-term memory model. We use continuous-time data on the SSP of the South China Sea as well as satellite observations of the height and temperature of the sea surface to make use of the long-term and short-term memory-related capacities of the proposed model. Result It can achieve highly accurate results while using a small number of samples by virtue of the unique structure of its memory. Compared with the single empirical orthogonal function regression method, the inversion accuracy of this model is improved by 24.5%, and it performed exceptionally well in regions with frequent mesoscale movements. Discussion This enables it to effectively address the challenges posed by the sparse sample distribution and the frequent mesoscale movements of the South China Sea.

Single-cell sequencing advances in research on mesenchymal stem/stromal cells - Qingxi Long; Pingshu Zhang; Ya Ou; Wen Li; Qi Yan; Xiaodong Yuan (Human Cell, 2024)

Annual mapping of Spartina alterniflora with deep learning and spectral-phenological features from 2017 to 2021 in the mainland of China - Xiarong Li; Jinyan Tian; Xiaojuan Li; Yongxin Yu; Yang Ou; Lin Zhu; Xiumin Zhu; Bingfeng Zhou; Huili Gong (International Journal of Remote Sensing, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Association between ambient temperature and mammalian-related injuries in Guangzhou, China, 2014–2019 - Jia-Jun Ma; Ze-Jie Xu; Boheng Liang; Zhou Yang; Li Li; Hao-Neng Huang; Bo-Wen Ming; Pengzhe Qin; Chun-Quan Ou (Science of The Total Environment, 2024)

The overpressure and temperature characteristics of high volatile liquid fuel explosions in extreme environments: Effects of low initial ambient temperatures and pressures - Zhongkun Yang; Lingxiao Ou; Jing Zhang; Yongxu Wang; Dan Zhang; Lifeng Xie; Bin Li (Process Safety and Environmental Protection, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

Evaluation of the positioning capability of a novel concept design of dynamic positioning-assisted mooring systems for floating offshore wind turbines - Dongsheng Qiao; Huimin Li; Haizhi Liang; Bin Wang; Weijun Zhang; Jinping Ou (Ocean Engineering, 2024)

Effects of biochar immobilization of Serratia sp. F4 OR414381 on bioremediation of petroleum contamination and bacterial community composition in loess soil - Xuhong Zhang; Manli Wu; Ting Zhang; Huan Gao; Yawen Ou; Mengqi Li (Journal of Hazardous Materials, 2024)

Pathogens inactivation and preservation of Pacific white shrimp by atmospheric cold plasma treatment - Xiulan Liu; Xingyu Chen; Yan Ou; Feng Li; Yang Jiao; Hu Shi (Innovative Food Science & Emerging Technologies, 2024)

Increasing single households challenges household decarbonization in Japan - Liqiao Huang; Yin Long; Zhiheng Chen; Yuan Li; Jiamin Ou; Yosuke Shigetomi; Yoshikuni Yoshida (Global Environmental Change, 2024)

Plastic hinge behavior of rectangular CFRP-confined RC columns: Meso-scale modelling and formulation - Lingling Fan; Liu Jin; Ou Zhao; Jian Liang; Ping Li; Xiuli Du (Engineering Structures, 2024)

Experimental and numerical investigations of austenitic stainless steel semi-oval hollow sections under combined compression and bending - Shuai Li; Tong Guo; Ou Zhao (Engineering Structures, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

Acidification induce chemical and microbial variation in tea plantation soils and bacterial degradation of the key acidifying phenolic acids - Yuhan Zhang; Binjie Wang; Guiwei Wang; Zhisheng Zheng; Ying Chen; Ou Li; Yulong Peng; Xiufang Hu (Archives of Microbiology, 2024)

The biocontrol potentials of rhizospheric bacterium Bacillus velezensis K0T24 against mulberry bacterial wilt disease - Wenlian Jiao; Ju Wen; Na Li; Ting Ou; Changyu Qiu; Yutong Ji; Kai Lin; Xiaojiao Liu; Jie Xie (Archives of Microbiology, 2024)

Betulinic acid attenuates T-2 toxin-induced lung injury by activating Nrf2 signaling pathway and inhibiting MAPK/NF-κB signaling pathway - Chunlin Huang; Zhaoping Ou; Li Kong; You Huang; Wenjiang Yang; Jiayu He; Mingqi Yang; Jing Wu; Siting Xiang; Yu Zhou; Jine Yi (Toxicon, 2024)

In-situ generation of iron activated percarbonate for sustainable sludge dewatering - Chengjian Li; Yu Zhang; Jingsai Ren; Zhihua Mo; Jialin Liang; Maoyou Ye; Wenzhi Ou; Shuiyu Sun; Suiyi Zhu (Science of The Total Environment, 2024)

Reprogramming of DNA methylation patterns mediates perfluorooctane sulfonate-induced fetal cardiac dysplasia - Min Qiu; Jing Chen; Mingqin Liu; Yan Shi; Zhiqiang Nie; Guanghui Dong; Xiaohong Li; Jimei Chen; Yanqiu Ou; Jian Zhuang (Science of The Total Environment, 2024)

Citrus transcription factor CsERF098 cooperates with CsWRKY70 to participate in response of fruit to green mold - Ting Li; Wenjun Wang; Qi Chen; Ou Chen; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Synthesis of polyacrylate-divinylbenzene hydroxamic resins and its gallium adsorption performance in sulfuric acid solution - Yujie Li; Xiangxiang Chen; Bao Guo; Zilin Dai; Zhenxing Kong; Fangxu Li; Juhua Ou (Journal of Water Process Engineering, 2024)

Construction of Co-ZIF-derived CoS2@Cu hollow heterogeneous nanotube array for the detection of hydrazine in environmental water samples - Lian Ou; Jie Yang; Li Xu; Shan Zhao; Xiaoli Xiong; Ting Xiao (Environmental Research, 2024)

High-performance spent coffee grounds-based 3D microporous biochar for the efficient capture of Cd2+ via a multi-pathway mechanism - Zhiwei Jin; Zhenluan Xue; Bo Li; Liying Ou; Linzhe Yan; Lixia Yang; Kai Yin; Jabrane Jouha; Penghui Shao; Zebing Zeng; Shenglian Luo (Chemical Engineering Journal, 2024)

Aqueous-phase product treatment and monetization options of wet waste hydrothermal liquefaction: Comprehensive techno-economic and life-cycle GHG emission assessment unveiling research opportunities - Yuan Jiang; Longwen Ou; Lesley Snowden-Swan; Hao Cai; Shuyun Li; Karthikeyan Ramasamy; Andrew Schmidt; Huamin Wang; Daniel M. Santosa; Mariefel V. Olarte; Mond Guo; Michael R. Thorson (Bioresource Technology, 2024)

Vertical variation in magnetic particles within atmospheric PM in indoor dustfall in industrial cities of northern China - Rui Zhang; Mingrui Li; Duo Wu; Xueping Ren; Zhao Wang; Yuhan Ou (Atmospheric Pollution Research, 2024)

Identification and validation of major and stable quantitative trait locus for falling number in common wheat (Triticum aestivum L.) - Zhi Li; Qinyi Luo; Yujie Gan; Xinli Li; Xia Ou; Yawen Deng; Shulan Fu; Zongxiang Tang; Feiquan Tan; Peigao Luo; Tianheng Ren (Theoretical and Applied Genetics, 2024)

Genetically Predicted Apolipoprotein E Levels with the Risk of Panvascular Diseases: A Mendelian Randomization Study - Yi-Ming Shi; Dian Ou; Jia-Ting Li; Le Bao; Xiao-Dan Liu; Wei Zhang; Huang Ding (Cardiovascular Toxicology, 2024)

Morphological Differences and Contour Visualization of Statoliths in Different Geographic Populations of Purpleback Flying Squid (Sthenoteuthis oualaniensis) - Moxian Chu; Bilin Liu; Liguo Ou; Ziyue Chen; Qingying Li (Journal of Marine Science and Engineering, 2024)
Statoliths are important hard tissues in cephalopods. Significant differences are found in the external morphology of statoliths in different groups or species. In this study, stepwise discriminant analysis was used to investigate the external morphological differences in purpleback flying squid statoliths in three different marine regions, comprising the East Indian Ocean (5° S–2° N, 82°–92° E), Central East Pacific Ocean (02°37′ S–0°59′ N, 99°44′ W–114°19′ W), and Northwest Indian Ocean (17°04′ N–17°18′ N, 61°05′ E–61°32′ E). The contours of statoliths were reconstructed visually by using Fourier analysis and the landmark method. The results obtained by stepwise discriminant analysis showed that the accuracy of identification was 84.4% for the traditional measurement method, 82.9% for the Fourier analysis method, and 87.3% for the landmark method. The contour visualization results showed that the purpleback flying squid statoliths were small in the Central East Pacific Ocean, and the curvature of the side region was the most obvious. The radian differentiation of statoliths was most gentle in the East Indian Ocean. In the Northwest Indian Ocean, the rostral region of statoliths was shorter and the dorsal region was smoother. The reconstruction results detected significant differences in the outer morphology of statoliths in different marine regions. The results obtained in this study show that all three methods are effective for identifying populations, but the landmark method is better than the traditional measurement method. The reconstruction of statolith contours using the Fourier transform and landmark methods provides an important scientific basis for conducting taxonomy, according to statolith morphology.

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

Air pollution and risk of sarcopenia: A two-sample Mendelian randomized study - Yuezhan Li; Xuee Ou; Qifeng Ou; Ding Pan (Chemosphere, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Outdoor artificial light at night and incident cardiovascular disease in adults: A national cohort study across China - Xiangming Hu; Le-Bing Wang; Bin Jalaludin; Luke D. Knibbs; Steve Hung Lam Yim; Xiang Qian Lao; Lidia Morawska; Zhiqiang Nie; Yingling Zhou; Li-Wen Hu; Wen-Zhong Huang; Yanqiu Ou; et al. (Science of The Total Environment, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

How does industrial transformative process shape the spatial dynamics of urban development? - Weize Song; Wenqing Yang; Na Wang; Can Wang; Zheng Li; Yifu Ou; Xiaoling Zhang (Land Use Policy, 2024)

Haze weather and mortality in China from 2014 to 2020: Definitions, vulnerability, and effect modification by haze characteristics - Zhou Yang; Jiangmei Liu; Jun Yang; Li Li; Ting Xiao; Maigeng Zhou; Chun-Quan Ou (Journal of Hazardous Materials, 2024)

Asymmetric disturbance and permeabilization of bilayer membranes by 3-nm carbon dots - Wenwen Li; Yurong Ma; Luping Ou; Cheng Xu; Yushuang Wei; Kai Yang; Bing Yuan (Journal of Hazardous Materials, 2024)

Urban agglomerations as an environmental dimension of antibiotics transmission through the “One Health” lens - Fangfang Ding; Ye Li; Tianhao He; Dongni Ou; Ye Huang; Guoyu Yin; Jing Yang; Shixue Wu; Erkai He; Min Liu (Journal of Hazardous Materials, 2024)

Responses of a polycyclic aromatic hydrocarbon-degrading bacterium, Paraburkholderia fungorum JT-M8, to Cd (II) under P-limited oligotrophic conditions - Jinghua Li; Yiwen Ou; Lijuan Wang; Yue Zheng; Weiyun Xu; Jianbiao Peng; Xin Zhang; Zhiguo Cao; Junpei Ye (Journal of Hazardous Materials, 2024)

Intercalation of HKUST-1: A strategy for conferring GOM with accurate size-sieving, self-cleaning, and antibacterial multi-functionalities - Xiao Ke Zheng; Hao Yu; Wen Li Gan; Yi Liang; Xinyi Hu; Tao Tang; Yinfen Cheng; Hao Yao; Jian Zhen Ou (Desalination, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Membrane lipid remodeling and autophagy to cope with phosphorus deficiency in the dinoflagellate Prorocentrum shikokuense - Da-Wei Li; Jin-Zhou Tan; Zhuo-Fan Li; Lin-Jian Ou (Chemosphere, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Psychrobacter species enrichment as potential microplastic degrader and the putative biodegradation mechanism in Shenzhen Bay sediment, China - Danyun Ou; Yue Ni; Weiwen Li; Weiyi He; Lei Wang; Hao Huang; Zhong Pan (Journal of Hazardous Materials, 2024)

Effect of fire and post-fire management on soil microbial communities in a lower subtropical forest ecosystem after a mountain fire - Mengmeng Yang; Xuan Luo; Ying Cai; Brian N. Mwangi; Muhammad Sadiq Khan; Fasih Ullah Haider; Wanxuan Huang; Xianli Cheng; Zefan Yang; Hongen Zhou; Shizhong Liu; Qianmei Zhang; et al. (Journal of Environmental Management, 2024)

Coal structure identification based on geophysical logging data: Insights from Wavelet Transform (WT) and Particle Swarm Optimization Support Vector Machine (PSO-SVM) algorithms - Zhongzheng Tong; Yanjun Meng; Jinchuan Zhang; Yaning Wu; Zhen Li; Dongsheng Wang; Xingqi Li; Guangxi Ou (International Journal of Coal Geology, 2024)

Enhancement of coal tar pitch carbonization with biochar: A metallurgical formed biocoke product produced by waste coke breeze and bamboo powder - Lin Wang; Yongbin Yang; Yang Ou; Yinrui Dong; Qiang Zhong; Yan Zhang; Qian Li; Zhucheng Huang; Tao Jiang (Fuel, 2024)

Characteristic volatiles of Fu brick tea formed primarily by extracellular enzymes during Aspergillus cristatus fermentation - Zhong Wang; Qifang Jin; Ronggang Jiang; Yang Liu; He Xie; Xingchang Ou; Qin Li; Zhonghua Liu; Jian'an Huang (Food Research International, 2024)

New insights into endocrine reproductive toxicity of Microcystis aeruginosa combined with ammonia exposure in zebrafish - Kang Ou-Yang; Qian Zhang; Liangmou Wang; Hui Yang; Ya He; Dapeng Li; Li Li (Environmental Pollution, 2024)

Flexural buckling of press-braked stainless steel Z-section columns: Testing, numerical modelling and design - Shuai Li; Ou Zhao (Engineering Structures, 2024)

Elastomers with ultrahigh mechanical properties for flexible sensing and triboelectric nanogenerators - Zhichao Zhang; Wenhao Cao; Muqun Wang; Liang Tuo; Ting Xie; Fangyan Ou; Xueying Duan; Riyao Cong; Chuang Ning; Wenyu Pan; Shuangliang Zhao; Zequan Li; et al. (Chemical Engineering Journal, 2024)

Unravelling molecular fractionation of dissolved organic matter on ferrihydrite-phosphate complexes - Yanan Ou; Jialin Chi; Fangbai Li; Qing Chen; Liping Fang (Chemical Geology, 2024)

Predicting survival time for cold exposure by thermoregulation modeling - Jinping Zhao; Yan Wang; Dengsong Ou; Hanqing Wang; Yuguo Li; Qihong Deng (Building and Environment, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Matching root water uptake patterns to fine root and soil water distributions - Wei Zhu; Dehai Zhao; Nan Di; Doudou Li; Ou Zhou; Yiming Sun; Liming Jia; Changjun Ding; Benye Xi (Plant and Soil, 2024)

miRNA-146a-5p Inhibits Hypoxia-Induced Myocardial Fibrosis Through EndMT - Yan Wang; Jie Yu; Chunxia Ou; Yue Zhao; Lixing Chen; Wenke Cai; Huawei Wang; Shiying Huang; Jie Hu; Guihu Sun; Longjun Li (Cardiovascular Toxicology, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Cooperative roles of phosphate and dissolved organic matter in inhibiting ferrihydrite transformation and their distinct fates - Jialin Chi; Yanan Ou; Fangbai Li; Wenjun Zhang; Hang Zhai; Tongxu Liu; Qing Chen; Xiaoxia Zhou; Liping Fang (Science of The Total Environment, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

MePOD12 participates the regulation to postharvest physiological deterioration by ROS scavenging and lignin accumulation in cassava tuberous roots - Feifei An; Jingjing Xue; Xiuqin Luo; Ting Chen; Zhuowen Wei; Wenli Zhu; Wenjun Ou; Kaimian Li; Jie Cai; Songbi Chen (Postharvest Biology and Technology, 2024)

DNA hypomethylation-associated transcriptional rewiring enables resistance to heavy metal mercury (Hg) stress in rice - Weixuan Cong; Ning Li; Yiling Miao; Yuxi Huang; Wenhao Zhao; Ying Kang; Bingqi Zhang; Jinbin Wang; Jiayu Zhang; Yinhe Lv; Jiamo Li; Jian Zhang; et al. (Journal of Hazardous Materials, 2024)

Multi-omics analysis reveals the toxic mechanism of ammonia-enhanced Microcystis aeruginosa exposure causing liver fat deposition and muscle nutrient loss in zebrafish - Kang Ou-Yang; Yu Kuang; Hui Yang; Ya He; Liangmou Wang; Xinyu Wang; Dapeng Li; Li Li (Journal of Hazardous Materials, 2024)

Phase transformation of Cr(VI) host-mineral driven by citric acid-aided mechanochemical approach for advanced remediation of chromium ore processing residue-contaminated soil - Qi Li; Xiaoming Zhang; Junhao Zheng; Jingxi Qin; Chunyu Ou; Qi Liao; Mengying Si; Zhihui Yang; Weichun Yang (Journal of Hazardous Materials, 2024)

Large-scale offshore wind energy integration by wind-thermal bundled power system: A case study of Yangxi, China - Runzhao Li; Xiaoming Jin; Ping Yang; Yimin Feng; Yun Liu; Shichao Wang; Xiaoliang Ou; Pengxiao Zeng; Yaoneng Li (Journal of Cleaner Production, 2024)

Synergistic conversion of iron ore sintering dust and waste biochar to produce direct reduction iron and syngas: Gasification, reduction behavior and thermodynamic analysis - Lin Wang; Yongbin Yang; Yang Ou; Peiyao Tang; Chen Liu; Qiang Zhong; Yan Zhang; Lingyun Yi; Qian Li; Zhucheng Huang; Tao Jiang (Journal of Cleaner Production, 2024)

Improvement of inverse dispersion technique for ground roll attenuation in sedimentary environment - Ziqi Jin; Guofa Li; Guoxiu Ou (Journal of Applied Geophysics, 2024)

Effect of ferric ions on Cronobacter sakazakii growth, biofilm formation, and swarming motility - Yang Wang; Na Ling; Yaping Wang; Dexin Ou; Zhao Liang; Guoqing Li; Hongyuan Zhao; Yingwang Ye (International Journal of Food Microbiology, 2024)

The potential mechanism of concentrated mannan-oligosaccharide promoting goldfish’s (Carassius auratus Linnaeus) resistance to Ichthyophthirius multifiliis invasion - Senyue Liu; Ming Xu; Baipeng Chen; Fulong Li; Yongqiang Deng; Yufan Zhang; Gang Lin; Defang Chen; Yi Geng; Yangping Ou; Xiaoli Huang (Fish & Shellfish Immunology, 2024)

Hydrophilic porous boronate imprinted hydrogels for ultrafast transport and highly specific separation of flavoniods: A interfacial cooperative emulsion imprinted strategy based on microreactors - Shucheng Liu; Nana Tang; Xuan Zhang; Hao Huang; Jinyu Li; Hongxiang Ou (Chemical Engineering Journal, 2024)

A study on the effectiveness of sodium selenite in treating cadmium and perfluoro octane sulfonic (PFOS) poisoned zebrafish (Danio rerio) - Wang Lu; Waqas Ahmed; Mohsin Mahmood; Ou Wenjie; Li Jiannan; Wang Yunting; Yang Jie; Xu Wenxin; Fu Xiuxian; Hongwei Zhao; Wenjie Liu; Weidong Li; et al. (Biological Trace Element Research, 2024)

LncRNA SPRY4-IT1 regulates 16HBE cell malignant transformation induced by particulate matter through DUSP6-ERK1/2-Chk1 signaling pathway - Yanli Li; Dan Tang; Jian Zhang; Wanting Ou; Xuan Sun; Qiaoyuan Yang; Jianjun Wu (Chemosphere, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Optimization and purification of bioproducts from Bacillus velezensis PhCL fermentation and their potential on industrial application and bioremediation - Chonlong Chio; Sarita Shrestha; Griffin Carr; Janak Raj Khatiwada; Yuen Zhu; Ou Li; Xuantong Chen; Jing Hu; Wensheng Qin (Science of The Total Environment, 2023)

Global, regional, and national burden of asbestosis from 1990 to 2019 and the implications for prevention and control - Zejin Ou; Xin Li; Jiaxin Cui; Shaofang Zhu; Kexin Feng; Jialao Ma; Kangyong Wu; Yuquan Chen; Yiwei Su; Shihao Tang; Danping Duan; Yixian Ren; et al. (Science of The Total Environment, 2023)

Two new eudesmane sesquiterpenoids with neuroprotective activity from Pogostemon cablin - Qi Zheng; Chuan Ma; Liang Xiong; Cheng Peng; Li Guo; Da-Le Guo; E Zhao; Qin-Mei Zhou; Ou Dai (Phytochemistry Letters, 2023)

Synergistic recycling of biochar from sawdust pyrolysis and waste coke breeze to produce metallurgical quality biocoke with syngas as a by-product - Lin Wang; Yongbin Yang; Yang Ou; Qiang Zhong; Peiyao Tang; Yan Zhang; Lingyun Yi; Qian Li; Zhucheng Huang; Tao Jiang (Fuel, 2023)

Deciphering the probiotic properties and safety assessment of a novel multi-stress-tolerant aromatic yeast Pichia kudriavzevii HJ2 from marine mangroves - Yanmei Li; Xueyan Mo; Jianwen Xiong; Kunmei Huang; Minglei Zheng; Qiong Jiang; Guijiao Su; Qian Ou; Hongping Pan; Chengjian Jiang (Food Bioscience, 2023)

ZnO nanoparticles mediated by Azadirachta indica as nano fertilizer: Improvement in physiological and biochemical indices of Zea mays grown in Cr-contaminated soil - Sajid Mehmood; Wenjie Ou; Waqas Ahmed; Jochen Bundschuh; Muhammad Rizwan; Mohsin Mahmood; Haider Sultan; Juha M. Alatalo; Ahmed S.M. Elnahal; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

A real-time spatial deformation estimation method based on spatial curvature decomposition and interpolation - Yonghui An; Jiesheng Chen; Huihui Li; Jinping Ou (Engineering Structures, 2023)

Regional Modeling of the Lithospheric Magnetic Field from Local and Satellite Constraints: A Case Study of the Xinjiang Region - Yan Feng; Jiaxuan Zhang; Shengqing Xiong; JinYuan Zhang; Jiaming Ou; Shuang Liu; Yijun Li; Ya Huang (Pure and Applied Geophysics, 2023)

Production of all-male non-transgenic zebrafish by conditional primordial germ cell ablation - Fang Wang; Yong-Yong Feng; Xu-Guang Wang; Mi Ou; Xin-Cheng Zhang; Jian Zhao; Kun-Ci Chen; Kai-Bin Li (Fish Physiology and Biochemistry, 2023)

The sound and surprise: overlapping meta-analyses on the topic of safety and efficacy of PD-1 and PD-L1 inhibitors in the treatment of non-small cell lung cancer - Shun-Long Ou; Jing Luo; Song Wang; Kai-Yue Li; Su-Ya Du; Qian Jiang (European Journal of Clinical Pharmacology, 2023)

Propofol modulates neural dynamics of thalamo-cortical system associated with anesthetic levels in rats - Xuliang Jiang; Xin Wen; Guoyao Ou; Shitong Li; Yali Chen; Jun Zhang; Zhenhu Liang (Cognitive Neurodynamics, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Deployment priority of public charging speeds for increasing battery electric vehicle usability - Wan Li; Zhenhong Lin; Shiqi(Shawn) Ou; Boyu Wang (Transportation Research Part D: Transport and Environment, 2023)

Natural product osthole can significantly disrupt cell wall integrity and dynamic balance of Fusarium oxysporum - Ke Hu; Rongyu Li; Feixu Mo; Yi Ding; Aiai Zhou; Xue Guo; Ruotong Li; Min Li; Minggui Ou; Ming Li (Pesticide Biochemistry and Physiology, 2023)

Enhancements for stabilizing functional in potential field inversion to recover sparse models with reasonable values and dipping structures - Yang Ou; Qingtian Lü; Jiayong Yan; Dingyu Jia; Yang Li (Journal of Applied Geophysics, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

Characterization of the key odor-active compounds in different aroma types of Fu brick tea using HS-SPME/GC-MSO combined with sensory-directed flavor analysis - Xuexue Zheng; Tengfei Hu; He Xie; Xingchang Ou; Jianan Huang; Chao Wang; Zhonghua Liu; Qin Li (Food Chemistry, 2023)

Assessment of microplastic contamination in an eastern Pacific tuna (Katsuwonus pelamis) and evaluation of its health risk implication through molecular docking and metabolomics studies - Lijun Wu; Xiaojie Dai; Jing Xu; Danyun Ou; Lei Wang; Hui Lin; Weiyi He; Haitao Lin; Rupeng Du; Hao Huang; Weiwen Li; Zhong Pan (Food Chemistry, 2023)

Integrated metabolomic and transcriptomic responses to heat stress in a high-altitude fish, Triplophysa siluroides - Yeyu Chen; Xiaoyun Wu; Pengcheng Li; Ya Liu; Mingjiang Song; Feiyang Li; Jun Ou; Jiansheng Lai (Fish & Shellfish Immunology, 2023)

Performance degradation by column foot damage: From column foot joints to frames - Ya-Jie Wu; Chen Liu; Qi-Fang Xie; Li-Peng Zhang; Tian-Wei Zhang; Jia-Jia Ou (Engineering Structures, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Heteropoly acid supported on hierarchical Y zeolite decorated SiC foam as the structured catalytic packing for reactive distillation synthesis of ethyl lactate - Qiuyan Ding; Hengyu Shen; Zongliang Kou; Hong Li; Xiaolei Fan; Xiaoxia Ou; Yilai Jiao; Xin Gao (Chemical Engineering Journal, 2023)

Plant-inspired modification strategy for the large-scale, versatile preparation of cellulose-based products with highly effective and durable UV-protective, antimicrobial, and antiviral performance - Songnan Hu; Yuehu Li; Fang Peng; Jinfen Ou; Lei Guo; Yian Chen; Yun Li; Fengxia Yue; Haisong Qi (Chemical Engineering Journal, 2023)

Electrochemical oxidation treatment of reverse osmosis concentrated landfill leachate: Effect of operation parameters and evolution of dissolved organic matter - Ye-Chao Tian; Wen-Xiang Ji; Yu-Ze Han; Ze-Tao Wu; Hai-Ou Song; Ai-Min Li; Wen-Tao Li (Chemical Engineering Journal, 2023)

Dextran-based micelles for combinational chemo-photodynamic therapy of tumors via in vivo chemiluminescence - Chendi Ding; Zhaoqing Shi; Meitong Ou; Yingbang Li; Li Huang; Wenyan Wang; Qili Huang; Meihang Li; Chunbo Chen; Xiaowei Zeng; Hongzhong Chen; Lin Mei (Carbohydrate Polymers, 2023)

Isolation and characterization of 73 SNP markers in Schizopygopsis chengi baoxingensis - Mingjiang Song; Yeyu Chen; Xiaoyun Wu; Ya Liu; Feiyang Li; Quan Gong; Jun Ou; Pengcheng Li; Qiaolin Zou; Jiansheng Lai (Conservation Genetics Resources, 2023)

The various effect of cow manure compost on the degradation of imazethapyr in different soil types - Lei Cheng; Lixia Wang; Xinhong Wang; Yang Ou; Huiping Liu; Xia Hou; Liming Yan; Xinyi Li (Chemosphere, 2023)

Leveraging opportunity of low carbon transition by super-emitter cities in China - Heran Zheng; Zengkai Zhang; Erik Dietzenbacher; Ya Zhou; Johannes Többen; Kuishuang Feng; Daniel Moran; Meng Jiang; Yuli Shan; Daoping Wang; Xiaoyu Liu; Li Li; et al. (Science Bulletin, 2023)

Simultaneous oxidization-adsorption for arsenic and antimony by biological Fe-Mn binary oxides (BFMO): The efficiencies and mechanism - Mengying Si; Wei Cao; Chunyu Ou; Guangyuan Tu; Weichun Yang; Qingzhu Li; Qi Liao; Zhihui Yang (Process Safety and Environmental Protection, 2023)

A biomimetic design for efficient petrochemical spill disposal: CoFe-PBA modified superhydrophobic melamine sponge with mechanical/chemical durability and low fire risk - Haocun Guan; Rongjia Li; Richeng Lian; Jiahui Cui; Mingyu Ou; Lei Liu; Xilei Chen; Chuanmei Jiao; Shaoping Kuang (Journal of Hazardous Materials, 2023)

Enhancing degradation of norfloxacin using chrysanthemum-shaped bimetallic NH2-MIL-53(Fe/Ti) photocatalysts under visible light irradiation - Wen Gao; Fangyuan Wang; Meilin Ou; Qianqian Wu; Lei Wang; Haonan Zhu; Yuanyuan Li; Ning Kong; Jianping Qiu; Shanshan Hu; Shuang Song (Journal of Environmental Chemical Engineering, 2023)

A review of struvite crystallization for nutrient source recovery from wastewater - Qian Guan; Yingpeng Li; Yun Zhong; Wei Liu; Jiajie Zhang; Xin Yu; Ranwen Ou; Guisheng Zeng (Journal of Environmental Management, 2023)

Iron nanoparticles decorated TiO2 hollow microspheres for boosting degradation of tetracycline in a photo-Fenton catalytic system - Hongling Dai; Zhaochen Liu; Li Ou; Yue Shen; Zhihui Ning; Fengping Hu; Xiaoming Peng (Journal of Environmental Chemical Engineering, 2023)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

A paternal protein facilitates sperm RNA delivery to regulate zygotic development - Dongdong Li; Shijing Huang; Yongping Chai; Ruiqian Zhao; Jing Gong; Qiangfeng Cliff Zhang; Guangshuo Ou; Wenyu Wen (Science China Life Sciences, 2023)

A novel approach using multispectral imaging for rapid development of seed pellet formulations to mitigate drought stress in alfalfa - Zhicheng Jia; Chengming Ou; Shoujiang Sun; Juan Wang; Jingyu Liu; Manli Li; Shangang Jia; Peisheng Mao (Computers and Electronics in Agriculture, 2023)

Chemistry of formation and elimination of formaldehyde in foods - Yixin Li; Juanying Ou; Caihuan Huang; Fu Liu; Shiyi Ou; Jie Zheng (Trends in Food Science & Technology, 2023)

Regularity of rural settlement changes driven by rapid urbanization in North China over the three decades - Yansui Liu; Cong Ou; Yurui Li; Liqiang Zhang; Jianhua He (Science Bulletin, 2023)

Reversed tension characteristics in subsea mooring connectors for an FPSO SPM in shallow water - Peng Li; Gang Ma; Dongsheng Qiao; Hang Luo; Hongtao Li; Jinping Ou (Ocean Engineering, 2023)

Upcycling waste phosphogypsum as an alternative filler for asphalt pavement - Li Ou; Rui Li; Hongzhou Zhu; Hongduo Zhao; Ruipu Chen (Journal of Cleaner Production, 2023)

A clean and efficient innovative technology for refractory sulfide gold ore: In situ gold extraction via self-generated thiosulfate - Yang Ou; Yongbin Yang; Lin Wang; Ke Li; Wei Gao; Yan Zhang; Qian Li; Tao Jiang (Journal of Cleaner Production, 2023)

A harsh environment resistant robust Co(OH)2@stearic acid nanocellulose-based membrane for oil-water separation and wastewater purification - Zuozhu Yin; Min Li; Zihao Li; Yuanting Deng; Mingshan Xue; Yuhua Chen; Junfei Ou; Sheng Lei; Yidan Luo; Chan Xie (Journal of Environmental Management, 2023)

N-acyl homoserine lactone mediating initial adhesion of microalgal biofilm formation - Zixuan Ou; Xindi Chen; Xinming Wu; Changren Zhou; Kaijie Zhang; Jingyang Luo; Fang Fang; Yinqiang Sun; Ming Li; Qian Feng (Environmental Research, 2023)

Flexural buckling behaviour and residual resistances of hot-rolled stainless steel channel section columns after exposure to elevated temperatures - Shuai Li; Yating Liang; Ou Zhao (Engineering Structures, 2023)

Characteristics and control strategies of indoor particles: An updated review - Jing Li; Guangtao Fan; Yinping Ou; Qihong Deng (Energy and Buildings, 2023)

Ultra-high output hybrid nanogenerator for self-powered smart mariculture monitoring and warning system - Liqiang Liu; Jun Li; Zhengxin Guan; Leilei Zhao; Zhiyu Tian; Shouchuang Jia; Hongxin Hong; Zeyu He; Haiyang Wen; Ruiyuan Huang; Hui Cui; Wei Ou-Yang; et al. (Chemical Engineering Journal, 2023)

Corrigendum to “An NIR-II light responsive antibacterial gelation for repetitious photothermal/thermodynamic synergistic therapy” [Chem. Eng. J. 407 (2021) 127200] - Qinzhe Li; Yewei Zhang; Xuan Huang; Dongliang Yang; Lixing Weng; Changjin Ou; Xuejiao Song; Xiaochen Dong (Chemical Engineering Journal, 2023)

Study on the failure characteristics of overburden and the evolution law of seepage field in deep buried thick coal seam under aquifers - Yang Li; Xinghai Lei; Nan Wang; Yuqi Ren; Xiangyang Jin; Guoshuai Li; Tiezheng Li; Xiangji Ou (Natural Hazards, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Circ-SFMBT2 sponges miR-224-5p to induce ketamine-induced cystitis by up-regulating metadherin (MTDH) - Fanchang Zeng; Qinghui Wu; Mi Song; Xinli Kang; Zhewen Ou; Zuobing Yang; Liumei Luo; Daoyuan Li (Human Cell, 2023)

Synthesis and characterization of an artificial glucosinolate bearing a chlorthalonil-based aglycon as a potent inhibitor of glucosinolate transporters - Yingjie Wen; Xunyuan Jiang; Dehong Li; Ziyue Ou; Ye Yu; Ronghua Chen; Changming Chen; Hanhong Xu (Phytochemistry, 2023)

The wall-associated kinase gene family in pea (Pisum sativum) and its function in response to B deficiency and Al toxicity - Xuewen Li; Meiyin Ou; Li Li; Yalin Li; Yingming Feng; Xin Huang; František Baluška; Sergey Shabala; Min Yu; Weiming Shi; Feihua Wu (Journal of Plant Physiology, 2023)

Preparation and performance of porous ceramsite for Ag+ removal in sewage treatment with total phosphorus tailings - Nanyan Hu; Yafei Lv; Binyu Luo; Yicheng Ye; Fanghui Fu; Jinpeng Jia; Zhibing Ou; Jiangli Li (Journal of Cleaner Production, 2023)

Preparation of formed coke product as a coke substitute using a solid waste fuel: Trimethylbenzene improvement on coal tar pitch - Lin Wang; Yongbin Yang; Yang Ou; Peiyao Tang; Chen Liu; Xiaoxuan Zhang; Qiang Zhong; Qian Li; Tao Jiang (Fuel, 2023)

Collaborative interfacial modification and surficial passivation for high-efficiency MA-free wide-bandgap perovskite solar cells - Yali Ou; Hao Huang; Hongxi Shi; Ziyu Li; Zhijia Chen; Muhammad Mateen; Zhangbo Lu; Dan Chi; Shihua Huang (Chemical Engineering Journal, 2023)

Locating and characterizing potential rainfall-induced landslides on a regional scale based on SBAS-InSAR technique - Jinhui Li; Xinfu Xing; Jinping Ou (Bulletin of Engineering Geology and the Environment, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Inapparent decrease in phytoplankton biomass accompanied by significant size composition succession in the shellfish aquaculture farm in the western Taiwan strait - Yu Mo; Aifeng Li; Zhaohe Luo; Cun Jia; Rimei Ou; Jinli Qiu; Xinyu Chang; Hao Huang; Lei Wang (Frontiers in Marine Science, 2023)
We conducted an annual monthly sampling in the aquaculture areas of Lianjiang and Zhangpu, Fujian province, in the west coast of the Taiwan Strait, to gain insight into the effects of shellfish aquaculture on total phytoplankton biomass and its distribution in phytoplankton size fractions. We observed that the total chlorophyll-a (TChl-a) concentration was higher in Zhangpu (annual mean 2.690 ± 2.375 μg/L) than in Lianjiang (annual mean 1.700 ± 1.500 μg/L) and that Lianjiang had a high N/P ratio during the study, which may have been the main reason for the differences in phytoplankton biomass between the two shellfish aquaculture areas. The response of phytoplankton to shellfish aquaculture was different in the northern versus southern areas. During the aquaculture period of Lianjiang, the TChl-a concentration of surface water was approximately 14% lower than that of bottom water, and such a decreasing trend of Chl-a concentration was consistently present in micro-, nano-, and pico-size fractions. Phytoplankton depletion was not observed during investigation in Zhangpu, which showed highly variable in environmental factors. The contribution of pico-sized Chl-a to TChl-a is evaluated by shellfish aquaculture to some extent in Lianjiang. The shift from the dominance of nano-phytoplankton to the dominance of micro- phytoplankton and pico-phytoplankton was caused mainly by seasonal variation in environmental conditions. In complex marine environments, the distribution of phytoplankton biomass in phytoplankton size fractions showed no significant response to shellfish aquaculture.

Evaluating the ecological vulnerability of Chongqing using deep learning - Jun-Yi Wu; Hong Liu; Tong Li; Yuan Ou-Yang; Jing-Hua Zhang; Teng-Jiao Zhang; Yong Huang; Wen-Long Gao; Lu Shao (Environmental Science and Pollution Research, 2023)

Surface modification of cellulose nanocrystals by physically adsorbing lactoferrin as pickering stabilizers: Emulsion stabilization and in vitro lipid digestion - Xueying Li; Penghui Sun; Liang Fu; Jie Zheng; Shiyi Ou; Caihuan Huang; Juanying Ou; Hua Zhou; Danyue Zhao; Tao Yang; Fu Liu (Food Structure, 2023)

Chemical characterization and source attribution of organic pollutants in industrial wastewaters from a Chinese chemical industrial park - Yihua Huang; Yinong You; Manman Wu; Min Han; Jin Zhang; Wei Gao; Danping Xie; Hongzhan Chen; Hui Ou; Ninghui Song; Chunlei Cheng; Wen Zhuang; et al. (Environmental Research, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

A Study on Measuring the Wind Field in the Air Using a Multi-rotor UAV Mounted with an Anemometer - Zhengnong Li; Ou Pu; Yueyue Pan; Bin Huang; Zhefei Zhao; Honghua Wu (Boundary-Layer Meteorology, 2023)

How can tourism help to revitalize the countryside? Content analysis based on the case of tourism enabling rural revitalization - Chenxi Li; Yingying Fang; Yizhong Wang; Yue Xu; Zhihong Zong; Yi Yang; Chennian Wang; Zhuoping Ou; Min Wang (Environment, Development and Sustainability, 2023)

A refined recycled carbonatite model for the δ13C negative anomaly in the upper Doushantuo Formation - Pengfei Xi; Yongsheng Liu; Junhua Li; Wei Chen; Detao He; Xiaobin Ou; Wenxia Wei; Ao Yang (Precambrian Research, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Self-enhanced ROS generation by responsive co-delivery of H2O2 and O2 based on a versatile composite biomaterial for hypoxia-irrelevant multimodal antibiofilm therapy - Jiayu Xiao; Luo Hai; Ke Yang; Yuze Luo; Zefeng Wang; Junqin Li; Chunlei Ou; Li Wang; Le Deng; Dinggeng He (Chemical Engineering Journal, 2023)

Comparative study on effects of pozzolanic nano-SiO2 and non-pozzolanic nano-TiO2 on the microstructure and macro properties of cement paste subjected to early-age frost attack - Shuai Bai; Lingbo Yu; Xinchun Guan; Hui Li; Jinping Ou (Cold Regions Science and Technology, 2023)

Study on the Bottom-Hole Rock-Breaking Law of Electrohydraulic Shockwave - Kerou Liu; Hui Zhang; Jun Li; Kuangsheng Zhang; Yangyong Ou; Yufei Chen; Xinrui Wang; Zhixiang Cai (Rock Mechanics and Rock Engineering, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Towards Ensemble-Based Kilometer-Scale Climate Simulations over the Third Pole Region - Andreas F. Prein; Nikolina Ban; Tinghai Ou; Jianping Tang; Koichi Sakaguchi; Emily Collier; Sanjay Jayanarayanan; Lu Li; Stefan Sobolowski; Xingchao Chen; Xu Zhou; Hui-Wen Lai; et al. (Climate Dynamics, 2023)

Early Cambrian microfossils from the cherts in carbonates of the Kuruktag area, the Tarim block - Zhi-li Zhang; Zhi-ji Ou; Hui-li Li; Shuang-jian Li; Jiang Wu; Fan-wei Meng (Carbonates and Evaporites, 2023)

Adverse impacts of development on the deltamethrin-exposed host Ephestia elutella (Lepidoptera: Pyralidae) on population parameters of Habrobracon hebetor (Hymenoptera: Braconidae) - Xiu-Qin Wang; Hou-Ding Ou; Hao-Xi Li; Lan Wei; Yao Huang; Mao-Fa Yang (Crop Protection, 2023)

Deleting UL49.5 in duck plague virus causes attachment, entry and spread defects - Chunmei Li; Mingshu Wang; Anchun Cheng; Bin Tian; Juan Huang; Ying Wu; Qiao Yang; Qun Gao; Di Sun; Shaqiu Zhang; Xumin Ou; Sai Mao; et al. (Veterinary Microbiology, 2023)

Enhanced virulence of genetically engineered Autographa californica nucleopolyhedrovirus owing to accelerated viral DNA replication aided by inserted ascovirus genes - Huan Yu; Chang-Jin Yang; Yi-Yi Ou-Yang; Yue Tong; Hui-Yu Lan; Jia-Min Gan; Shi-Wei Li; Ding-Yi Bai; Guo-Hua Huang (Pesticide Biochemistry and Physiology, 2023)

A data-driven model to quantify the impact of river discharge on tide-river dynamics in the Yangtze River estuary - Huayang Cai; Bo Li; Erwan Garel; Haidong Pan; Tongtiegang Zhao; Feng Liu; Yuting Ma; Suying Ou (Journal of Hydrology, 2023)

Characterization of anthocyanin accumulation, nutritional properties, and postharvest attributes of transgenic purple tomato - Wei Jian; Xiaogang Ou; Lixinyu Sun; Yu Chen; Shiyu Liu; Wang Lu; Xian Yang; Zhengwu Zhao; Zhengguo Li (Food Chemistry, 2023)

Distribution and fate of Tibetan Plateau loess - Xiangjun Liu; Xiaodong Miao; Junsheng Nie; Xiaojian Zhang; Yixuan Wang; Xiangzhong Li; Xianjiao Ou; Zhongping Lai (CATENA, 2023)

Novel mutation in LRP5 gene cause rare osteosclerosis: cases studies and literature review - Dichen Zhao; Lei Sun; Wenbin Zheng; Jing Hu; Bingna Zhou; Ou Wang; Yan Jiang; Weibo Xia; Xiaoping Xing; Mei Li (Molecular Genetics and Genomics, 2023)
To study the effects of low-density lipoprotein receptor-related protein 5 ( LRP5 ) gene mutations on bone, and to open up our view of LRP5 and Wnt pathways on bone mass regulation. Three patients with increased bone mineral density or thickened bone cortex were included, who were 30-year-old, 22-year-old and 50-year-old men, respectively. The latter two patients were son and father of a same family. The characteristics of bone X-rays were evaluated in detail. Bone turnover markers were detected, such as procollagen type 1 amino-terminal peptide (P1NP), alkaline phosphatase (ALP), and type 1 collagen carboxyl terminal peptide (β-CTX). Dual energy X-ray absorptiometry (DXA) was used to measure the bone mineral density (BMD) at lumbar spine and proximal femur of the patients. The targeted next-generation sequencing (NGS) technology was used to detect pathogenic gene mutations, which were further verified by Sanger sequencing. Moreover, the gene mutation spectrum and phenotypic characteristics of reported patients with LRP5 gain-of-function mutations were summarized by reviewing the literature. The main characteristics of the first patient were headache, facial paralysis, high BMD (lumbar vertebrae 1–4: 1.877 g/cm 2 , Z-score: 5.8; total hip: 1.705 g/cm 2 , Z-score: 5.7), slightly increased P1NP (87.0 ng/mL) and β-CTX (0.761 ng/mL) level, and with thickened bone cortex, especially the cranial vault. The latter two patients showed enlargement of the mandible and enlarged osseous prominence of the tours palatinus. X-rays showed that the bone cortex of skull and long bones were thickened. The bone turnover markers and BMD were normal. All three cases carried novel missense mutations in LRP5 gene, which were mutation in exon 3 (c.586 T > G, p.Trp196Gly) of the first patient, and mutation in exon 20 (c.4240C > A, p.Arg1414Ser) of the latter two patients. Combined with the reported literature, a total of 19 gain-of-function mutations in LRP5 were detected in 113 patients from 33 families. Hotspot mutations included c.724G > A, c.512G > T and c.758C > T. Furthermore, mutations in the exon 3 of LRP5 may cause severe phenotypes. LRP5 gain-of-function mutations can lead to rare autosomal dominant osteosclerosis type Ι (ADO Ι), which was characterized by increased bone mass and thickened bone cortex. In-depth research on the Wnt pathway will be benefit for discovering important mechanisms of bone mass regulation.

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Simulation analysis of passengers’ rescheduling strategies in metro station under COVID-19 - Ying Lu; Dexin Ou; Zhipeng Zhou; Hongyang Li; Yongliang Deng; Yunxuan Deng; Ziyao Zhang (Tunnelling and Underground Space Technology, 2023)

Sluggish lithium isotopic response of continental intraplate basalts to recycled sedimentary carbonate - Yang-Yang Wang; Cheng-Long Yu; Dong-Bo Tan; He Sun; Hai-Ou Gu; Fengtai Tong; Li-Hui Chen; Yilin Xiao (Lithos, 2023)

Effectiveness and mechanism of nano iron oxides modified halloysite nanotubes for uranium sequestration - Minhua Su; Tao Ou; Jiayi Li; Lizhi Tong; Weixing Han; Yuhua Wu; Diyun Chen (Journal of Environmental Chemical Engineering, 2023)

Structural behaviour of press-braked austenitic stainless steel slender channel section beam-columns - Shuai Li; Andi Su; Ou Zhao (Engineering Structures, 2023)

Green photocatalytic syntheses using water as solvent/hydrogen source/oxygen source - Wen-Tao Ouyang; Fang Xiao; Li-Juan Ou; Wei-Min He (Current Opinion in Green and Sustainable Chemistry, 2023)

Study on the air distribution characteristics of equipartition-ring column attachment ventilation mode - Tianqi Wang; Ou Han; Angui Li; Haiguo Yin; Jiaxing Li; Yuanqing Ma; Yicun Hou (Building and Environment, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

Complete genome of Sphingomonas paucimobilis ZJSH1, an endophytic bacterium from Dendrobium officinale with stress resistance and growth promotion potential - Jin Li; Hangtao Wu; Qian Pu; Chu Zhang; Ying Chen; Zhengxin Lin; Xiufang Hu; Ou Li (Archives of Microbiology, 2023)

Organic–inorganic composite modifiers enhance restoration potential of Nerium oleander L. to lead–zinc tailing: application of phytoremediation - Rongkui Su; Qiqi Ou; Hanqing Wang; Xiangrong Dai; Yonghua Chen; Yiting Luo; Haisong Yao; Danxia Ouyang; Zishi Li; Zhixiang Wang (Environmental Science and Pollution Research, 2023)

Deep reinforcement learning method for satellite range scheduling problem - Junwei Ou; Lining Xing; Feng Yao; Mengjun Li; Jimin Lv; Yongming He; Yanjie Song; Jian Wu; Guoting Zhang (Swarm and Evolutionary Computation, 2023)

Cyhalofop-butyl and pyribenzoxim-induced oxidative stress and transcriptome changes in the muscle of crayfish (Procambarus clarkii) - Kang Ou-Yang; Tangqi Feng; Yifang Han; Jianhong Li; Hongju Ma (Science of The Total Environment, 2023)

Molecular mechanism of anti-inflammatory effects of the proteasome inhibitor MG-132 on Con A-induced acute liver injury in mice - Chunlan Shan; Deyuan Ou; Yanling Xiong; Hongsong Cheng; Chun Song; Mei Li; Tian Fang; Zhentao Cheng; Fujun Miao (Research in Veterinary Science, 2023)

Late Ordovician microphytoplankton in Southwest China: recording paleogeographic variations across the Hirnantian glaciation - Lei-Ming Yin; Tenger Borjigin; Zhi-Ji Ou; Li-Zeng Bian (Palaeoworld, 2023)

SecReT6 update: a comprehensive resource of bacterial Type VI Secretion Systems - Jianfeng Zhang; Jiahao Guan; Meng Wang; Gang Li; Marko Djordjevic; Cui Tai; Hui Wang; Zixin Deng; Zhaoyan Chen; Hong-Yu Ou (Science China Life Sciences, 2023)

Transcriptome- and metabolome-based candidate mechanism of BCR-ABL-independent resistance to olverembatinib in Philadelphia chromosome–positive acute lymphoblastic leukemia - Zhao Yin; Meiyan Liao; Rongrong Yan; Guangchao Li; Ruiming Ou; Zhi Liu; Qi Zhong; Huijuan Shen; Yangmin Zhu; Shuangfeng Xie; Qing Zhang; Shuang Liu; et al. (Functional & Integrative Genomics, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Gene Expression and Epigenetic Modification of Aromatase during Sex Reversal and Gonadal Development in Blotched Snakehead (Channa maculata) - Sujing Huang; Yuxia Wu; Kunci Chen; Xiaotian Zhang; Jian Zhao; Qing Luo; Haiyang Liu; Fang Wang; Kaibin Li; Shuzhan Fei; Xincheng Zhang; Mi Ou (Fishes, 2023)
The cyp19a1 gene codes aromatase that converts androgen to estrogen, which plays a central role in early female differentiation and ovarian development in teleosts. For the blotched snakehead (Channa maculata), an important aquaculture fish that is susceptible to hormone-induced sex reversal, two aromatase genes were characterized in the present study, cyp19a1a and cyp19a1b. We analyzed gene expression and the epigenetic state of cyp19a1a and cyp19a1b in different adult tissues: the gonad and brain from normal XX females (XX-F), normal XY males (XY-M), sex-reversal females (XY-F) induced by estrogen, and YY super-males (YY-M), and gonads at different development stages. Cyp19a1a exhibited strong female-biased expression patterns in the ovary, and cyp19a1b dominantly expressed in the brain with no sex bias. Cyp19a1a’s expression pattern in the XY-F ovary was similar to that in the XX-F ovary, with a relatively high expression level, which was far higher than that in XY-M and YY-M testis. Meanwhile, CpG methylation levels of cyp19a1a promoter were lower in XX-F and XY-F ovaries compared with XY-M and YY-M testis. A significantly negative correlation between the CpG methylation levels and cyp19a1a expression was elucidated in XX-F, XY-M, XY-F, and YY-M gonads. Furthermore, the strong female-biased cyp19a1a expression was closely related to ovarian differentiation and maturation, and the overall methylation levels of cyp19a1a promoter were inversely correlated with cyp19a1a expression. There were no detectable sexually dimorphic differences in cyp19a1b expression and CpG methylation levels of cyp19a1b promoter in the brain and gonad between sexes in C. maculata, thus the function of cyp19a1b in C. maculata needs further research. Our research illustrates that cyp19a1a is closely related to estrogen production, ovary differentiation/maintenance, and sex reversal, and epigenetic modification plays a crucial part in maintaining the sexual dimorphic expression of cyp19a1a, ovarian differentiation and oogenesis in C. maculata.

Preparation of reed-based hydrothermal carbonized carbon photocatalyst and effective degradation of methylene blue and tetracycline - Hao Xu; Yangyuan Ou; Xinjiang Hu; Daihui Chen; Xingong Li; Chunfang Tang; Xia Zheng (Environmental Science and Pollution Research, 2023)

Abatement of binary gaseous chlorinated VOC by biotrickling filter: Performance, interactions, and microbial community - Qian Li; Zeqin Tang; Dujuan Ou Yang; Jiahui Zhang; Jianmeng Chen; Dongzhi Chen (Chemosphere, 2023)

Sex-specific markers developed by 2b-RAD and genome sequencing reveal an XX/XY sex-determination system in mud carp (Cirrhinus molitorella) - Haiyang Liu; Weiwei Xia; Bingjie Li; Lan Liu; Yakun Wang; Qing Luo; Mi Ou; Xinping Zhu; Kunci Chen; Jian Zhao (Aquaculture, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Genome-wide identification of the CsPAL gene family and functional analysis for strengthening green mold resistance in citrus fruit - Linli Wei; Wenjun Wang; Ting Li; Ou Chen; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Eco-friendly and low-energy innovative scheme of self-generated thiosulfate by atmospheric oxidation for green gold extraction - Yang Ou; Yongbin Yang; Ke Li; Wei Gao; Lin Wang; Qian Li; Tao Jiang (Journal of Cleaner Production, 2023)

Hyperspectral imaging combined with chemometrics for rapid detection of talcum powder adulterated in wheat flour - Hong-Ju He; Yan Chen; Guanglei Li; Yuling Wang; Xingqi Ou; Jingli Guo (Food Control, 2023)

Sodium Para-Aminosalicylic Acid Modulates Autophagy to Lessen Lead-Induced Neurodegeneration in Rat Cortex - Lei-lei Wang; Xiao-juan Zhu; Yuan-yuan Fang; Yan Li; Yue-song Zhao; Cui-liu Gan; Jing-jing Luo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Neurotoxicity Research, 2023)

Supply and demand dynamics of hydrologic ecosystem services in the rapidly urbanizing Taihu Lake Basin of China - Yu Tao; Zhaobi Li; Xiao Sun; Jiangxiao Qiu; Steven G. Pueppke; Weixin Ou; Jie Guo; Qin Tao; Fei Wang (Applied Geography, 2023)

Clinical evaluation of efficacy of leflunomide combined with low-dose prednisone for treatment of myasthenia gravis - Xin Huang; Li Qiu; Yaru Lu; Jiaxin Chen; Wenhao Yang; Changyi Ou; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2023)

Sounds of snapping shrimp (Alpheidae) as important input to the soundscape in the southeast China coastal sea - Zhongchang Song; Wenzhan Ou; Yingnan Su; Hongquan Li; Wenxin Fan; Shengyao Sun; Teng Wang; Xiaohui Xu; Yu Zhang (Frontiers in Marine Science, 2023)
As a biological sound source widely distributed in temperate and tropical coastal waters, snapping shrimp produce strong pulses which can serve as honest signals to indicate habitat-specific soundscape. The past decade has witnessed the growing interest in investigating the acoustical activity of snapping shrimp across many shallow waters including the coastal line of the west Pacific Ocean. It was extended to the Southeast China coastal area where snapping sounds and the associated soundscape were recorded at four sites. Customized codes incorporating bandwidth and amplitude threshold operations were developed to detect snaps from the ambient noise to estimate snap rate and extract snaps individually. The subsequent analysis suggested that snaps recorded at different sites were unanimously stronger than background noise. Sound pressure level of the snaps ranged from 150 dB to 190 dB (re 1 μPa). The characteristics of snaps, including sound pressure level, duration, peak frequency, -3dB bandwidth from different sites are examined to evaluate the variability across the sites. Though snapping pulses had peak frequencies and the -3 dB bandwidth consistently below 10 kHz, snaps had considerable energy extending to the high frequency range over 200 kHz. The analysis of the acoustic data received for 7 consecutive days at one site indicated that the snap rate corresponded to tidal level periodicity. A high tide was accompanied with a local high snap rate regardless of light but this local snap rate peak was much higher at night. The mean rate fluctuated between 2000 and 4000 snaps per minute and more snaps were recorded after sunset suggesting that snapping shrimp living in the area snapped in response to light. These data may indicate that snaps are important communication means in light-limited condition and deepen our understanding on the correlation of snapping behavior and ecological environments.

Two new spongian diterpene derivatives from the aquaculture sponge Spongia officinalis Linnaeus, 1759 - Tianyun Jin; Pinglin Li; Cili Wang; Xuli Tang; Xiaoli Yv; Kai Li; Lianzhong Luo; Huilong Ou; Guoqiang Li (Natural Product Research, 2023)

Early identification of strawberry leaves disease utilizing hyperspectral imaging combing with spectral features, multiple vegetation indices and textural features - Gangshan Wu; Yinlong Fang; Qiyou Jiang; Ming Cui; Na Li; Yunmeng Ou; Zhihua Diao; Baohua Zhang (Computers and Electronics in Agriculture, 2023)

Generation of myostatin gene-edited blotched snakehead (Channa maculata) using CRISPR/Cas9 system - Mi Ou; Fang Wang; Kaibin Li; Yuxia Wu; Sujing Huang; Qing Luo; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Kunci Chen; Jian Zhao (Aquaculture, 2023)

Large-scale mariculture of the sponge Haliclona simulans on floating rafts in Zhao'an Bay, Fujian Province, China - Zhunfei Li; Guangyuan Xia; Huilong Ou; Ming Chen; Yingzhe You; Jun Chen (Aquaculture, 2023)

Using habitat classification and large-scale spatial planning model to identify environmental areas: A case study in the area of the Northwest Pacific Ocean - Huang Hao; Cai Lei; Lei Wang; Weiwen Li; Ou Danyun; Wu Lijun; Ou Rimei; Lin Lianghua (Marine Policy, 2023)

Numerical investigation of wave run-up and load on heaving cylinder subjected to regular waves - Xinlong Wang; Dongsheng Qiao; Linxiao Jin; Jun Yan; Bin Wang; Binbin Li; Jinping Ou (Ocean Engineering, 2023)

Effects of stand age and structure on root distribution and root water uptake in fast-growing poplar plantations - Wei Zhu; Ou Zhou; Yiming Sun; Ximeng Li; Nan Di; Doudou Li; Gulimire Yilihamu; Yafei Wang; Jingyi Fu; Benye Xi; Liming Jia (Journal of Hydrology, 2023)

Removal of tetracycline from water by catalytic photodegradation combined with the microalga Scenedesmus obliquus and the responses of algal photosynthesis and transcription - Zhehua Chen; Dong Ou; Gan Gu; Shumei Gao; Xi Li; Changwei Hu; Xianrui Liang; Yuejin Zhang (Journal of Environmental Management, 2023)

Post-fire behaviour and residual resistance of hot-rolled stainless steel channel sections under major-axis combined loading - Shuai Li; Andi Su; Ou Zhao (Engineering Structures, 2023)

Thermoregulatory analysis of warm footbaths before bedtime: Implications for enhancing sleep quality - Jinping Zhao; Faming Wang; Dengsong Ou; Binkan Zhou; Yuguo Li; Hanqing Wang; Qihong Deng (Building and Environment, 2023)

S-ketamine promotes autophagy and alleviates neuropathic pain by inhibiting PI3K/Akt/mTOR signaling pathway - Jia Han; Xianjie Zhang; Leqiang Xia; Ou Liao; Qiulan Li (Molecular & Cellular Toxicology, 2023)

Correction to: Effects of Sub-chronic Lead Exposure on Essential Element Levels in Mice - Shaojun Li; Chun Yang; Xiang Yi; Ruokun Wei; Michael Aschner; Yueming Jiang; Shiyan Ou; Chaocong Yao (Biological Trace Element Research, 2023)

Effects of Sub-chronic Lead Exposure on Essential Element Levels in Mice - Shaojun Li; Chun Yang; Xiang Yi; Ruokun Wei; Michael Aschner; Yueming Jiang; Shiyan Ou; Chaocong Yao (Biological Trace Element Research, 2023)

Effects of Bacillus sp. and Lactobacillus sp. combination as a water additive on the culture pond water and growth performance of hybrid grouper (Epinephelus fuscoguttatus × Epinephelus polyphekadion) - Jianpeng Huang; Eric Amenyogbe; Guanghai Ou; Yu Li; Zhenwei Wen; Xingtao Jiang; Gang Chen (Frontiers in Marine Science, 2022)
The individual Probiotic application has become increasingly widespread in aquaculture and has been extensively studied. However, investigating probiotics as water additives in the grouper culture is still lacking. This study evaluated the functional efficacy of the Bacillus subtilis CICC 10071 (3 × 1011 CFU / g) and Lactobacillus sp. (8 × 1011 CFU / g) combination in a 1:1 ratio on the rearing water quality, water microbial community structure, and growth performance of hybrid grouper. Depending on the additive concentrations of probiotics, we designed four groups, each in triplicate: control (WT, 0g/m3), low concentration (WL, 0.038g/m3), middle concentration (WM, 0.075g/m3), and high concentration (WH, 0.113g/m3). The result shows that throughout the 22-day feeding period, the water supplementation of probiotics significantly decreased Ammonia (NH3) and nitrite (NO2-) in culture water. Final weight (FW), Specific growth rate (SGR), and Weight gain rate (WGR) in treated groups were higher than that in the control group (P<0.05). Analysis of water microbiota revealed that the dominant phylum Bacteroidetes, Proteobacteria, Cyanobacteria, and Actinobacteria enriched in the culture water. Furthermore, we found that the Probiotics combination could significantly reduce the abundance of Cetobacterium (phyla Fusobacteria) related to ammonia and nitrite. The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States 2 (PICRUSt2) also shows that the 'metabolism of other amino acids and ‘Fatty acid biosynthesis’ functions of water microbiota were reinforced by the addition of the probiotic combination. Thus, the probiotic combination exhibited a range of advantages in the grouper culture environment, and further in-depth studies are needed.

Identification of a stable major-effect quantitative trait locus for pre-harvest sprouting in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Zhi Li; Yongyan Chen; Xia Ou; Mengning Wang; Nanxin Wang; Wei Li; Yawen Deng; Yixin Diao; Zixin Sun; Qinyi Luo; Xinli Li; Liqi Zhao; et al. (Theoretical and Applied Genetics, 2022)

Regional Prediction of Coal and Gas Outburst Under Uncertain Conditions Based on the Spatial Distribution of Risk Index - Guorui Zhang; Enyuan Wang; Jianchun Ou; Zhonghui Li (Natural Resources Research, 2022)

SOX9/MKLN1-AS Axis Induces Hepatocellular Carcinoma Proliferation and Epithelial–Mesenchymal Transition - Chao Guo; Shuhuang Zhou; Weimin Yi; Pingzhou Yang; Ou Li; Jianming Liu; Chuang Peng (Biochemical Genetics, 2022)

Calibration and validation of three evapotranspiration models in a tea field in the humid region of south‐east China - Chuan Zhang; Lanlan Li; Haofang Yan; Mingxiong Ou; Muhammad Akhlaq; Wencheng Zhang; Song Huang (Irrigation and Drainage, 2022)
Evapotranspiration (ET c ) is the most important part of agricultural water consumption. Accurate determination of the ET c of tea trees is important in the water management of tea fields. In this study, three models, the Penman–Monteith (PM), Priestley–Taylor (PT) and crop coefficient (KC) models, were applied and calibrated using meteorological data of 2017 in a tea field. The calibrated models were validated using the Bowen ratio energy balance (BREB) method with the data of 2018 and 2019 in the tea field. The canopy resistance of the PM model was calibrated by the inverse method with the BREB‐measured ET c using the Katerji and Perrier (KP) submodel with R 2 equal to 0.80. The annual mean value of the coefficient in the PT model ( α = 1.03) was determined based on the BREB results and meteorological data. In addition, the crop coefficients of tea trees based on the measured ET c and reference evapotranspiration (ET 0 ) were comprehensively evaluated, with values of 0.86, 1.19 and 0.96 at the three growth stages, showing a cyclical evolution within a year. The PT model performed best, with a root mean square error (RMSE) equal to 0.82 mm day −1 and a Nash–Sutcliffe efficiency (NSE) equal to 0.90. The PM model underestimated ET c with RMSE equal to 0.79 mm day −1 and NSE equal to 0.84, while the KC method overestimated ET c .

Structural control on the Baiyinha'er gold mineralization (Southern Central Asian Orogenic belt) related to Early Paleozoic Paleo-Asian Oceanic subduction - Junlai Liu; Tao Jin; Yangwang Ou; Linwei Li; Cheng Zhang; Tianjiao Lu; Xiaoyu Chen (International Journal of Earth Sciences, 2022)

Two new triterpenoid glycosides from leaves of Cyclocarya paliurus - Huihui Sun; Hui Zhu; Jianping Wu; Yuyan Wang; Guihua Li; Yiqian Liu; Xiwen Chang; Saiyu Ou; Wenwen Zha; Huiyun Chen; Rui Gui; Xiaoai He; et al. (Natural Product Research, 2022)

Hydrodynamic Analysis of a Modular Integrated Floating Structure System Based on Dolphin-Fender Mooring - Nianxin Ren; Yuekai Yu; Xiang Li; Jinping Ou (Journal of Marine Science and Engineering, 2022)
For both the expansion of important islands/reefs and the development of marine resources in South China Sea, a modular integrated floating structure (MIFS) system with tidal self-adaptation dolphin-fender mooring (DFM) has been proposed. The DFM, coupled with wave energy converters (WEC), can serve as an anti-motion system. Considering both the modules’ hydrodynamic interaction effect and the connectors’ mechanical coupling effect, both dynamic responses of the MIFS system and the WEC’s output power characteristics were investigated under typical sea conditions. Based on the comprehensive consideration of key factors (safety, economy, and comfort), the effects of both the DFM and module connectors were systematically studied for the MIFS system. Preliminarily optimal design parameters of corresponding connectors and WECs were suggested. The security of the MIFS system under extreme sea conditions was checked, and a promising survival strategy has been proposed. In addition, the modular expansion scheme of the MIFS system was further discussed, and the results indicated that the proposed MIFS system shows good expansibility. The WEC can not only improve both dynamic responses and the comfort of inner modules, but also make considerable wave energy contributions.

Cocktail Formula and Application Prospects for Oral and Maxillofacial Organoids - Mingyu Ou; Qing Li; Xiaofang Ling; Jinguang Yao; Xiaoqiang Mo (Tissue Engineering and Regenerative Medicine, 2022)

MYOCD is Required for Cardiomyocyte-like Cells Induction from Human Urine Cells and Fibroblasts Through Remodeling Chromatin - Xiangyu Zhang; Lijun Chen; Xingnan Huang; Huan Chen; Baomei Cai; Yue Qin; Yating Chen; Sihua Ou; Xiaoxi Li; Zichao Wu; Ziyu Feng; Mengying Zeng; et al. (Stem Cell Reviews and Reports, 2022)

RNA-Seq Reveals the Effect of Ethylene on the Volatile Organic Components (VOCs) of Cavendish Banana at Different Post-harvesting Stages - Tongxin Dou; Chunhua Hu; Shujing Zhao; Huijun Gao; Weidi He; Guiming Deng; Ou Sheng; Fangcheng Bi; Qiaosong Yang; Chunyu Li; Ganjun Yi; Tao Dong (Journal of Plant Growth Regulation, 2022)
Aroma serves as one of the decisive factors influencing the value of banana commodities. Most of characteristic volatile organic components (VOCs) are formed during post-harvesting. However, the changing of VOCs of banana at different post-harvesting stages remain ambiguous. In this study, the VOCs of Cavendish banana for the four typical post-harvesting stages (green stage/half of yellow stage/yellow ripening stage/over ripening stage) are clarified using headspace solid phase micro-extraction (HS-SPME), combined with gas chromatography-mass spectrometry (GC–MS). The results inferred that the relative content of branched-chain esters such as acetate and butyrate, which form the main contributors of aroma in bananas, is higher in the T2 and T3 stages. Further, RNA-Seq technology was employed to clarify the formation mechanism of banana aroma in the post-harvesting stage. The MaTGL4 gene of the linoleic acid metabolism pathway and the MaBCAT3 and MaBCAT5 genes of the valine, leucine and isoleucine degradation pathway in banana suggest the expression is active late in the ripening stage, and the upregulated expression of these genes is analogous to the formation of aroma components such as branched-chain esters and hexenal. The above results not only provide baseline data on the differences in physical and chemical properties of VOCs in various post-harvesting stages of banana production, but also provide theoretical guidance facilitating the subsequent improvement of the commercial value of bananas through genetic improvement.

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Submarine Small-Scale Features of Cyclic Steps in the Penghu Canyon: Implications for the Migration of Canyon - Shaoyu Zhang; Junjiang Zhu; Yonggang Jia; Sanzhong Li; Ruixue Chen; Xingquan Chen; Xiaolin Ou; Qianqian Li (Journal of Marine Science and Engineering, 2022)
The submarine canyons are an important clue to study the evolution process of seafloor geomorphology and they generally indicate the significant linear grooves on the seafloor related to seafloor geodynamic erosion during the evolution of geomorphology. The submarine canyons or canyon groups are not only the channels for the sediment transport from shallow sediments with land-based sources to the deep sea in the sediment source-sink system, but also a key temporary sediment deposition area to study sediment transport patterns and the evolution of submarine geomorphology. In this paper, we processed and analyzed the multibeam bathymetry data acquired in the South China Sea continental margin by the research vessel “Dongfanghong 3” in 2020. Based on fine submarine geomorphological features identified from multibeam bathymetry data, we construct the formation pattern of the cyclic steps. The six cyclic steps (wavelengths of 1–6 km and wave heights of 19–81 m) are found in the lower section of the Penghu canyon and they appeared at the conjunction part of the Penghu and the Taiwan canyon. Based on location and the wavelength variations of the cyclic steps, we propose that the cyclic steps are formed by turbidity current flow along the Penghu and the Taiwan canyons. The axis of the cyclic step CS4–CS6 is shifted westward by about 5° compared to the axis of the cyclic step CS1–CS3. The inconsistency in the axis direction of the cyclic steps CS1–CS3 and CS4–CS6 suggests that is where the migration of the Penghu canyon occurred.

A strategy of model space search for dynamic causal modeling in task fMRI data exploratory analysis - Yilin Ou; Peishan Dai; Xiaoyan Zhou; Tong Xiong; Yang Li; Zailiang Chen; Beiji Zou (Physical and Engineering Sciences in Medicine, 2022)

Hydrodynamic Analysis of a Novel Modular Floating Structure System Integrated with Floating Artificial Reefs and Wave Energy Converters - Yanwei Li; Nianxin Ren; Xiang Li; Jinping Ou (Journal of Marine Science and Engineering, 2022)
A novel modular floating structure (MFS) system moored by tension legs was proposed, which is composed of hexagonal floating modules, floating artificial reefs and wave energy converters (WECs). The integration of floating artificial reefs and WECs into the MFS can improve the marine environment and produce considerable electricity. The effects of both wave characteristics and the module quantity on the hydrodynamic responses of the MFS system were studied in depth, based on a time-domain numerical model. Both the modules’ hydrodynamic interaction effect and the connectors’ mechanical coupling effect were considered. The results indicate that floating artificial reefs combined with WECs can effectively reduce wave loads and convert wave energy into electricity for the MFS system. More modules involved in the MFS system could significantly reduce motion response and produced more wave energy output, which indicates that the MFS system is suitable for large-scale expansion. The effect of different power take-off (PTO) damping coefficients on the WECs’ performance was further investigated, and the optimal damping coefficient was recommended for the MFS system. Finally, the main extreme responses of the MFS system were further investigated, and its safety was checked thoroughly. One survival strategy was proposed, which could efficiently reduce extreme connector loads by more than 50%.

Altered Effective Connectivity Among the Cerebellum and Cerebrum in Patients with Major Depressive Disorder Using Multisite Resting-State fMRI - Peishan Dai; Xiaoyan Zhou; Tong Xiong; Yilin Ou; Zailiang Chen; Beiji Zou; Weihui Li; Zhongchao Huang (The Cerebellum, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Remarkable effects of microbial factors on soil phosphorus bioavailability: A country‐scale study - Jing‐li Lu; Pu Jia; Shi‐wei Feng; Yu‐tao Wang; Jin Zheng; Shu‐ning Ou; Zhuo‐hui Wu; Bin Liao; Wen‐sheng Shu; Jie‐Liang Liang; Jin‐tian Li (Global Change Biology, 2022)
Low soil phosphorus (P) bioavailability causes the widespread occurrence of P‐limited terrestrial ecosystems around the globe. Exploring the factors influencing soil P bioavailability at large spatial scales is critical for managing these ecosystems. However, previous studies have mostly focused on abiotic factors. In this study, we explored the effects of microbial factors on soil P bioavailability of terrestrial ecosystems using a country‐scale sampling effort. Our results showed that soil microbial biomass carbon (MBC) and acid phosphatase were important predictors of soil P bioavailability of agro‐ and natural ecosystems across China although they appeared less important than total soil P. The two microbial factors had a positive effect on soil P bioavailability of both ecosystem types and were able to mediate the effects of several abiotic factors (e.g., mean annual temperature). Meanwhile, we revealed that soil phytase could affect soil P bioavailability at the country scale via ways similar to those of soil MBC and acid phosphatase, a pattern being more pronounced in agroecosystems than in natural ecosystems. Moreover, we obtained evidence for the positive effects of microbial genes encoding these enzymes on soil P bioavailability at the country scale although their effect sizes varied between the two ecosystem types. Taken together, this study demonstrated the remarkable effects of microbial factors on soil P bioavailability at a large spatial scale, highlighting the importance to consider microbial factors in managing the widespread P‐limited terrestrial ecosystems.

Talaromyces marneffei Mp1p Antigen Detection may Play an Important Role in the Early Diagnosis of Talaromycosis in Patients with Acquired Immunodeficiency Syndrome - Xiaoman Chen; Xu Ou; Haodi Wang; Liya Li; Pengle Guo; Xiejie Chen; Weiping Cai; Xiaoping Tang; Linghua Li (Mycopathologia, 2022)

The expression discrepancy and characteristics of long non-coding RNAs in peripheral blood leukocytes from amyotrophic lateral sclerosis patients - Yujiao Yu; Dejiang Pang; Chunyu Li; Xiaojing Gu; Yongping Chen; Ruwei Ou; Qianqian Wei; Huifang Shang (Molecular Neurobiology, 2022)

Integrated transcriptomic and metabolomic analyses of Caucasian clover (Trifolium ambiguum Bieb.) in response to freezing stress - Dan Mou; Zongren Li; Wenhui Liu; Guoling Liang; Zhifeng Jia; Hongyan Yu; Jiuluan Wang; Weiyou Ou; Kai Liu; Xixi Yao; Yu Zhan; Geliang Ma; et al. (Brazilian Journal of Botany, 2022)

Therapeutic Effects of Sodium Para-Aminosalicylic Acid on Cognitive Deficits and Activated ERK1/2-p90RSK/NF-κB Inflammatory Pathway in Pb-Exposed Rats - Li-li Lu; Yu-wen Zhang; Zhao-cong Li; Yuan-yuan Fang; Lei-lei Wang; Yue-song Zhao; Shao-jun Li; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2022)

Dissolved Organic Matter and Activities of Extracellular Enzymes in Two Lagoons (South China Sea) Affected by Aquaculture - Linjian Ou; Jianting Li; Xianyang Zhang; Zhou Wang; Jian Zou; Songhui Lu (Frontiers in Marine Science, 2022)
Xincun Lagoon and Li’an Lagoon are typical tropical lagoons containing unique seagrass meadow and mangrove forest ecosystems. However, nutrient pollution from human activities threatens ecosystem health in these areas. A year-long bimonthly survey was carried out to study the bioavailability of organic nutrients through hydrolysis of the extracellular enzymes β-glucosidase (GLU), leucine aminopeptidase (LAP), and alkaline phosphatase (AP) in the two lagoons. The results showed that the nutrient statuses in Xincun Lagoon and Li’an Lagoon were highly variable and enriched with organic nutrients, especially nitrogen. Organic nitrogen and phosphorus were actively recycled in the lagoons through active LAP and AP hydrolysis. The enzyme activities were mostly produced by particulate-associated bacteria and were positively regulated by the existence of organic nutrients. The enzymatic stoichiometry results indicated the importance of dissolved proteins and aminopolysaccharides as sources of both carbon and nitrogen and a potential phosphorus limitation on microbial growth in the lagoons. Our results emphasized the importance of EEAs in the recycling of organic nutrients and the potential influence of enriched organic nutrients on both microorganisms and plants in Xincun Lagoon and Li’an Lagoon.

Identification and validation of quantitative trait loci for the functional stay green trait in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Tianheng Ren; Tao Fan; Shulin Chen; Yongyan Chen; Xia Ou; Qing Jiang; Wanhua Peng; Zhenglong Ren; Feiquan Tan; Peigao Luo; Zhi Li (Theoretical and Applied Genetics, 2022)

Development of a 48-Well Dynamic Suspension Culture System for Pancreatic Differentiation from Human Embryonic Stem Cells - Yizhe Song; Xiaoqian Chen; Decan Liang; Jing Liu; Jingqiu Li; Zhensheng Ou; Tingting Tang; Peiwen Xing; Leilei Guo; Shidu Zhang; Qunrui Ye; Wenjia Li; et al. (Stem Cell Reviews and Reports, 2022)

SSR analysis and fingerprint construction to evaluate the genetic diversity of medicinal plum varieties - Rui Wang; Xin Li; Wei Zhang; Jinmei Ou; Chengwu Fang; Qianqian Song; Huiyin Zhou (Journal of Plant Biochemistry and Biotechnology, 2022)

Genome-wide locus-specific DNA methylation repatterning may facilitate rapid evolution of mercury resistance in rice - Weixuan Cong; Ning Li; Jinbin Wang; Ying Kang; Yiling Miao; Chunming Xu; Ziqi Wang; Tongtong Liu; Lei Gong; Bao Liu; Xiufang Ou (Genes & Genomics, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

Four new prenylflavonol glycosides from the leaves of Cyclocarya paliurus - Zi-Jun Ye; Hui-Hui Sun; Zu-Hui Chen; Jian-Ping Wu; Jing Li; Hui Zhu; Lu-Lu Huang; Xi-Wen Chang; Sai-Yu Ou; Wen-Xuan Wang; Xiao-Ai He; Gang-Zhi Zhu; et al. (Natural Product Research, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Submarine Geomorphological Features and Their Origins Analyzed from Multibeam Bathymetry Data in the South China Sea - Xiaolin Ou; Junjiang Zhu; Sanzhong Li; Yonggang Jia; Zhongjia Jia; Shengsheng Zhang; Shaoyu Zhang; Ruixue Chen; Xingquan Chen; Dong Ding; Huilin Xing; Yanhui Suo; et al. (Journal of Marine Science and Engineering, 2021)
We processed the raw multi-beam bathymetry data acquired in the central and northeastern part of the South China Sea by eliminating noise and abnormal water depth values caused by environmental factors, and a high resolution bathymetric map with a 20-m grid interval was constructed. Various scales of seafloor geomorphological features were identified from the data, including an image of Shenhu canyon, which is located in the northern continental margin of the South China Sea; submarine reticular dunes in the north of the Dongsha atoll; submarine parallel dunes in the northeast of the Dongsha atoll; and several seamounts in the southwest sub-basin and in the east sub-basin. In the processing step, various anomalies in the multi-beam bathymetry data were corrected. The optimal swath filtering and surface filtering methods were chosen for different scales of seafloor topography in order to restore the true geomorphological features. For the large-scale features with abrupt elevation changes, such as seamounts (heights of ~111–778 m) and submarine canyons (incision height of ~90–230 m), we applied swath filtering to remove noise from the full water depth range of the data, and then surface filtering to remove small noises in the local areas. For the reticular dunes and parallel dunes (heights of ~2–32 m), we applied only surface filtering to refine the data. Based on the geometries of the geomorphological features with different scales, the marine hydrodynamic conditions, and the regional structure in the local areas, we propose that the Shenhu submarine canyon was formed by turbidity current erosion during the Sag subsidence and the sediment collapse. The submarine reticular dunes in the north of the Dongsha atoll were built by the multi-direction dominant currents caused by the previously recognised internal solitary waves around the Dongsha atoll. The submarine parallel dunes in the northeast of the Dongsha atoll were built by the repeated washing of sediments with the influence of the tidal currents and internal solitary waves. The conical, linear and irregular seamounts identified from the bathymetry data were formed during the spreading of the southwest sub-basin and the east sub-basin. The identified seamounts in the multi-beam bathymetry data are correlated to deep magmatic activities, the Zhongnan transform fault and the NE-trending faults.

The ecological mechanisms of Acetes blooms as a threat to the security of cooling systems in coastal nuclear power plants - Lina An; Lei Wang; Danyun Ou; Cun Jia; Weiwen Li; Ye Ding; Chengmao You; Jianji Liao; Hao Huang (Journal of Coastal Conservation, 2021)
Recently, there have been an increasing number of reports on the shutdown of coastal nuclear power plants because of outbreaks of marine organisms, such as jellyfish and fish. These organisms clog the pipes during an outbreak or when they accumulate near nuclear power plants in coastal regions. The safety of nuclear power plants is threatened by Acetes blooms. Thus, based on the physiology and ecology of Acetes , including the biology, auxology, feeding ecology, population dynamics, environmental suitability and effects of nuclear power plant thermal effluents, three hypotheses were proposed by previous studies to explain the ecological mechanisms of an Acetes bloom: (1) the wintering ground hypothesis, (2) the population dynamics hypothesis and (3) the ecosystem dynamics hypothesis. The main content and prevention measures used in previous studies were introduced and reviewed. Ecological protection combined with relevant environmental protection policies and laws in coastal areas are the long-term goals for the management of Acetes blooms.

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Treadmill Exercise Relieves Chronic Restraint Stress-induced Cognitive Impairments in Mice Via Activating Protein Phosphatase 2A - Wenjing Zhang; Haining Ou; Borui Zhang; Meifeng Zheng; Lan Yan; Yang Chen; Kwok-Fai So; Li Zhang (Neuroscience Bulletin, 2021)

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Potential roles for microRNAs in facilitating physiological adaptation to low‐temperature stress in Penaeus vannamei - QingJian Liang; WenNa Dong; MuFei Ou; ZhongHua Li; Yuan Liu; Weina Wang (Journal of Fish Diseases, 2021)
Water temperature is one of the most common physiological stressors in aquaculture. Previous studies demonstrate that organisms require miRNA activity for survival in various unfavourable environmental conditions. However, the detailed role of miRNA in response to low‐temperature stress is still unclear. This study was conducted to construct a comprehensive miRNA dataset for the Penaeus vannamei after low‐temperature stress. A total of 329 known miRNAs and 60 putative novel miRNAs were identified. Among them, 17 miRNAs were identified with the most significant differences, and they were found to be involved in stimulation or stress processes. The main enriched target pathways of the 17 miRNAs were the Hippo signalling pathway, autophagy, apoptosis and MAPK signalling. In addition, all the 17 miRNAs identified were up‐regulated, suggesting that miRNA by inhibiting the expression of target genes constitutes an effective strategy for Penaeus vannamei to cope with low‐temperature stress. The 35‐putative target of the 17 miRNAs was related to apoptosis and autophagy‐related proteins, such as Pxt, DRAM2, cytochrome c, ATG2B, JNK, ATG4 and API5. The analysis of miRNA expression profiles contributes to the understanding of the molecular mechanisms of low‐temperature tolerance in Penaeus vannamei . This study's findings enrich current miRNA resources and offer the possibility to validate the involvement of 17 miRNAs in the response of shrimp to low‐temperature stress.

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Long Non-coding RNA GAS5 Worsens Coronary Atherosclerosis Through MicroRNA-194-3p/TXNIP Axis - Yanbing Li; Yu Geng; Boda Zhou; Xuejiao Wu; Ou Zhang; Xiaonan Guan; Yajun Xue; Siyuan Li; Xianjing Zhuang; Jie Zhou; Meng Chang; Guobin Miao; et al. (Molecular Neurobiology, 2021)
It is formerly conducted that long non-coding RNA growth arrest-specific 5 (GAS5) is involved in the process of coronary atherosclerosis (AS). The regulatory effects of GAS5 on the microRNA (miR)-194-3p/thioredoxin-interacting protein (TXNIP) axis in AS have been insufficiently explored yet. Thereafter, this work is started from GAS5/miR-194-3p/TXNIP axis in AS. AS rats were modeled to obtain their coronary vascular tissues and endothelial cells (ECs), in which GAS5, miR-194-3p, and TXNIP expression were tested. ECs were identified by immunohistochemistry. The mechanism among GAS5, miR-194-3p, and TXNIP was determined. ECs were transfected with inhibited GAS5 or overexpressed miR-194-3p to decipher their functions in proliferation and apoptosis of ECs in AS. Raised GAS5 and TXNIP and degraded miR-194-3p expression levels exhibited in AS. GAS5 bound to miR-194-3p while miR-194-3p targeted TXNIP. Depleting GAS5 or restoring miR-194-3p enhanced proliferation and depressed apoptosis of ECs in AS. This work clearly manifests that inhibited GAS5 facilitates the growth of ECs through miR-194-3p-targeted TXNIP in AS, consolidating the basal reference to the curing for AS.

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Interface interaction between high-siliceous/calcareous mineral granules and model cell membranes dominated by electrostatic force - Mulan Chen; Faqin Dong; Hailong Li; Yulian Zhao; Shi Ou; Mingxue Liu; Wei Zhang (Environmental Science and Pollution Research, 2021)

Simulation and test of the movement process of mixed flow composed of slurry and coarse particle - Xian-jun Ji; Ying Liang; Guo-qiang Ou; Hua-li Pan (European Journal of Environmental and Civil Engineering, 2021)

Correction to: Utilization of a Wheat55K SNP array-derived high-density genetic map for high-resolution mapping of quantitative trait loci for important kernel-related traits in common wheat - Tianheng Ren; Tao Fan; Shulin Chen; Chunsheng Li; Yongyan Chen; Xia Ou; Qing Jiang; Zhenglong Ren; Feiquan Tan; Peigao Luo; Chen Chen; Zhi Li (Theoretical and Applied Genetics, 2021)

Characteristics of soil erosion and sediment size distribution for different land uses in the Chinese Mollisol region - Hai-ou Shen; Jun Feng; Dong-li Wang; Hong-li Li; Yu Wang (Journal of Mountain Science, 2021)

Genomewide comparative analysis of codon usage bias in three sequenced Jatropha curcas - ZHANJUN WANG; GUIYI WANG; QIANWEN CAI; YAO JIANG; CHENCHEN WANG; HAIMENG XIA; ZIQI WU; JIE LI; ZULAN OU; ZHONGDONG XU; JISEN SHI; JINHUI CHEN (Journal of Genetics, 2021)

Utilization of a Wheat55K SNP array-derived high-density genetic map for high-resolution mapping of quantitative trait loci for important kernel-related traits in common wheat - Tianheng Ren; Tao Fan; Shulin Chen; Chunsheng Li; Yongyan Chen; Xia Ou; Qing Jiang; Zhenglong Ren; Feiquan Tan; Peigao Luo; Chen Chen; Zhi Li (Theoretical and Applied Genetics, 2021)

A high‐throughput ultrasonic spraying inoculation method promotes colony cultivation of rare microbial species - Xizhi Huang; Pengjie Li; Mengfan Zhou; Yiwei Li; Xiaowen Ou; Peng Chen; Georg Guggenberger; Bi‐Feng Liu (Environmental Microbiology, 2021)
Summary Current method for obtaining microbial colonies still relies on traditional dilution and spreading plate (DSP) procedures, which is labor‐intensive, skill‐dependent, low‐throughput and inevitably causing dilution‐to‐extinction of rare microorganisms. Herein, we proposed a novel ultrasonic spraying inoculation (USI) method that disperses microbial suspensions into millions of aerosols containing single cells, which lately be deposited freely on a gel plate to achieve high‐throughput culturing of colonies. Compared with DSP, USI significantly increased both distributing uniformity and throughput of the colonies on agar plates, improving the minimal colony‐forming abundance of rare Escherichia coli mixed in a lake sample from 1% to 0.01%. Applying this novel USI to a lake sample, 16 cellulose‐degrading colonies were screened out among 4766 colonies on an enlarged 150‐mm‐diameter LB plate. Meanwhile, they could only be occasionally observed when using commonly used DSP procedures. 16S rRNA sequencing further showed that USI increased colony‐forming species from 11 (by DSP) to 23, including seven completely undetectable microorganisms in DSP‐reared communities. In addition to avoidance of dilution‐to‐extinction, operation‐friendly USI efficiently inoculated microbial samples on the agar plate in a high‐throughput and single‐cell form, which eliminated masking or out‐competition from other species in associated groups, thereby improving rare species cultivability.

Concentration of circulating microparticles: a new biomarker of acute heart failure after cardiac surgery with cardiopulmonary bypass - Yuquan Li; Haoxiang Yuan; Caiyun Chen; Chao Chen; Jian Ma; Yating Chen; Yan Li; Yupeng Jian; Donghong Liu; Zhijun Ou; Jingsong Ou (Science China Life Sciences, 2021)

The impact of urbanization and consumption patterns on China’s black carbon emissions based on input–output analysis and structural decomposition analysis - Zhongci Deng; Ping Kang; Zhen Wang; Xiaoling Zhang; Weijie Li; Yihan Ou; Yu Lei; Ying Dang; Zhongren Deng (Environmental Science and Pollution Research, 2021)

Genotype and Phenotype Correlations for TBL1XR1 in Neurodevelopmental Disorders - Yingting Quan; Qiumeng Zhang; Meilin Chen; Huidan Wu; Jianjun Ou; Yidong Shen; Kuokuo Li; Guanglei Xun; Jingping Zhao; Zhengmao Hu; Kun Xia; Hui Guo (Journal of Molecular Neuroscience, 2020)

Optimizing Human Epidermal Growth Factor for its Endurance and Specificity Via Directed Evolution: Functional Importance of Leucine at Position 8 - Yujie Sun; Nanyan Yang; Fei Li; Jinxin Ou; Xin Liu; Qing Zhang (International Journal of Peptide Research and Therapeutics, 2020)

First identification and genomic characterization of equine hepacivirus sub-type 3 strain in China - Liyan Wu; Jiajun Ou; Siqi Cai; Jinzhao Ji; Zixin Ren; Ran Shao; Shoujun Li (Virus Genes, 2020)

Genomic sequencing and characterization of a novel group of canine bufaviruses from Henan province, China - Ran Shao; Feiyan Zheng; Siqi Cai; Jinzhao Ji; Zixin Ren; Jiawei Zhao; Liyan Wu; Jiajun Ou; Gang Lu; Shoujun Li (Archives of Virology, 2020)

Puerarin Alleviates Lipopolysaccharide-Induced Myocardial Fibrosis by Inhibiting PARP-1 to Prevent HMGB1-Mediated TLR4-NF-κB Signaling Pathway - Shu-Yuan Ni; Xing-Long Zhong; Ze-Hua Li; Dong-Jian Huang; Wen-Ting Xu; Yan Zhou; Cai-Wen Ou; Min-Sheng Chen (Cardiovascular Toxicology, 2020)

Single-nucleotide polymorphisms influence the promoter activities of systemic lupus erythematosus-associated genes - Jinjun Qiu; Xiaoming Qin; Jinli Wen; Li Wu; Lei Kong; Yangxi Ou; Shucai Yang (Biotechnology Letters, 2020)

Study of failure mechanism of bottom-hole rock mass approaching a gas-fractured zone during nitrogen drilling - Luo Chengbo; Jiang Zujun; Li Gao; He Long; Ou Biao; Meng Yingfeng; Xiao Guoyi; Yan Yancheng; Wang Xiyong (Arabian Journal of Geosciences, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

First report of feline morbillivirus in mainland China - JiaJun Ou; Shaotang Ye; Haibin Xu; Jijing Zhao; Zixin Ren; Gang Lu; Shoujun Li (Archives of Virology, 2020)

Effects of hourly levels of ambient air pollution on ambulance emergency call-outs in Shenzhen, China - Ting-Ting Chen; Zhi-Ying Zhan; Yi-Min Yu; Li-Jun Xu; Ying Guan; Chun-Quan Ou (Environmental Science and Pollution Research, 2020)

Biofertilizer application triggered microbial assembly in microaggregates associated with tomato bacterial wilt suppression - Menghui Dong; Mengli Zhao; Zongzhuan Shen; Xuhui Deng; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2020)

Identification of Mycobacterium abscessus species and subspecies using the Cas12a/sgRNA-based nucleic acid detection platform - Guohui Xiao; Su Zhang; Zhihang Liang; Guanqiang Li; Mutong Fang; Yaya Liu; Juanjuan Zhang; Min Ou; Xing He; Tianyu Zhang; Changchun Zeng; Lei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Effect of spatially variable saturated hydraulic conductivity with non-stationary characteristics on the stability of reservoir landslides - Yang Xue; Yiping Wu; Fasheng Miao; Linwei Li; Kang Liao; Guangzhao Ou (Stochastic Environmental Research and Risk Assessment, 2020)

An ecological barrier between the Himalayas and the Hengduan Mountains maintains the disjunct distribution of Roscoea - De‐Bao Li; Xiao‐Kun Ou; Jian‐Li Zhao; Qing‐Jun Li (Journal of Biogeography, 2020)
Aim Regional disjunction in mountainous regions is ubiquitous and is closely associated with the evolution of mountain biodiversity. However, the mechanisms of maintaining regional disjunction are often ignored, especially regarding the role of ecological barriers. The aim of this study is to test whether an ecological barrier maintains the regional disjunction of Roscoea between the Himalayas (HIM) and the Hengduan Mountains/Yun‐Gui Plateau (HMY). Location The Himalayas and the Hengduan Mountains/Yun‐Gui Plateau, Asia. Taxon Monocot:Zingiberales:Zingiberaceae: Roscoea . Methods Occurrence data from Roscoea were collected from public databases and field investigations. Environmental niche modelling (ENM) was used to predict the potential distribution of Roscoea during the Last Interglacial (LIG), the Last Glacial Maximum (LGM), the present and the future. An environmental variable difference test, principal component analysis (PCA), discriminant function analysis (DFA) and niche identity test were employed to qualify and quantify the contributions of environmental factors to ecological divergence based on 7 and 26 environmental variables. Results Environmental niche modelling predicted an ecological gap of Roscoea between the HIM and the HMY from the LIG into the future, excluding the LGM. Statistically significant differences were detected in eight unique environmental variables across the Gap, which was mostly related to low temperatures and high moisture levels. The PCA, DFA and niche identity test suggested larger ecological separations among the Gap, the HIM and the HMY based on 26 environmental variables than based on seven variables. Main conclusions All clues point to an ecological barrier that has been maintaining the regional disjunction of Roscoea . This ecological barrier is predicted to be stable under future climate change and may reflect long‐term ecological divergence shaped by the adaptation of Roscoea to divergent habitats. Our study highlights that the effects of specific environmental variables, with possible interactions among multiple ecological factors, being closely related to the ecological barrier.

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Transcriptome Profile Analysis of Twisted Leaf Disease Response in Susceptible Sugarcane with Narenga porphyrocoma Genetic Background - Jinju Wei; Zhihui Xiu; Huiping Ou; Junhui Chen; Huayan Jiang; Xiaoqiu Zhang; Ronghua Zhang; Hui Zhou; Yiyun Gui; Haibi Li; Yangrui Li; Rongzhong Yang; et al. (Tropical Plant Biology, 2019)

Integrated analysis of quantitative proteome and transcriptional profiles reveals abnormal gene expression and signal pathway in bladder cancer - Songbai Liao; Minglin Ou; Liusheng Lai; Hua Lin; Yaoshuang Zou; Yonggang Yu; Xuede Li; Yong Dai; Weiguo Sui (Genes & Genomics, 2019)

Surface-adaptive nanoparticles with near-infrared aggregation-induced emission for image-guided tumor resection - Xiaoyan Zhang; Cong Li; Wenyi Liu; Hanlin Ou; Dan Ding (Science China Life Sciences, 2019)

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

Effects of rainfall intensity and topography on rill development and rill characteristics on loessial hillslopes in China - Hai-ou Shen; Fen-li Zheng; Lei Wang; Lei-lei Wen (Journal of Mountain Science, 2019)

Different response to middle-Palaeozoic magmatism during intracontinental orogenic processes: evidence from southeastern South China Block - Quan Ou; Jian–Qing Lai; Bruna B. Carvalho; Feng Zi; Hua Kong; Bin Li; Zi–Qi Jiang (International Geology Review, 2019)

A Method for Reducing Cogging Torque of Integrated Propulsion Motor - Huanyu Ou; Yuli Hu; Zhaoyong Mao; Yukai Li (Journal of Marine Science and Engineering, 2019)
How to reduce the cogging torque of the integrated propeller motor is an important means to improve its noise performance because cogging torque is one of the key factors causing torque ripple. We proposed a method to reduce the cogging torque by optimizing the size of the Halbach array’s auxiliary pole. First, an analytical model for the airgap magnetic field of Halbach array based on different dimensions (including the circumference ratio and the radial thickness) of the auxiliary pole is given. Then the finite element method is used to verify the analytical model. On the basis, we calculated the cogging torque of different size of auxiliary poles as sample data by combining different circumference ratio and radial thickness. Furthermore, using the two-variable single-objective neural network genetic optimization algorithm based on Backpropagation (BP), we obtain the optimal size of the auxiliary pole. Finally, comparing the motor cogging torque and torque ripple before and after optimization indicated that the cogging torque and torque ripple are effectively reduced after optimizing the size of the auxiliary pole.

Identification of environmental factors controlling phosphorus fractions and mobility in restored wetlands by multivariate statistics - Hu Cui; Yang Ou; Lixia Wang; Haitao Wu; Baixing Yan; Lu Han; Yingxin Li (Environmental Science and Pollution Research, 2019)

Geotechnical properties and microstructure of lime-stabilized silt clay - Fu Zhu; Zechuang Li; Weizhi Dong; Yangyun Ou (Bulletin of Engineering Geology and the Environment, 2019)

Genetic diversity, population structure and identification of Dendrobium cultivars with high polysaccharide contents using SCoT, SCAR and nested PCR markers - Qingguo Li; Jianmei Mo; Wenru Wu; Juan Yang; Jinjin Li; Tianxing Lai; Zhanlun Ou; Zhenwen Qiu; Shixia Guan; Junjie Liao (Genetic Resources and Crop Evolution, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Comparative Analysis of CRISPR Loci Found in Streptomyces Genome Sequences - Jinqi Zhang; Xiaobin Li; Zixin Deng; Hong-Yu Ou (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Interannual wave climate variability in the Taiwan Strait and its relationship to ENSO events - Yanda Ou; Fangguo Zhai; Peiliang Li (Journal of Oceanology and Limnology, 2018)

Low pH stress responsive transcriptome of seedling roots in wheat (Triticum aestivum L.) - Haiyan Hu; Jie He; Junjie Zhao; Xingqi Ou; Hongmin Li; Zhengang Ru (Genes & Genomics, 2018)

Intensified variability of the El Niño–Southern Oscillation enhances its modulations on tree growths in southeastern China over the past 218 years - Lei Wang; Keyan Fang; Dai Chen; Zhipeng Dong; Feifei Zhou; Yingjun Li; Peng Zhang; Tinghai Ou; Guoyang Guo; Xinguang Cao; Mingtong Yu (International Journal of Climatology, 2018)
Lack of long‐term tree‐ring records in the core regions of the Asian summer monsoon in southeastern China limits our ability of evaluating the current climate change in a historical context. In this study, we developed the first 218‐year tree‐ring chronology (1798–2015) of Pinus massoniana in Zhangping area, Fujian Province, humid subtropical China. This chronology is positively correlated with winter–spring (January–March) temperature ( r = 0.359, p r = 0.351, p r = 0.30, N = 66) matches closely with the ENSO variability during 1950–2015. The modulations of the ENSO on regional tree growth have been the most conspicuous since the 1950s, which corresponds to its enhanced inter‐annual variability. The extreme growth anomalies match quite well with the extreme years of the moisture‐sensitive chronologies. The dry epoch from 1935 to 1958 is the most severe long‐lasting drought in our tree rings, which is a widely distributed pattern in southeastern China and is likely modulated by the La Niña‐like modes in that period.

Model Test on Self-Weight Consolidation of the Red Mud Tailings Placed in the Karsts - Jiequan Li; Xiaoduo Ou (Geotechnical and Geological Engineering, 2018)

Soil pre-fumigation could effectively improve the disease suppressiveness of biofertilizer to banana Fusarium wilt disease by reshaping the soil microbiome - Zongzhuan Shen; Chao Xue; Paul W. J. Taylor; Yannan Ou; Beibei Wang; Yan Zhao; Yunze Ruan; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2018)

High Selenium Yeast mitigates aluminum-induced cerebral inflammation by increasing oxidative stress and blocking NO production - Changyu Cao; Xiaowen Li; Lei Qin; Junchong Luo; Mengdan Zhang; Zijian Ou; Kai Wang (BioMetals, 2018)

Rainfall and inflow effects on soil erosion for hillslopes dominated by sheet erosion or rill erosion in the Chinese Mollisol region - Hai-ou Shen; Lei-lei Wen; Yun-feng He; Wei Hu; Hong-li Li; Xiao-cui Che; Xin Li (Journal of Mountain Science, 2018)

Long runout mechanism of the Shenzhen 2015 landslide: insights from a two-phase flow viewpoint - Cheng Qiao; Guo-qiang Ou; Hua-li Pan; Chao-jun Ouyang; Yang Jia (Journal of Mountain Science, 2018)

A grid-based tropospheric product for China using a GNSS network - Hongxing Zhang; Yunbin Yuan; Wei Li; Baocheng Zhang; Jikun Ou (Journal of Geodesy, 2018)

Germplasm screening of Musa spp. for resistance to Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) - Cunwu Zuo; Guiming Deng; Bin Li; Heqiang Huo; Chunyu Li; Chunhua Hu; Ruibin Kuang; Qiaosong Yang; Tao Dong; Ou Sheng; Ganjun Yi (European Journal of Plant Pathology, 2018)

Immobilization of soil cadmium using combined amendments of illite/smectite clay with bone chars - Hong Li; Jieyong Ou; Xuedong Wang; Zengguang Yan; Youya Zhou (Environmental Science and Pollution Research, 2018)

Identification of the dwarf gene GmDW1 in soybean (Glycine max L.) by combining mapping-by-sequencing and linkage analysis - Zhong-feng Li; Yong Guo; Lin Ou; Huilong Hong; Jun Wang; Zhang-xiong Liu; Bingfu Guo; Lijuan Zhang; Lijuan Qiu (Theoretical and Applied Genetics, 2018)

Different tolerance mechanism to alkaline stresses between Populus bolleana and its desert relative Populus euphratica - Yufang Sun; Yongbin Ou; Yongfeng Gao; Xuan Zhang; Yongmei He; Yuan Li; Yinan Yao (Plant and Soil, 2018)

Pyr-miR171f-targeted PyrSCL6 and PyrSCL22 genes regulate shoot growth by responding to IAA signaling in pear - Shuling Jiang; Qiuju Chen; Qiulei Zhang; Yi Zhang; Ningning Hao; Chunqing Ou; Fei Wang; Tianzhong Li (Tree Genetics & Genomes, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Impact of water level fluctuations on the development of phytoplankton in a large subtropical reservoir: implications for the management of cyanobacteria - Qiuhua Li; Jing Xiao; Teng Ou; Mengshu Han; Jingfu Wang; Jingan Chen; Yulin Li; Nico Salmaso (Environmental Science and Pollution Research, 2018)

Effects of live rock on removal of dissolved inorganic nitrogen in coral aquaria - Yan Li; Xinqing Zheng; Xiaozhou Yang; Dangyun Ou; Rongcheng Lin; Xinming Liu (Acta Oceanologica Sinica, 2017)

Characterization of a metagenome-derived protease from contaminated agricultural soil microorganisms and its random mutagenesis - Chengjian Jiang; Liang Zhang; Fajia Li; Can Meng; Rong Zeng; Jie Deng; Peihong Shen; Qian Ou; Bo Wu (Folia Microbiologica, 2017)

New observations on Vetulicola longbaoshanensis from the Lower Cambrian Guanshan Biota (Series 2, Stage 4), South China - JinShu Li; JianNi Liu; Qiang Ou (Science China Earth Sciences, 2017)

Three divergent approaches identified the same RGF1 receptors in Arabidopsis thaliana - Yang Ou; Jia Li (Science China Life Sciences, 2017)

Interannual-decadal variability of wintertime mixed layer depths in the North Pacific detected by an ensemble of ocean syntheses - Takahiro Toyoda; Yosuke Fujii; Tsurane Kuragano; Naohiro Kosugi; Daisuke Sasano; Masafumi Kamachi; Yoichi Ishikawa; Shuhei Masuda; Kanako Sato; Toshiyuki Awaji; Fabrice Hernandez; Nicolas Ferry; et al. (Climate Dynamics, 2017)

Intercomparison and validation of the mixed layer depth fields of global ocean syntheses - Takahiro Toyoda; Yosuke Fujii; Tsurane Kuragano; Masafumi Kamachi; Yoichi Ishikawa; Shuhei Masuda; Kanako Sato; Toshiyuki Awaji; Fabrice Hernandez; Nicolas Ferry; Stéphanie Guinehut; Matthew J. Martin; et al. (Climate Dynamics, 2017)

TERT Genetic Mutations as Prognostic Marker in Glioma - Peiliang Geng; Xiaoxin Zhao; Juanjuan Ou; Jianjun Li; Rina Sa; Houjie Liang (Molecular Neurobiology, 2017)

Examining two sets of introgression lines reveals background-independent and stably expressed QTL that improve grain appearance quality in rice (Oryza sativa L.) - Xianjin Qiu; Kai Chen; Wenkai Lv; Xiaoxue Ou; Yajun Zhu; Danying Xing; Longwei Yang; Fangjun Fan; Jie Yang; Jianlong Xu; Tianqing Zheng; Zhikang Li (Theoretical and Applied Genetics, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Future Science Prize goes to non-invasive prenatal testing - Kang Li; Yaou Duan; Magdalene Yin Lin Ting; Zhiying Ou; Li Liu; Kang Zhang; Xin Fu (Science China Life Sciences, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

The Comparatively Proteomic Analysis in Response to Cold Stress in Cassava Plantlets - Feifei An; Genghu Li; Qing X. Li; Kaimian Li; Luiz J. C. B. Carvalho; Wenjun Ou; Songbi Chen (Plant Molecular Biology Reporter, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Structural geometrical analysis and simulation of decollement growth folds in piedmont Fauqi Anticline of Zagros Mountains, Iraq - ChengHua Ou; Wei Chen; ChaoChun Li; WenJiang Zhou (Science China Earth Sciences, 2016)

Curcumin attenuates osteogenic differentiation and calcification of rat vascular smooth muscle cells - Menglin Hou; Yan Song; Zhenlin Li; Chufan Luo; Jing-Song Ou; Huimin Yu; Jianyun Yan; Lihe Lu (Molecular and Cellular Biochemistry, 2016)

The flagellin hypervariable region is a potential flagella display domain in probiotic Escherichia coli strain Nissle 1917 - Ying Yang; Yi Yang; Bingming Ou; Pengpeng Xia; Mingxu Zhou; Luan Li; Guoqiang Zhu (Archives of Microbiology, 2016)

Three new 2,5-diketopiperazines from the fish intestinal Streptomyces sp. MNU FJ-36 - Yi-xin Ou; Jia-fu Huang; Xiu-min Li; Qian-jin Kang; Yu-tian Pan (Natural Product Research, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Empirical calibration of the clinopyroxene–garnet magnesium isotope geothermometer and implications - Wang-Ye Li; Fang-Zhen Teng; Yilin Xiao; Hai-Ou Gu; Xiang-Ping Zha; Jian Huang (Contributions to Mineralogy and Petrology, 2016)

Targeting AMPK signalling pathway with natural medicines for atherosclerosis therapy: an integration of in silico screening and in vitro assay - Tiantong Ou; Xumin Hou; Shaofeng Guan; Jinjie Dai; Wenzheng Han; Ruogu Li; Wenxia Wang; Xinkai Qu; Min Zhang (Natural Product Research, 2016)

A Comprehensive Analysis of Influence ERCC Polymorphisms Confer on the Development of Brain Tumors - Peiliang Geng; Juanjuan Ou; Jianjun Li; Yunmei Liao; Ning Wang; Ganfeng Xie; Rina Sa; Chen Liu; Lisha Xiang; Houjie Liang (Molecular Neurobiology, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Analysis of Glial Distribution in Drosophila Adult Brains - Jiayao Ou; Zongbao Gao; Li Song; Margaret S. Ho (Neuroscience Bulletin, 2016)

Genetic Contribution of Polymorphisms in Glutathione S-Transferases to Brain Tumor Risk - Peiliang Geng; Jianjun Li; Ning Wang; Juanjuan Ou; Ganfeng Xie; Rina Sa; Chen Liu; Lisha Xiang; Hongtao Li; Houjie Liang (Molecular Neurobiology, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Boron deficiency affects root vessel anatomy and mineral nutrient allocation of Poncirus trifoliata (L.) Raf. - Li Mei; Qiaohong Li; Huan Wang; Ou Sheng; Shu-ang Peng (Acta Physiologiae Plantarum, 2016)

Functional polymorphisms in the gene encoding macrophage migration inhibitory factor (MIF) are associated with active pulmonary tuberculosis - Shou-Gang Kuai; Qin-Fang Ou; De-Hong You; Zhong-Bo Shang; Jun Wang; Jun Liu; Xi-Ke Zhou; Hao Pei; Li-Hua Huang (Infectious Diseases, 2016)

Change of Polysaccharide Content and Its Relation with Nitrogen Level in Sugarcane Leaves Under Nitrogen-Fixing Bacteria Inoculation and Nitrogen Supply - Xi-Hui Liu; Hui-Ping Ou; Rong-Zhong Yang; Rong-Hua Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Further studies on the numerical simulation of bubble plumes in the cold seepage active region - Canping Li; Limin Gou; Jiachun You; Xuewei Liu; Chuling Ou (Acta Oceanologica Sinica, 2016)

Atomic connectomics signatures for characterization and differentiation of mild cognitive impairment - Jinli Ou; Li Xie; Xiang Li; Dajiang Zhu; Douglas P. Terry; A. Nicholas Puente; Rongxin Jiang; Yaowu Chen; Lihong Wang; Dinggang Shen; Jing Zhang; L. Stephen Miller; et al. (Brain Imaging and Behavior, 2015)

The toxic mechanism and bioactive components of Chinese leek root exudates acting against Fusarium oxysporum f. sp. cubense tropical race 4 - Cunwu Zuo; Chunyu Li; Bin Li; Yuerong Wei; Chunhua Hu; Qiaosong Yang; Jing Yang; Ou Sheng; Ruibin Kuang; Guiming Deng; Manosh Kumar Biswas; Ganjun Yi (European Journal of Plant Pathology, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Effects of norfloxacin on hepatic genes expression of P450 isoforms (CYP1A and CYP3A), GST and P-glycoprotein (P-gp) in Swordtail fish (Xiphophorus Helleri) - Ximei Liang; Lan Wang; Ruikang Ou; Xiangping Nie; YuFeng Yang; Fang Wang; Kaibin Li (Ecotoxicology, 2015)

Late Quaternary pollen records from the Yangtze River Delta, East China, and its implications for the Asian monsoon evolution - Yunfa Miao; Ping Zhang; Shengmei Lu; Xiaoying Wu; Lili Li; Huogen Chen; Xiangqian Li; Qiaoyin Miao; Wenli Feng; Jian Ou (Arabian Journal of Geosciences, 2015)

RETRACTED ARTICLE: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2015)

Characterizing and Differentiating Brain State Dynamics via Hidden Markov Models - Jinli Ou; Li Xie; Changfeng Jin; Xiang Li; Dajiang Zhu; Rongxin Jiang; Yaowu Chen; Jing Zhang; Lingjiang Li; Tianming Liu (Brain Topography, 2015)

Erratum to: Functional Characterization of a Putative Bacterial Wilt Resistance Gene (RE-bw) in Eggplant - Xiao Xi’ou; Li Guannan; Cao Bihao; Lei Jianjun; Chen Qinghua; Jiang Jin; Cheng Yujing (Plant Molecular Biology Reporter, 2015)

Functional Characterization of a Putative Bacterial Wilt Resistance Gene (RE-bw) in Eggplant - Xiao Xi’ou; Cao Bihao; Li Guannan; Lei Jianjun; Chen Qinghua; Jiang Jin; Cheng Yujing (Plant Molecular Biology Reporter, 2015)

Two novel CAII mutations causing carbonic anhydrase II deficiency syndrome in two unrelated Chinese families - Qianqian Pang; Xuan Qi; Yan Jiang; Ou Wang; Mei Li; Xiaoping Xing; Jin Dong; Weibo Xia (Metabolic Brain Disease, 2015)

Association of hypertension and obesity with renal cell carcinoma risk: a report from the Shanghai Men’s and Women’s Health Studies - Tian Shen; Xiao-Ou Shu; Yong-Bing Xiang; Hong-Lan Li; Hui Cai; Yu-Tang Gao; Wei Zheng; Loren Lipworth (Cancer Causes & Control, 2015)

Roles of miRNA-24 in regulating endothelial nitric oxide synthase expression and vascular endothelial cell proliferation - Wenyu Zhang; Limei Yan; Yumei Li; Wei Chen; Nan Hu; Hui Wang; Hesheng Ou (Molecular and Cellular Biochemistry, 2015)

The Endothelium as a Target for the Treatment of Heart Failure - Ou Yang; Jie Li; Jian Kong (Cell Biochemistry and Biophysics, 2015)

SecReT6 : a web‐based resource for type VI secretion systems found in bacteria - Jun Li; Yufeng Yao; H. Howard Xu; Limin Hao; Zixin Deng; Kumar Rajakumar; Hong‐Yu Ou (Environmental Microbiology, 2015)
Summary SecReT6 ( http://db‐mml.sjtu.edu.cn/SecReT6/ ) is an integrated database providing comprehensive information on type VI secretion systems ( T6SSs ) in bacteria. T6SSs are a class of sophisticated cell contact‐dependent apparatuses involved in mediating antagonistic or synergistic communications between bacteria and/or bacteria and eukaryotes. These apparatuses have recently been found to be widely distributed among G ram‐negative bacterial species. SecReT6 offers a unique, readily explorable archive of known and putative T6SSs , and cognate effectors found in bacteria. It currently contains data on 11 167 core T6SS components mapping to 906 T6SSs found in 498 bacterial strains representing 240 species, as well as a collection of over 600 directly relevant references. Also collated and archived were 1340 diverse candidate secreted effectors which were experimentally shown and/or predicted to be delivered by T6SSs into target eukaryotic and/or prokaryotic cells as well as 196 immunity proteins. A broad range of T6SS gene cluster detection and comparative analysis tools are readily accessible via SecReT6 , which may aid identification of effectors and immunity proteins around the T6SS core components. This database will be regularly updated to ensure its ongoing maximal utility and relevance to the scientific research community.

Lower Cambrian polychaete from China sheds light on early annelid evolution - Jianni Liu; Qiang Ou; Jian Han; Jinshu Li; Yichen Wu; Guoxiang Jiao; Tongjiang He (The Science of Nature, 2015)

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

Debris flow formation process and critical hydrodynamic conditions in the meizoseismal area of the Wenchuan earthquake - Jun Wang; Yan Yu; Hua-li Pan; Cheng Qiao; Guo-qiang Ou (Journal of Mountain Science, 2015)

Effect of dietary Chinese tea on growth performance, disease resistance and muscle fatty acid profile of channel catfish (Ictalurus punctatus) - Yao-bei-ping Zhang; Yi-bin Zhou; Ba-yi Sang; Xiao-chun Wan; Yan-ou Yang; Jian-li Zhang; Thomas L. Welker; Keshun Liu (Aquaculture International, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Prognostic Factors of Survival in Pathologic Incomplete Response Patients with Locally Advanced Breast Cancer After Neoadjuvant Chemotherapy - Ou Huang; Min Jiang; Xiao-song Chen; Jia-yi Wu; Wei-guo Chen; Ya-fei Li; Kun-wei Shen (Cell Biochemistry and Biophysics, 2015)

Association of variants on ADIPOQ and AdipoR1 and the prognosis of gastric cancer patients after gastrectomy treatment - Xuming Wu; Peizhan Chen; Yiyi Ou; Jibin Liu; Chenglin Li; Hui Wang; Fulin Qiang (Molecular Biology Reports, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

New versions of the BDS/GNSS zenith tropospheric delay model IGGtrop - Wei Li; Yunbin Yuan; Jikun Ou; Yanju Chai; Zishen Li; Yuei-An Liou; Ningbo Wang (Journal of Geodesy, 2015)

Mechanism of downcutting erosion of debris flow over a movable bed - Hua-li Pan; Jiang-cheng Huang; Guo-qiang Ou (Journal of Mountain Science, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Decomposition of China’s CO2 emissions from agriculture utilizing an improved Kaya identity - Wei Li; Qingxiang Ou; Yulu Chen (Environmental Science and Pollution Research, 2014)

Impact of Megacity Shanghai on the Urban Heat-Island Effects over the Downstream City Kunshan - Han-Qing Kang; Bin Zhu; Tong Zhu; Jia-Li Sun; Jian-Jun Ou (Boundary-Layer Meteorology, 2014)

Evolution characters of water exchange abilities between Dongting Lake and Yangtze River - Chaomin Ou; Jingbao Li; Yongqiang Zhou; Weiyan Cheng; Yan Yang; Zhonghua Zhao (Journal of Geographical Sciences, 2014)

Genistein Alleviates Radiation-Induced Pneumonitis by Depressing Ape1/Ref-1 Expression to Down-regulate Inflammatory Cytokines - Guo-Dong Liu; Lei Xia; Jian-Wu Zhu; Shan Ou; Meng-Xia Li; Yong He; Wei Luo; Juan Li; Qian Zhou; Xue-Qin Yang; Jin-Lu Shan; Ge Wang; et al. (Cell Biochemistry and Biophysics, 2014)

Synthesis and biological evaluation of 1-cyano-2-amino-benzimidazole derivatives as a novel class of antitumor agents - Zhang Hu; Lili Ou; Sidong Li; Lei Yang (Medicinal Chemistry Research, 2014)

Fully coupled time-domain simulation of dynamic positioning semi-submersible platform using dynamic surface control - Haizhi Liang; Luyu Li; Jinping Ou (Journal of Ocean University of China, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Use of different mooring models on global response analysis of an innovative deep draft platform - Dongsheng Qiao; Binbin Li; Jinping Ou (Journal of Ocean University of China, 2014)

In vitro study of nano-HA/PLLA composite scaffold for rabbit BMSC differentiation under TGF-β1 induction - Weimin Zhu; Kang Chen; Wei Lu; Qifeng Sun; Liangquan Peng; Wenzhe Fen; Hao Li; Yangkan Ou; Haifeng Liu; Daping Wang; Yanjun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2014)

CRTC3 polymorphisms were associated with the plasma level of total cholesterol and the risks of overweight and hypertriglyceridemia in a Chinese Han population - Zejin Ou; Guanghai Wang; Qiang Li; Zuliang Ma; Meng Dai; Fei Zou (Molecular Biology Reports, 2014)

Circulating cytokines and gastric cancer risk - Meira Epplein; Yong-Bing Xiang; Qiuyin Cai; Richard M. Peek; Honglan Li; Pelayo Correa; Jing Gao; Jie Wu; Angelika Michel; Michael Pawlita; Wei Zheng; Xiao-Ou Shu (Cancer Causes & Control, 2013)

Local scour and the laws of scour pit’s shape downstream of debris flow sabo dam - Hua-li Pan; Shun Yang; Guo-qiang Ou; Jiang-cheng Huang (Journal of Mountain Science, 2013)

Sciadopitysin: active component from Taxus chinensis for anti-Alzheimer's disease - Qiong Gu; Yanping Li; Yingchun Chen; Peifen Yao; Tianmiao Ou (Natural Product Research, 2013)

Fruit and vegetable intake and the risk of colorectal cancer: results from the Shanghai Men’s Health Study - Emily Vogtmann; Yong-Bing Xiang; Hong-Lan Li; Emily B. Levitan; Gong Yang; John W. Waterbor; Jing Gao; Hui Cai; Li Xie; Qi-Jun Wu; Bin Zhang; Yu-Tang Gao; et al. (Cancer Causes & Control, 2013)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Role of microRNA-21 in regulating 3T3-L1 adipocyte differentiation and adiponectin expression - Min Kang; Li-Mei Yan; Wen-Yu Zhang; Yu-Mei Li; An-Zhou Tang; He-Sheng Ou (Molecular Biology Reports, 2013)

Ecto-5′-nucleotidase (CD73) promotes tumor angiogenesis - Li Wang; Shaoxian Tang; Yingjian Wang; Siguang Xu; Jerry Yu; Xiuling Zhi; Zhouluo Ou; Jiayin Yang; Ping Zhou; Zhimin Shao (Clinical & Experimental Metastasis, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Antibacterial nanostructured composite films for biomedical applications: microstructural characteristics, biocompatibility, and antibacterial mechanisms - Fei-Peng Lee; Duen-Jeng Wang; Li-Kai Chen; Chun-Ming Kung; Yi-Chien Wu; Keng-Liang Ou; Chih-Hua Yu (Biofouling, 2013)

Microspore embryogenesis and production of haploid and doubled haploid plants in carrot (Daucus carota L.) - Jin-Rong Li; Fei-Yun Zhuang; Cheng-Gang Ou; Hong Hu; Zhi-Wei Zhao; Ji-Hua Mao (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Effect of Blast-Induced Vibration from New Railway Tunnel on Existing Adjacent Railway Tunnel in Xinjiang, China - Qingguo Liang; Jie Li; Dewu Li; Erfeng Ou (Rock Mechanics and Rock Engineering, 2013)

A Shortcut to the Optimization of Cellulase Production Using the Mutant Trichoderma reesei YC-108 - Zhong-li Yan; Xiao-hong Cao; Qing-dai Liu; Zhi-yan Yang; Yu-ou Teng; Juan Zhao (Indian Journal of Microbiology, 2012)

Dietary B vitamin and methionine intakes and lung cancer risk among female never smokers in China - Yumie Takata; Qiuyin Cai; Alicia Beeghly-Fadiel; Honglan Li; Martha J. Shrubsole; Bu-Tian Ji; Gong Yang; Wong-Ho Chow; Yu-Tang Gao; Wei Zheng; Xiao-Ou Shu (Cancer Causes & Control, 2012)

Identification of a novel C22-∆4-producing docosahexaenoic acid (DHA) specific polyunsaturated fatty acid desaturase gene from Isochrysis galbana and its expression in Saccharomyces cerevisiae - Tonglei Shi; Aiqun Yu; Ming Li; Xiuyuan Ou; Laijun Xing; Mingchun Li (Biotechnology Letters, 2012)

Extraction of line-of-sight ionospheric observables from GPS data using precise point positioning - BaoCheng Zhang; JiKun Ou; YunBin Yuan; ZiShen Li (Science China Earth Sciences, 2012)

Two-step method for the determination of the differential code biases of COMPASS satellites - Zishen Li; Yunbin Yuan; Hui Li; Jikun Ou; Xingliang Huo (Journal of Geodesy, 2012)

Primary culture of hemocytes from Eriocheir sinensis and their immune effects to the novel crustacean pathogen Spiroplasma eriocheiris - Tingming Liang; Hong Ji; Jie Du; Jiangtao Ou; Wenjie Li; Ting Wu; Qingguo Meng; Wei Gu; Wen Wang (Molecular Biology Reports, 2012)

Chromophore-assisted laser inactivation in neural development - Wei Li; Nico Stuurman; Guangshuo Ou (Neuroscience Bulletin, 2012)

Effects of the dispatch modes of the Three Gorges Reservoir on the water regimes in the Dongting Lake area in typical years - Chaomin Ou; Jingbao Li; Zhaoqing Zhang; Xichun Li; Guo Yu; Xiaohong Liao (Journal of Geographical Sciences, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Erratum to: Correlations of Trace Element levels in the Diet, Blood, Urine and Feces in the Chinese Male - Ying Wang; Yang-Li Ou; Ya-Qiong Liu; Qing Xie; Qing-Fen Liu; Quan Wu; Ti-Qiang Fan; Lai-Lai Yan; Jing-Yu Wang (Biological Trace Element Research, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Cloning and expression of the two new variants of Nav1.5/SCN5A in rat brain - Cheng-Tao Ren; Dong-Mei Li; Shao-Wu Ou; Yun-Jie Wang; Yi Lin; Zhi-Hong Zong; Masaki Kameyama; Asako Kameyama (Molecular and Cellular Biochemistry, 2012)

Lanthanide Salts of Heteropoly Molybdotungstosilicate LnHSiMo10W2O40·xH2O (Ln = Pr, Nd, Sm, Gd, Tb, Dy, Yb) Binding to Bovine Serum Albumin: A Fluorescence Quenching Study - Ai-Min Bai; Yu Ou-Yang; Hua-Li Yue; Xiao-Ling Li; Yan-Jun Hu (Biological Trace Element Research, 2012)

Determination of the specific interaction between palmatine and bovine serum albumin - Yu Ou-Yang; Xiao-Ling Li; Hong Wang; Min Fang; Yan-Jun Hu (Molecular Biology Reports, 2012)

Effects of SCR-3 on the immunosuppression accompanied with the systemic inflammatory response syndrome - Jun Li; Jie Niu; Shan Ou; Zhan-Yong Ye; Deng-Qun Liu; Feng-Chao Wang; Yong-Ping Su; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Implication of genetic variants near TMEM18, BCDIN3D/FAIM2, and MC4R with coronary artery disease and obesity in Chinese: a angiography-based study - Hao Huang; Zhi Zeng; Li Zhang; Rui Liu; Xian Li; Ou Qiang; Yucheng Chen (Molecular Biology Reports, 2012)

Correlations of Trace Element Levels in the Diet, Blood, Urine, and Feces in the Chinese Male - Ying Wang; Yang-Li Ou; Ya-Qiong Liu; Qing Xie; Qing-Fen Liu; Quan Wu; Ti-Qiang Fan; Lai-Lai Yan; Jing-Yu Wang (Biological Trace Element Research, 2012)

Grain-size characteristics and climate variability in TMS5e sequence of Tumen section in southern Tengger Desert, northwestern China - Xiaohao Wen; Baosheng Li; Fengnian Wang; Yanming Zheng; Dongfeng Niu; Yuejin Si; Xianjiao Ou (Chinese Geographical Science, 2012)

Identification and analysis of the gene cluster involved in biosynthesis of paenibactin, a catecholate siderophore produced by Paenibacillus elgii B69 - Yanping Wen; Xuechang Wu; Yi Teng; Chaodong Qian; Zhajun Zhan; Yuhua Zhao; Ou Li (Environmental Microbiology, 2011)
Summary Bacteria belonging to the genus Paenibacillus are recognized as rich sources of bioactive natural products. To date, there are few characterized siderophores from this genus. Here, through genome analysis, we identified a non‐ribosomal peptide biosynthetic gene cluster ( pae ) responsible for siderophore assembly in Paenibacillus elgii B69. The 12.8 kb gene cluster comprises six open reading frames encoding proteins similar to the components of the bacillibactin biosynthetic machinery and bacillibactin esterase. To examine the product of the pae gene cluster, we cultured P. elgii B69 in iron‐deficient medium for siderophore expression. A novel siderophore structurally similar to bacillibactin, designated paenibactin, was purified and characterized. Its structure was determined as a cyclic trimeric lactone of 2,3‐dihydroxybenzoyl‐alanine‐threonine. The involvement of the pae gene cluster in paenibactin biosynthesis was confirmed by the biochemical assay of adenylation domain specificity. Furthermore, we demonstrated that the pae gene cluster evolves from an ancestral bacillibactin biosynthetic gene cluster via sequence and phylogenetic analyses. The structural difference between paenibactin and bacillibactin may stem from a mutation‐induced change in the adenylation domain specificity. Based on these findings and published models for bacillibactin, we proposed models for paenibactin biosynthesis, ferric–paenibactin uptake and paenibactin‐bounded iron release.

Inhibitory effect of celecoxib in lung carcinoma by regulation of cyclooxygenase-2/cytosolic phospholipase A2 and peroxisome proliferator-activated receptor gamma - Ming Zhang; Zhi-Gang Xu; Zhuo Shi; Dan Shao; Ou Li; Wei Li; Zhi-Jun Li; Kai-Zhong Wang; Li Chen (Molecular and Cellular Biochemistry, 2011)

Isolation of a novel C18-Δ9 polyunsaturated fatty acid specific elongase gene from DHA-producing Isochrysis galbana H29 and its use for the reconstitution of the alternative Δ8 pathway in Saccharomyces cerevisiae - Ming Li; Xiuyuan Ou; Xiangdong Yang; Dongquan Guo; Xueyan Qian; Laijun Xing; Mingchun Li (Biotechnology Letters, 2011)

Systematic analysis of potato acid invertase genes reveals that a cold-responsive member, StvacINV1, regulates cold-induced sweetening of tubers - Xun Liu; Chi Zhang; Yongbin Ou; Yuan Lin; Botao Song; Conghua Xie; Jun Liu; Xiu-Qing Li (Molecular Genetics and Genomics, 2011)

Numerical study on global motion of Truss Spar in frequency and time domains for the Liwan 3-1 area - Lu Li; Binbin Li; Jinping Ou (Journal of Ocean University of China, 2011)

Modulation of the assay system for the sensory integration of 2 sensory stimuli that inhibit each other in nematode Caenorhabditis elegans - Yin-Xia Li; Yang Wang; Ya-Ou Hu; Ji-Xiang Zhong; Da-Yong Wang (Neuroscience Bulletin, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Spatial interpolation of daily precipitation in China: 1951–2005 - Deliang Chen; Tinghai Ou; Lebing Gong; Chong-Yu Xu; Weijing Li; Chang-Hoi Ho; Weihong Qian (Advances in Atmospheric Sciences, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Influence of CYP2C19 on the relationship between pharmacokinetics and intragastric pH of omeprazole administered by successive intravenous infusions in Chinese healthy volunteers - Yongqing Wang; Hongwen Zhang; Ling Meng; Meifeng Wang; Hongyu Yuan; Ning Ou; Haibo Zhang; Ziyan Li; Ruihua Shi (European Journal of Clinical Pharmacology, 2010)

Cationic liposome coupled endostatin gene for treatment of peritoneal colon cancer - Keng-Li Lan; Fu Ou-Yang; Sang-Hue Yen; How-Ling Shih; Keng-Hsin Lan (Clinical & Experimental Metastasis, 2010)

The pheV Phenylalanine tRNA Gene in Klebsiella pneumoniae Clinical Isolates Is an Integration Hotspot for Possible Niche-Adaptation Genomic Islands - Nan Chen; Hong-Yu Ou; Jon Jurriaan van Aartsen; XiaoFei Jiang; Min Li; ZeHua Yang; QuHao Wei; XiaoYun Chen; Xinyi He; Zixin Deng; Kumar Rajakumar; Yuan Lu (Current Microbiology, 2010)

Identification and characterization of a novel capsid protein encoded by Singapore grouper iridovirus ORF038L - Qing Jiao Wan; Jie Gong; Xiao Hong Huang; You Hua Huang; Sheng Zhou; Zheng Liang Ou-Yang; Jian Hao Cao; Li Li Ye; Qi Wei Qin (Archives of Virology, 2010)

Design approaches for active, semi-active and passive control systems based on analysis of characteristics of active control force - Jinping Ou; Hui Li (Earthquake Engineering and Engineering Vibration, 2009)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Fas expression on peripheral blood lymphocytes in systemic lupus erythematosus: relation to the organ damage and lymphocytes apoptosis - Lian-Hong Li; Wen-Xian Li; Ou Wu; Guo-Qing Zhang; Hai-Feng Pan; Xiang-Pei Li; Jian-Hua Xu; Hong Dai; Dong-Qing Ye (Molecular Biology Reports, 2009)

Family cancer history affecting risk of colorectal cancer in a prospective cohort of Chinese women - Gwen Murphy; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Michael Blaise Cook; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wei Zheng; Wong-Ho Chow (Cancer Causes & Control, 2009)

Isolation and characterization of new microsatellite markers from the burbot (Lota Lota) - Ying Y. Zhao; Jiao Li; Xiao W. Sun; Li Q. Liang; Xiao D. Zhu; Hong S. Ou-yang (Conservation Genetics, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Family history of malignancies and risk of breast cancer: prospective data from the Shanghai women’s health study - Briseis A. Kilfoy; Yawei Zhang; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wong-Ho Chow; Wei Zheng (Cancer Causes & Control, 2008)

Induction of nucleoside phosphorylase in Enterobacter aerogenes and enzymatic synthesis of adenine arabinoside - Xiao-kun Wei; Qing-bao Ding; Lu Zhang; Yong-li Guo; Lin Ou; Chang-lu Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Sedimentary characteristics of paleo-aeolian dune sands of Salawusu Formation in the Salawusu River Valley - Xianjiao Ou; Baosheng Li; Heling Jin; Guangrong Dong; David Dian Zhang; Zheng Wu; Xiaohao Wen; Lanhua Zeng; Chuntao Ouyang; Yi Yang; Yufei Liu (Journal of Geographical Sciences, 2008)

Cold events of Holocene indicated by primary elements distribution of the high-resolution sand dunes in the Salawusu River Valley - Dongfeng Niu; Baosheng Li; Shuhuan Du; Xiaohao Wen; Shifan Qiu; Xianjiao Ou; Yi Yang (Journal of Geographical Sciences, 2008)

RNA interference of ecto-5′-nucleotidase (CD73) inhibits human breast cancer cell growth and invasion - Xiuling Zhi; Sifeng Chen; Ping Zhou; Zhimin Shao; Li Wang; Zhouluo Ou; Lianhua Yin (Clinical & Experimental Metastasis, 2007)

Effects of Injection Systems and Plastic Mulches on Distribution and Emissions of Cis- and Trans-1,3-Dichloropropene and Chloropicrin - Li-Tse Ou; John E. Thomas; L. Hartwell Allen; Joseph C. Vu; Donald W. Dickson (Archives of Environmental Contamination and Toxicology, 2007)

Semiactive variable stiffness control for parametric vibration of cables - Hui Li; Wenli Chen; Jinping Ou (Earthquake Engineering and Engineering Vibration, 2006)

Deposition of sandstorms in a vegetation-covered sand dune in Ejin Oasis and its characteristics - Xiaohao Wen; Baosheng Li; Wei Wang; Sen Li; Xianjiao Ou; Yanming Zheng (Journal of Geographical Sciences, 2006)

Effects of Application Methods of Metam Sodium and Plastic Covers on Horizontal and Vertical Distributions of Methyl Isothiocyanate in Bedded Field Plots - Li-Tse Ou; John E. Thomas; L. Hartwell Allen; Joseph C. Vu; Donald W. Dickson (Archives of Environmental Contamination and Toxicology, 2006)

Analysis of DNA-Binding Activity of the JC Virus Minor Capsid Protein VP2 - Yih-Leh Huang; Meilin Wang; Wei-Chih Ou; Chiung-Yau Fung; Li-Sheng Chen; Deching Chang (Journal of NeuroVirology, 2003)

Degradation of 1,3-dichloropropene by a soil bacterial consortium and Rhodococcus sp. AS2C isolated from the consortium - Li-Tse Ou; John E. Thomas; Keun-Yook Chung; Andrew V. Ogram (Biodegradation, 2001)

Membrane permeability of fructose-1,6-diphosphate in lipid vesicles and endothelial cells - William D. Ehringer; Wenying Niu; Benjamin Chiang; Ou-Li Wang; Laura Gordon; Sufan Chien (Molecular and Cellular Biochemistry, 2000)

Influence of glass microbeads on growth, activity and morphological changes of Bacillus megaterium - Li-Tse Ou; Martin Alexander (Archives of Microbiology, 1974)